Dysregulated methylation of the human BOLL promoter hinders germ cell development from spermatogonia to spermatids - Tsung-Yen Lin; Hsing-Yi Chen; Yung-Hsuan Cheng; Chun-Wun Lu; Hsiu-Yen Ma; Hsiu-Chiung Hou; Yung-Ming Lin; Shih-Chieh Lin; Yu-Sheng Cheng (Molecular Biology Reports, 2026)

MEK inhibitor cobimetinib increases calreticulin and induces immune modulation in TNBC - Ling-Ming Tseng; Ka-Yi Lau; Ji-Lin Chen; Pei-Yi Chu; Chun-Teng Huang; Wan-Lun Wang; Yuan-Ya Chang; Jiun-I Lai; Chi-Cheng Huang; Ming-Shen Dai; Chun-Yu Liu (Journal of Molecular Medicine, 2026)
Immunogenic cell death (ICD) can activate immune cells and potentiate the response to immunotherapy. The mitogen-activated protein kinase (MAPK) signaling pathway regulates the immune response and mediates T-cell receptor signaling. Activation of the MAPK signaling pathway decreases the levels of tumor-infiltrating lymphocytes in triple-negative breast cancer (TNBC) and is associated with worse survival. Here, we investigated the potential of the MEK inhibitor cobimetinib as an ICD inducer in TNBC. We demonstrated that cobimetinib elicited hallmarks of ICD, including elevated levels of damage-associated molecular patterns. Ectopic ERK expression attenuated cobimetinib-induced CRT. Cobimetinib also evoked caspase-8 activation with increased Bax and Bak expression, while caspase inhibitor suppressed cobimetinib-induced CRT expression and apoptosis. In immunocompetent (BALB/c) mice bearing 4T1 tumors, cobimetinib exhibited stronger tumor growth inhibition than in immunodeficient (nude) mice, suggesting an immune-dependent antitumor effect. Furthermore, cobimetinib treatment increased the proportions of naïve CD8 + T cells and effector CD4 + T cells and decreases the proportion of myeloid-derived suppressor cells in immunocompetent mice bearing 4T1 tumors. Notably, we observed differential immunomodulatory effects of cobimetinib in tumor-bearing mice compared to non–tumor-bearing immunocompetent mice. Our findings indicate that MEK inhibition is associated with ICD-related molecular alterations, and that cobimetinib may contribute to immune modulation in TNBC.

N-glycan signatures of immunoglobulins-depleted serum proteins in colorectal cancer - Huiai Lu; Yuanyuan Liu; Yi Wang; Jiajing Lin; Liming Cheng; Xin Liu; Si Liu; at (Glycoconjugate Journal, 2026)

New perspectives on the role of oil-gas in mineralization of sandstone-hosted uranium deposits: Carbonate evidence from Yuejin Ⅱ, Qaidam Basin, China - Yi-Han Lin; Ming-Sen Fan; Pei Ni; Jun-Yi Pan; Jun-Ying Ding; Zhi-Lin Cheng; Zhao-Hui Li; Xue-Feng Gao; Ping Feng (Journal of Asian Earth Sciences, 2026)

Enhancement by Ce addition to La-Zr-mixed oxide supported Ni catalysts on the mid-temperature steam reforming of methane - Li-Chun Lin; Teng-Li Yu; Cheng-Yao Hung; Guan-Yu Chen; Yi-Ning Chao; Shawn D. Lin (Fuel, 2026)

Trace element concentrations and tissue distribution in cetaceans from different ecological groups in Chinese waters - Yaoyao Shi; Hao Cheng; Fanyu Lin; Yang Liu; Cai Lin; Yi Liu; Yan Tan; Qianhui Zeng; Yuke Zhang; Xianyan Wang; Liyuan Zhao (Environmental Pollution, 2026)

A dual mechanical tuning framework for rigid pillared elastic metamaterials: Geometric reconfiguration and controllable prestress - Zu Shao; Tong Cheng; Yi Zhang; Wei Zhong Jiang; Zhu Kun Mi; Xiang Jie Wei; Xin Guo; Wang Lin Xiong; Kai Hao Lin; Chuang Li; Shu Hao Song; Cheng Shen; et al. (Engineering Structures, 2026)

Seismic rehabilitation of severely earthquake-damaged ductile RC T-shaped beams using mechanically anchored CFRP strips: Anchorage requirements and experimental validation - Chien-Kuo Chiu; Yi-Feng Lin; Hsin-Fang Sung; Lung-Cheng Hsieh (Engineering Structures, 2026)

An auxetic trampoline metamaterial with tunable bandgap under prestrain - Tong Cheng; Gui Lei Chen; Wei Zhong Jiang; Yi Zhang; Xiang Jie Wei; Zhu Kun Mi; Xiao Ji; Lin Hua; Jia Hui Zhang; Shu Hao Song; Cheng Shen; Xin Ren (Engineering Structures, 2026)

How do non-emergency medical transportation services influence patients’ subjective well-being? - Maryam Yousefibaseri; Yi-Ling Cheng; Jane Lin (Transportation Research Part D: Transport and Environment, 2026)

Hypurpurins A-P, furanolabdane diterpenoids from the aerial parts of Hypoestes purpurea and their bioactivities - Lin-Fen Ding; Bin Cheng; Mei-Yi Zhang; Shi-Huan Yin; Xin-Ying Wang; Lu Sai; Hui-ling Zhou; Xuan Jiang; Jia Su; Xing-De Wu (Phytochemistry, 2026)

Chalcopyrite as an indicator of uranium mineralization in the Qigequan deposit, western Qaidam Basin: Constraints from mineralogy, geochemistry, and sulfur isotopes - Yi-Han Lin; Ming-Sen Fan; Pei Ni; Jun-Yi Pan; Jun-Ying Ding; Wen-Yi Wu; Chen Zhang; Zhe Chi; Zhi-Lin Cheng; Bin Guo; Yi-Fan Gao (Journal of Geochemical Exploration, 2026)

Persistence of a high-risk opportunistic pathogen amid compartment-resolved antibiotic resistance attenuation in acute shock-loaded micro-wetlands - Rong-min Zhang; Zi-yao Liu; Hui-ting Chen; Xin-ce Yang; Liwei Shi; Yi-cheng Zhang; Xin-ting Li; Lin-lin Yang; Jing-yu Xu; Xin-lei Lian; Li Li; Xian-hui Huang; et al. (Journal of Environmental Chemical Engineering, 2026)

Chemical-free closed-loop conversion of nitrate into struvite fertilizer via exsolved high-entropy perovskite electrocatalyst - Li-Hui Yang; Yi-Heng Liu; Si-Hao Lv; Man-Ting Liao; Hui Lin; Wei Li; Cao Yang; An-Qi Wang; Hao-Yi Cheng (Journal of Environmental Chemical Engineering, 2026)

Divergent activation of a glutathione-tryptophan module by cysteine and hydrogen sulfide enables metabolic recovery from cyanide poisoning in rice - Yi Kang; Xing-Hui Feng; Cheng-Zhi Li; Yu-Juan Lin; Xiao-Zhang Yu (Journal of Environmental Chemical Engineering, 2026)

Corrigendum to “Multi-omics insights into flavor compounds production and constipation-relieving benefits of different Lactiplantibacillus plantarum-fermented cereal beverages” [Food Res. Int. 217 (2025) 116764] - Wen-Jie Jiang; Ya-Xin Jiang; Lin Cheng; Yu-Chen Ning; Jia-Yi Hou; Fei-Liang Zhong; Ting Yuan; Xue-Gang Luo (Food Research International, 2026)

Unraveling the modulating mechanism of Maillard reaction gradients on structural properties and emulsifying stabilization of Prunus mume melanoidins - Wen-zhang Qian; Yi-xiao Xiao; Shou-wei Yin; Ji-cheng Chen; Jin-lin Guo; Shun Gao (Food Chemistry, 2026)

W1/O/W2 emulsion stabilized by β-lactoglobulin/exopolysaccharides/epigallocatechin gallate complex: Protective effects on Lactobacillus plantarum A81 during storage, pasteurization and gastrointestinal digestion - Cuicui Duan; Yi Zhang; Hongru Wang; Siyang Sui; Hui Liu; Cheng Wu; Lin Ma; Fumin Ma; Xiaolei Li; Dan Li (Food Chemistry, 2026)

Tailoring Cu-doped SmMn2O5 with rich Mn4+ active sites for highly efficient and selective ultra-low temperature photothermal NOx catalytic reduction - Mingxia Wu; Jiale Cheng; Yu Wang; Siying Zhang; Yi Li; Ruixue Bai; Chunming Yang; Lin Liu; Feng Fu; Jun Wan (Chemical Engineering Journal, 2026)

Mechanobiological antagonism of integrin β1/β3 gates YAP-driven reactionary dentinogenesis through fluid shear stress sensing - Peiqi Liu; Hui Zhang; Haoyu Wang; Jingning Gou; Lingxiang Lian; Bilun Jin; Yi Guo; Wei Gong; Chenxu Wang; Yijie Wang; Rui Zou; Bo Cheng; et al. (Chemical Engineering Journal, 2026)

Phylogenomics, reticulate evolution, and taxonomic revision of East Asian Cardamine (Brassicaceae) in the Hengduan biodiversity hotspot - Jia-lu Li; Dan-hui Liu; Jiang-lin Miao; Yi He; Liao-cheng Zhao; Di Zhang; Ke-ping Ma; Quan-ru Liu (Molecular Phylogenetics and Evolution, 2026)

Tuning the pore architecture of HKUST-1 via Polyvinylpyrrolidone for superior CH4 capture - Bin Zhou; Yanlin Chen; Zhen Wang; Haifei Lin; Haiqing Shuang; Zeyou Meng; Liang Cheng; Yi Zhang; Qiqi Yin (Chemical Engineering Journal, 2026)

First visualization of intact sperm storage tubules in the duck oviduct: A fluorescent labeling approach for targeted SST sampling - Hsiu-Lien Herbie Lin; Chin-Hui Su; Shih-Yi Huang; Ya-Hsin Kuo; Liang-Yuan Wei; Yi-Ying Chang; Ching-Wei Chang; Jeng-Fang Huang; Pascal Mermillod; Chih-Hsiang Cheng (Animal Reproduction Science, 2026)

Hydraulic conductivity and the associated xylem anatomy as reliable predictors of tree productivity for Populus species along the fast-slow spectrum - Attaullah Khan; Xue-Wei Gong; Jing-Jing Guo; Cheng-Lin Yuan; Shen-Hao Song; Zhong-Yi Pang; Yan-Hui Peng; Xue-Kai Sun; Guang-You Hao (Agricultural and Forest Meteorology, 2026)

Mobilized-clay-driven toppling: A new mechanism resolving the “energy paradox” of under-dip slope failure in flysch terrains - Thanh-Tùng Nguyễn; Ivo Baroň; Filip Hartvich; Jiří Havlík; Lenka Kociánová; Jan Klimeš; Jan Černý; Martin Šutjak; Václav Dušek; Cheng-Han Lin; Chia-Han Tseng; Yi-Chin Chen; et al. (Landslides, 2026)

Reclamation to aquaculture ponds accelerates losses of Fe-bound organic carbon in estuarine wetlands - Junma Chen; Liwen Cheng; Yunying Fang; Ji Chen; Weiqi Wang; Yi Zheng; Shiyu Chen; Lin Wang; Jordi Sardans (Water Research, 2026)

Minutes-long soft X-ray prompt emission from a compact object merger - An Li; Chen-Wei Wang; Niccolò Passaleva; Jie An; Bin-Bin Zhang; Eleonora Troja; Yi-Han Iris Yin; Yuan Liu; Shao-Lin Xiong; Li-Ping Xin; Yi-Xuan Shao; Jun Yang; et al. (Science Bulletin, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Late Holocene human-environment interactions on a small island of the Taiwan Strait - Ranjan Kumar Mohanty; Abdur Rahman; Yi-Chen Ho; Yu-Chen Lu; Cheng-Tao Lin; Hung-Chun Chao; Ling-Ho Chung; Chin-Yung Chao; Liang-Chi Wang (Quaternary International, 2026)

Undescribed phenylspirodrimane dimers with anti-gouty activity from the coral-derived fungus Stachybotrys chartarum - Shuang Lin; Yi-Fan Geng; Hanxiao Zeng; Zixue Chai; Baolei Fan; Jun-Cheng Su; Yonghui Zhang; Zhengxi Hu (Phytochemistry, 2026)

Differential thermal sensitivity among shallow-water octocorals and its association with holobiont composition - Hsien-Yu Cheng; Yu-Chien Wang; Yan-Zhen Meng; Chien-Yi Wu; An-Chi Liu; Yen-Chih Lin; Jui-Hsun Hung; Shan-Hua Yang (Marine Environmental Research, 2026)

Caffeinated chewing gum improves military performances in special forces soldiers - Yi-Jie Shiu; Che-Hsiu Chen; Hung-Yu Lin; Chia-Cheng Yang; Chi-Wen Yen; Han-Yuan Chang; Hsuan-Ta Chen; Chih-Hui Chiu (European Journal of Applied Physiology, 2026)

Two new chroman derivatives from the desert plant endophytic fungus Lasiodiplodia sp - Wen-Xiang Tao; Jin Ye; Lin-Ping Zhang; Le Zhang; Dong-Yang Liu; Xiu-Feng Yang; Tian-Cheng Ma; Yi Sun; Chang Zhang; Fan-Wei Liu; Ying Chen; Bo Song (Natural Product Research, 2026)

H3K18 lactylation-regulated ATG10 is involved in the acute respiratory distress syndrome induced by acute exposure to hydrogen sulfide through activation of autophagy in lung epithelial cells - Bingyu Ling; Ping Geng; Bowen Fan; Xiaolong Wu; Yi Yang; Jiaheng Lin; Wenjie Li; Qizhan Liu; Cheng Cheng; Jinsong Zhang; Hao Wu (Journal of Hazardous Materials, 2026)

Scale up fermentation of Chenopodium formosanum dairy products with process optimization and evaluation of ACE inhibitory peptides and antioxidant activity - Chen-Che Hsieh; Jing-Rong Wu; Yi-Cheng Huang; Shin-Ping Lin; Jheng-Jhe Lu; Adyasa Barik; Shella Permatasari Santoso; Chang-Wei Hsieh; Hui-Wen Lin; Kuan-Chen Cheng (Food Bioscience, 2026)

Phenotype-independent bioorthogonal capture system eliminates circulating tumor cells and tumor-derived exosomes in whole blood - Yangze Ji; Xiaojie Wang; Yulin Wang; Shaowen Zhou; Jiong Yang; Tianjiao Zhou; Yi Wang; Xian Wu Cheng; Lei Xing; Hu-Lin Jiang (Chemical Engineering Journal, 2026)

Virulensome: a transient organelle mediating fungal virulence - Pei-Ji Zhao; Qian-Yi Hu; Si-Han Wang; Cheng-Song Wang; Xue-Xian Jian; Xing-Fu Wen; Yu-Lin Luo; Ya-Qi Zhang; Chun-Mei Xiang; Guo-Hong Li; Shu-Qun Liu; Ming-He Mo; et al. (Science China Life Sciences, 2026)

SYVN1-provoked RASA1 ubiquitination promotes pulmonary inflammation in chronic obstructive pulmonary disease - Ju-Hong Wu; Yi-Cheng Ma; Yu-Qi Wang; Hai-Long Miao; Meng-Xue Liu; Dong-Xu Hua; Min-Min Tang; Tian-Rui Sui; Zhi-Yong Wu; Yu Wang; Jin Yang; Hui Zhao; et al. (Inflammation Research, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Process-intensified synthesis of sulfonated peanut shell char through dilute acid hydrolysis and low-temperature sulfonation–carbonization for Pb2 + removal - Maria Stefani; Kuan-Chen Cheng; Theresia Angeline Veronica; Shella Permatasari Santoso; Edward Hartman Ernest; Shin-Ping Lin; Jindrayani Nyoo Putro; Wiyanti Fransisca Simanullang; Hsien-Yi Hsu; Chang-Wei Hsieh; Suryadi Ismadji (Journal of Environmental Chemical Engineering, 2026)

Dynamic Equivalent Drainage Method for Urban Flood Modeling: A Rainfall-adaptive Fusion Approach - Ming Wu; Yuqin Gao; Yaya Cheng; Xiao Chen; Jingang Zhang; Lin Yi (Water Resources Management, 2026)

Neutrophil extracellular traps in post-traumatic urethral microenvironment promote hypertrophic urethral stricture via the TLR9/NF-kB/Smad3/IL-8 axis - Ye-Hui Chen; Zhi-Bin Ke; Bo-Han Lin; Yi-Cheng Xu; Xue-Yi Xue; Qing-Shui Zheng; Xiong-Lin Sun; Yong Wei; Ying-Chun Liang; Ning Xu (Apoptosis, 2026)

Tracing the evolution of granitic magmas revealed by fayalite–ferrosilite-bearing microgranular enclaves in Jiuyishan area of South China Block - Jing-Yi Liu; Quan Ou; Jian-Qing Lai; Feng Zi; Kun Wang; Wen-Zhou Xiao; Zhi-Cheng Lin; Cui-Yun Wang; Qian-Cheng Feng; Jia Liao (Acta Geochimica, 2026)

Multiprotein-based nanomedicines with dual CD44/CD133 targeting and GSH-responsive drug release for improving cancer chemotherapy - Lu-Yi Yu; Pei-Wei Shueng; Yu-Hsin Wang; Yu-Wei Yen; Kuan-Wei Chen; Chieh-Ru Li; Hsin-Cheng Chiu; Yu-Wen Lin; Chun-Liang Lo (Drug Delivery and Translational Research, 2026)
Albumin, a highly biocompatible protein, has been utilized in the construction of anti-cancer drugs for the treatment of various cancers. However, albumin-based nanomedicines still face several clinical challenges, including low stability in the bloodstream, non-specific targeting ability, and lack of controlled release capability. To address these limitations, we developed a multiprotein-based nanomedicine for targeted chemotherapy of non-small cell lung cancer (NSCLC). This nanomedicine was assembled using a heart-shaped albumin and two Y-shaped anti-CD44 and anti-CD133 antibodies. To enhance stability and improve therapeutic efficacy, the multiproteins were crosslinked using disulfide bond linkers and loaded with paclitaxel and ceramide. This resulted in nanomedicines that exhibited responsiveness to glutathione (GSH) and demonstrated inhibition of tumor cancer cells and cancer stem cells (CSCs). Our experimental results indicated that the inclusion of anti-CD44 and anti-CD133 antibodies enhanced the targeting capability of nanomedicines towards cancer cells and CSCs in an in vitro study and the accumulation in both normoxic regions and hypoxic niches in in vivo tumor xenografts. The multiprotein-based nanomedicines also demonstrated GSH-dependent drug release behavior, induced apoptosis in cancer cells and CSCs, inhibited cell migration, and effectively suppressed NSCLC tumor growth. Overall, our findings presented a novel nanostructure created from differently shaped proteins for application in drug delivery. This multiprotein-based nanomedicines showed promising potential in addressing the limitations of albumin-based nanomedicines and may offer improved therapeutic outcomes for cancer treatment. Graphical Abstract

Non-radical PMS activation for simultaneous nitrite and sulfamethoxazole removal with inhibited nitrobyproduct formation - Jiawei Lin; Wenjun Zhou; Jiaqi Peng; Yongyou Hu; Hongfeng Zhang; Cheng Zhao; Qi Shan; Hao Zhou; Yi Yin (Journal of Water Process Engineering, 2026)

Transition metal-loaded granular activated carbon as efficient three-dimensional electrode for humic acid removal - Jianhong Jiang; Man Yang; Min Huang; Xinyao Guo; Xia Tao; Li Xu; Yue Lu; Lin Tang; Yi Cheng (Journal of Environmental Sciences, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Effective metal recovery from lithium-ion battery waste using a ternary deep eutectic solvent in a high solid-to-liquid ratio under mild and ambient conditions - Hsin-Jou Cheng; Yi-Jane Lin; Shu-Chi Chang; Shih-Yen Yang; Ting-Wei Lee; Chiaying Chen (Journal of Environmental Chemical Engineering, 2026)

Microbial-assisted copper migration stabilizes Fe/Cu cathodes for long-term bioelectro-Fenton degradation of bisphenol A - Chi-Wen Lin; Yu-Cheng Chiang; Hui Suan Ng; Shu-Hui Liu; Yi-Kai Yang (Journal of Environmental Chemical Engineering, 2026)

Genetic Diversity of Spodoptera litura in China Based on Mitochondrial DNA Analysis - Yu-Lin Li; Jian-Kun Long; Zhi-Ming Chang; Han-Cheng Wang; Jian-Yu Meng; Lin Yang; Jun-Yi Gao; Xiang-Sheng Chen (Phytoparasitica, 2026)

Tracing fluid evolution forming multistage wolframite mineralization in vein-type tungsten (-tin) deposit: new insight from LA-ICP-MS analysis of fluid inclusion - Zhi-Lin Cheng; Jun-Yi Pan; Pei Ni; Li-Li Chen; Jian-Ming Cui; Zhe Chi; Jun-Ying Ding (Mineralium Deposita, 2026)

A national-scale early detection and rapid response (EDRR) to invasive cane toads (Rhinella marina) in Taiwan - Yung-Chih Lai; Chun-Fu Lin; Li-Mien Tseng; Cheng-En Li; Jia-Han Lee; Jou-Yun Chen; Ming-Chih Wang; Chun-Hung Lai; Yueh-Feng Chen; Chun-Lin Ho; Wei-Chun Cheng; Yi-Ju Yang (Biological Invasions, 2026)

Targeting PTGS2/NF-κB Pathway: MG-132’s Role in Reducing Ischemic Stroke Injury - Yong-Sheng Wang; Yuan-Cheng Huang; Yong-Qi Wang; Yi-Xuan Zheng; Ying-Ren Gao; Min-Xia Wu; Fang-Hong Gao; Hong-Zhang Wang; Kun Liu; Lin Yan (Biochemical Genetics, 2026)

Application of ENU-mediated efficient mutagenesis in breeding of the big belly seahorse (Hippocampus abdominalis) - Xiao-lei Su; Chun-yu Hou; Lin Shi; Shi-chang Zhang; Cheng-de Fan; Jie-zhou Wang; Yi-cong Ma; Wu-hong Lv; Cong Liu; Guo-dong Zheng; Kai Wang (Aquaculture, 2026)

Development of an artificial intelligence (AI) marine scientific research model: The case of marine science and technology policy and its legitimate practice in Taiwan - Juei-Cheng Jao; Chiao-Wen Lin; Pin-Chien Chen; Yi-Cheng Chang; Yi-Juen Chen; Wen-Hong Liu (Marine Policy, 2026)

Bisphenol AP promotes pulmonary fibrosis by regulating macrophage function in a bleomycin-induced mouse model - Ze Chen; Zhenying Lin; Meng Ni; Baihe Li; Qianqian Zhang; Zelin Cao; Wei Li; Yanan Tang; Dongting Yao; Chunyu Cheng; Yi Hu; Xiaorui Liu; et al. (Toxicology, 2026)

A novel mechanism of uranium mineralization: The role of zircon adsorption at the Qigequan deposit, Qaidam Basin, NW China - Yi-Han Lin; Ming-Sen Fan; Pei Ni; Jun-Yi Pan; Zhe Chi; Zhi-Lin Cheng; Wen-Yi Wu; Chen Zhang; Bing-De Qi; Xue-Bin Wei (Sedimentary Geology, 2026)

Integrating the cognitive-affective-conative model and stress appraisal theory for adventure tourism: The impact of challenge perception and motivation on revisit intention - Lu-Ping Lin; Nien-Te Kuo; Kuo-Chien Chang; Yi-Sung Cheng (Journal of Outdoor Recreation and Tourism, 2026)

Low doses of chlorothalonil cause testicular impairment in mammals through the antimicrobial-like mechanism - Han-Zhang Wang; Yi-Ming Xiong; Shi-Lin Song; Qian-Cheng Zhao; Xuan-Yue Chen; Jing-Ran Gao; Yuan-Yuan Li; Zhan-Fen Qin (Journal of Hazardous Materials, 2026)

Inhibitory activity of dehulled adlay extrudate against ethanol-induced gastric mucosal injury and stability tests of active indicative components - Ming-Yi Lee; Shih-Min Hsia; Ching-I Lin; Yu-Chia Chang; Yi-Hsiang Liang; Lu-Chi Chan; Ju-Tsui Lin; Yi-Fen Chiang; Wei-Chih Sun; Cheng-Pei Chung (Journal of Cereal Science, 2026)

Synergistic co-preintercalation of nickel and aluminum ions into vanadium oxide hydrate as positive electrode material in ultrahigh-rate and high-capacity aqueous zinc-ion batteries - Hung-Lin Chen; Tsung-Yi Chen; En-Hao Li; Yen-Lin Chen; Wen-Hsuan Lu; Hsu-Chen Cheng; Shu-Yu Chen; Jue-Hua Pan; Hsiang-Jung Chen; Syuan-Cen Lin; Ruey-An Doong; Sanna Gull; et al. (Chemical Engineering Journal, 2026)

Physiological responses of maize (Zea mays L.) seedlings to the B chromosome - Nai-Yuan Cheng; Yi-Ting Hsu; Tzu-Che Lin; Ya-Ming Cheng (The Nucleus, 2026)

Multi-source remote sensing for spatial mapping of salt-affected agricultural soils in Taiwan - Nguyen-Thanh Son; Chein-Hui Syu; Chi-Farn Chen; Cheng-Ru Chen; Huan-Sheng Lin; Yi-Ting Zhang; Tsang-Sen Liu; Chun-Chien Yen (Applied Geomatics, 2026)

A review of Potentilla discolor Bunge: ethnomedicinal uses, phytochemistry, and pharmacology - Tong Shen; Jia-Cheng Xie; Yi-Lin He; Hong-Ying Yang (Advances in Traditional Medicine, 2026)

The interplay between antihypertensive medication and lifestyle with cardiovascular outcomes in patients with hypertension: the PURE-China study - Biyan Wang; Zhiguang Liu; Tong Bu; Sumathy Rangarajan; Qiuyan Ma; Xiaocong Li; Qi Qiu; Yang Lin; Lap Ah Tse; Bo Hu; Salim Yusuf; Qiujing Cai; et al. (EPMA Journal, 2026)

Captive breeding and early development of tank-reared lyretail anthias Pseudanthias squamipinnis (Peters, 1855): Assessments of hatching success, larval survival, and ontogeny - Ting-Chan Chou; Ang Lu; Yi-Yang Lin; Cheng-Chieh Wu; Hei-Wan Wong; Ho-Fai Yik; Bo-Kai Liao; Hong-Yi Gong; Yen-Ju Pan (Aquaculture, 2026)

Pore size of woven slit-film geotextiles subjected to unequal biaxial tensile strains obtained from wet sieving tests - Lin Tang; Kun Tu; Yi Cheng Hu; Wen Ming Shen; Yi Wang (Geotextiles and Geomembranes, 2026)

Influence of xanthan gum and guar gum on the gelation and structural properties of carboxylated cellulose nanofibers-based emulsion gels - Yanyan Cheng; Jieqiong Lin; Yi Luo; Jinzhou Xiao; Weiqi Fei; Jiajun Song; Huiliang Wen; Jianhua Xie (Food Hydrocolloids, 2026)

Sonofoam: An ultrasound-responsive foam for broad pleural coverage and sonoporation-enhanced drug delivery in pleurodesis - Hsin-Yi Lin; Wei-Chih Liao; Yun-Chieh Lin; Hsin-Chin Li; Min-Yu Tsou; Bo-Tai Cheng; Yu-Nan Huang; Ulziijargal Sukhbat; Chun-Yi Chiang; Chi-Fen Chuang; Zong-Han Hsieh; Chih-Yen Tu; et al. (Chemical Engineering Journal, 2026)

Microbial mechanisms of arbuscular mycorrhizal fungi in mitigating nitrous oxide emissions via regulating nitrogen metabolism in constructed wetlands - Xiang-Long He; Liang-Cheng Lin; Yi-Hao Li; Yu-Quan Zhong; Hao Xu; Jing-Wen Li; Can Liu; Jun-Feng Wang (Chemical Engineering Journal, 2026)

Melatonin suppresses glycolysis and coordinately disrupts DNA repair via targeting the YAP1-NAMPT signaling in breast cancer - Yi-Wen Lai; Cheng-Ying Chu; Zei-Wei Liu; Hsin-Ying Lu; Chi-Ching Lee; Mei-Hsiang Lin; Cheng-Wei Lin (Chemico-Biological Interactions, 2026)

Regulation of grain protein content by the amino acid permease gene OsAAP4 in rice - Ming-Xin Li; Feng-Lin Huang; Jin-Hong Lin; Jia-Yi Qu; Guo-Feng Wan; Gen-Cai Song; Jing Zhao; Yan Peng; Zhen-Ning Teng; Ling Liu; Cheng Zheng; Hou-Xiong Wu; et al. (Theoretical and Applied Genetics, 2026)

Correction to: Determination of critical power in trained rowers using a three-minute all-out rowing test - Ching-Feng Cheng; Yi-Shan Yang; Hui-Mei Lin; Chia-Lun Lee; Chun-Yi Wang (European Journal of Applied Physiology, 2026)

Disease outbreaks substantially enhance greenhouse gas emissions from Asian seabass (Lates calcarifer) aquaculture pond - Han-Yang Yeh; Chien-Wei Tu; Yi-Jung Chen; Wen-Ping Cheng; Pei-Yu Shih; Chia-Chia Yu; Wei-Sheng Zhang; Wei-En Hung; Yu-Ru Lin; Zhen Hao Liao; Wen-Chen Chou; Hsiao-Chun Tseng; et al. (Marine Pollution Bulletin, 2026)

Combined exposure to microplastics and cadmium alters gut microbiota composition in preschool children: A cross-sectional study - Chi-Sian Kao; Chuen-Bin Jiang; Chih-Chieh Yang; Ying-Lin Wang; Yi-Hua Chen; Hsing Jasmine Chao; Hsing-Cheng Hsi; Ling-Chu Chien (Journal of Hazardous Materials, 2026)

Electrochemical detection and electro-Fenton degradation of fipronil via Fe/Ni-BTC/MS-derived NiFe2O4@C core-shell catalyst - Yu-Qing Zhan; Cheng-Guo Liu; Jia-Jia Kou; Yi-Lin Niu; Hai-Jiao Xie; Liu Yang; Dashu Chen (Journal of Cleaner Production, 2026)

Dibifree, a dietary phytomix, improves glycemic control and adiposity via modulation of the gut–pancreas–adipose–immune axis in type 2 diabetes - Tzu-Yi Huang; Niann-Tzyy Dai; Hsiu-Jung Liao; Ly Hien Doan; Tai-Shan Cheng; Wen-Yu Hsieh; I-Hsuan Lin; Yu-Tang Huang; Chia-Ching Liaw; Hsiao-Sheng Liu; Wei-Ming Cheng; Chun-Li Su; et al. (Food Research International, 2026)

From genes to products: High-efficiency biosynthesis and holistic optimization strategies for monounsaturated fatty acids - Lu-Wei Xu; Yan-Cheng Lin; Yi-Ting Shen; Xin Qi; Zi-Xu Zhang; Wang Ma; Xiao-Man Sun (Food Microbiology, 2026)

Coupled CFD-DEM modeling of fine particles and fibers migration and clogging mechanisms in bridging regions - Ran Lin; Yinjian Huang; Jinzhou Zhao; Lan Ren; Zhihao Yu; Zhiqiang Li; Jianfa Wu; Yi Song; Cheng Shen (Computers and Geotechnics, 2026)

Electrochemically activated polypyrrole for full-polymer electrochemical deionization: Unraveling potential-gated ion exchange behavior and its application to oxyanion removal - Hung-Yi Huang; Yi-Heng Tu; Yi-An Chen; Cheng-Wei Lin; Yu-Hung Cheng; Hsing-Mei Chou; Yu-Hsiang Yang; Yun Ku; Zhiyin Yang; Sophia Uemura; Hsin-Lung Chen; Richard B. Kaner; et al. (Chemical Engineering Journal, 2026)

Isomeric halide engineering of self-assembled hole-selective layers for efficient indoor perovskite photovoltaics - Zhong-En Shi; Yi-Ting Hong; Cheng-Chieh Lu; Po-Cheng Shih; Shih-I Lu; Hsiao-Chi Hsieh; Sie-Rong Li; Yu-Che Lin; Zheng-Xuan Cai; Yan-Duo Lin; Chih-Ping Chen (Chemical Engineering Journal, 2026)

Deep Shale Matrix Permeability Evolution During Well Shut-In Under True Triaxial Stress - Jinzhou Zhao; Yanshan Guo; Zhihao Yu; Lan Ren; Ran Lin; Jianfa Wu; Yi Song; Cheng Shen (Rock Mechanics and Rock Engineering, 2026)

Brain Tissue-Derived Exosomal Proteomics Identifies Chemotaxis-Associated Protein Changes After Traumatic Brain Injury: An Exploratory Hippocampal Transcriptomic Comparison - Wei-can Chen; Xin-li Chen; Cheng-ye Lin; Yang-zi Huang; He-fan He; Yi-lin Zhou; Yi-bin Liu (Molecular Neurobiology, 2026)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

Population structure of Tachypleus tridentatus in Xiamen Bay: Proposing a network of transboundary marine protected areas - Yi-Hua Jin; Yi-Jia Shih; Hsin-I. Lin; Ya-Hui Chen; Yung-Sheng Cheng; Chia-Fa Lee; Yang-Chi Chang; Yi Chang (Regional Studies in Marine Science, 2025)

Nonlinear dynamics of rotating graphene-reinforced composite blades under 1:2 internal resonance in fluid-submerged environments - Yi-Han Cheng; Gui-Lin She (Ocean Engineering, 2025)

The effects of active surface morphing on the propulsive performance and acoustic characteristics of a flapping foil - Chun-yu Guo; Lei Jin; Guang-yu Shi; Lin Cai; Lu-cheng Sun; Yi-jie Sun (Ocean Engineering, 2025)

Temperature-dependent expression profiling of 16 HSP genes across developmental stages in Frankliniella occidentalis - Lin Shu; Yi-Jie Ma; Yu-Cheng Wang; Ya-Wen Chang; Yu-Zhou Du (Journal of Thermal Biology, 2025)

Physicochemical properties on the bone of hairtail (Trichiurus lepturus) under various treatments of cooking pressure and vinegar - Huey-Jine Chai; Shang-Ta Wang; Yun-En Chung; Yi-Ting Pan; Yu-Cheng Lin; Wen-Chieh Sung (International Journal of Gastronomy and Food Science, 2025)

New insights into the mechanism of quick-freezing reducing blueberry flavor loss: Coupling cellular microstructure maintenance and fatty acid metabolism regulation - Haiying Yang; Jia Guo; Shuhua Lin; Lvhong Huang; Xiaomei Cheng; Wenzhi Yi; Rongrong Wang; Yang Shan; Ning Jiang; Shenghua Ding (Food Research International, 2025)

Machine learning intelligently selects feature values to construct a sensor array based on tri-functional Mn-doped covalent organic polymer nanozymes for identifying flavonoid compounds - Guo-Qi Zhang; Wen-Cai Jiang; Xiao-Mei Li; Ren-Jie Li; Yi Feng; Ri-Ge Li Nai; Hui-Lin Cheng; Zhi-Bo Hou; Xiao-Jun Luo; Yan Zhao (Food Chemistry, 2025)

Mechanical performance of an assembled 3D auxetic hybrid structure under eccentric and axial compression - Jia Shuo Liu; Yi Zhang; Xiang Jie Wei; Wei Zhong Jiang; Meng Li Xue; Yi Chao Qu; Tao Ding; Jia Hui Zhang; Lin Hua; Tong Cheng; Xin Ren (Engineering Structures, 2025)

An enhanced nanoenzyme for remodeling the inflammatory microenvironment and low-temperature photothermal cascade therapy for rheumatoid arthritis - Sui Zhou; Yong Li; Yi-Tong Zhou; Meng-Wen Ma; Kai-Lin He; Kai Cheng; Jin-Xuan Fan; Bo Liu; Ling-Li Dong; Yuan-Di Zhao; Xin Liu (Chemical Engineering Journal, 2025)

Structural characterization and immunomodulatory activity of a novel pectin polysaccharide extracted from Gardenia jasminoides fruit - Yue Guo; Yanan Cheng; Bing Zheng; Jianhua Xie; Yi Chen; Huasi Lin; Hui Liu; Xiaobo Hu; Qiang Yu (Carbohydrate Polymers, 2025)

Identification, characterization, and expression profiling of rice MADS-box transcription factor genes associated with fluroxypyr-meptyl and oxyfluorfen metabolism - Zhi Zhong Zhou; Nian Hua Teng; Jia Lin Liang; Ying Yu Zeng; Yi Zhuo Wang; Li Qing Zeng; Xiao Liang Liu; Xi Ran Cheng; Zhao Jie Chen (Genetica, 2025)

Self-repair mechanisms of spiking neuron–astrocyte networks in working memory under diverse injury conditions - Bingyi Mo; Xiaoqian Liu; Lin Li; Shanshan Cheng; Yuan Zhu; Ming Yi; Lulu Lu (Cognitive Neurodynamics, 2025)

Serum cortisol and AdipoR2 rs12342 were involved in the correlation between stress and serum cholesterol in a gender-specific manner - Yi Lin Shen; Qi Wei Guo; Xue Cheng Li; Ke Xin Jia; Jun Yi Liu; Yan Zhi Yi; Jun Tao Ren; Jia Jing Cai; Guo Ming Su; Jia Lin; Ding Zhi Fang (Metabolic Brain Disease, 2025)

Characterization of neutral fluids in the volcanic geothermal system under the Tatun Volcano Group, Taiwan - Yi-Chia Lu; Chyi Wang; Sheng-Rong Song; Pei-Ling Wang; Ting-Jui Song; Sachihiro Taguchi; Tsung-Ren Peng; Li-Hung Lin; Jian-Cheng Lee; Hong-Chun Li (Journal of Geochemical Exploration, 2025)

Closing in on carbonate uranium isotopes as a paleo-redox proxy based on continuous records from Late Oligocene to Holocene island carbonates - Guolin Xiong; Feifei Zhang; Yi-Bo Lin; Guang-Yi Wei; Na Li; Mengchun Cao; Xuexue Jia; Jian Wang; Wen Yan; Hai Cheng; Shu-zhong Shen (Geochimica et Cosmochimica Acta, 2025)

Preparation of antibacterial CO2-based polycarbonate hydrogels with dual cross-linkages for co-loading of antibiotics and hypoglycemic agents and their applications on diabetic wound dressings - Zheng-Ian Lin; Tzu-Hsien Tsai; Guan-Lin Liu; Chih-Yuan Hsu; Siang-Ming Tsai; Yi-Ping Fang; Wing-Cheung Law; Han-Lin Tsai; Jia-Ying Tsai; Hsuan-Ying Chen; Bao-Tsan Ko; Pei-Wen Cheng; et al. (Chemical Engineering Journal, 2025)

Three-dimensional material point analysis of the Guanghua landslide influenced by topographic constraints - Yi-Pin Peng; Kuo-Hsin Yang; Wei-Lin Lee; Tatag Yufitra Rus; Shih-Hao Cheng; Jyun-Yen Wang; Chihping Kuo (Landslides, 2025)

Dynamic in situ counting of farmed Holothurians based on improved YOLOv8s-ByteTrack - Ke-Xin Liu; Fang Wang; Sheng-Cheng Hong; Jun-Yi Wang; Xin-Yu Zheng; Yuan-Shan Lin (Aquaculture International, 2025)

Sediment characteristics affecting natural radionuclide distribution and radiological assessment in a tropical wetland near Maanshan Nuclear Power Plant, Southern Taiwan - Ting-Chien Chen; Yi-Lung Yeh; Fan-Cheng Zeng; Chih-Chung Lin; Zhi-Mou Chen; Wei-Hsiang Huang (Environmental Monitoring and Assessment, 2025)

Regulating community redox metabolism for systematic mitigation of antibiotic chemical and biological risks - Ke Shi; Wen-Bin Xu; Han-Lin Cui; Li-Ying Zhang; Jing-Yi He; Wei-Wei Ben; Cheng-Yuan Su; Shu-Hong Gao; Ai-Jie Wang; Bin Liang (Water Research, 2025)

Manipulation of carbon dioxide adsorption and desorption via CO₂-philic fibrous polyethyleneimines under alternating current electric fields by frequency tuning - Chih-Wei Chen; Yi-Hua Lin; Chih-Chia Cheng; Chien-Hsing Lu; Jem-Kun Chen (Science of The Total Environment, 2025)

Monitoring for classical swine fever virus persistence and seropositivity in vaccinated pig farms using on-farm sentinel pigs during the pre-elimination phase toward a CSF-free status - Kuo-Jung Tsai; Hui-Yu Chen; Chun Wang; Chung-Shun Hung; Wei-Cheng Hsu; Tsu-Han Chen; Ming-Chung Deng; Cheng-Ta Tsai; Nien-Nong Lin; Jung-Pin Hsu; Chia-Yi Chang; Yu-Liang Huang (Preventive Veterinary Medicine, 2025)

Simulation and prediction of vertical migration of Cd²⁺ in heavy metal-contaminated soils amended with different passivators via Hydrus-1D - Ying Luo; Zhe Wang; Cheng-xia Wang; Jia-Qian Zhang; Kai Ye; Chao-liang Peng; Yi-ming Chen; Zhen-Long Zhang; Wen-xue Lin; Jing-yan Zhang; Shao-qin Chen (Journal of Environmental Chemical Engineering, 2025)

Functional properties and sensitization of β-lactoglobulin were improved by covalent binding with exopolysaccharides and (−)-epigallocatechin gallate - Cuicui Duan; Yi Zhang; Cheng Wu; Siyang Sui; Hui Liu; Hongru Wang; Lin Ma; Xiaolei Li; Fumin Ma; Dan Li (Food Research International, 2025)

Multi-omics insights into flavor compounds production and constipation-relieving benefits of different Lactiplantibacillus plantarum-fermented cereal beverages - Wen-Jie Jiang; Ya-Xin Jiang; Lin Cheng; Yu-Chen Ning; Jia-Yi Hou; Fei-Liang Zhong; Ting Yuan; Xue-Gang Luo (Food Research International, 2025)

Association between air pollution and obstructive sleep apnea in terms of respiratory event frequency and lung-to-finger circulation time - Rachel Chien; Zhihe Chen; Peizheng Wang; Wen-Te Liu; Ying-Ying Chen; Yen-Ling Chen; Arnab Majumdar; Jiunn-Horng Kang; Kang-Yun Lee; Wun-Hao Cheng; Yi-Chih Lin; Cheng-Jung Wu; et al. (Atmospheric Pollution Research, 2025)

Different Detection Strategies of Pediocin-Like Produced by Pediococcus pentosaceus - Hongbiao Li; Huojian Zheng; Lanxin Li; Yi Lin; Qiuxiang Cheng; Liping Wang; Yueliang Zhao; Zhenmin Liu (Probiotics and Antimicrobial Proteins, 2025)

Canagliflozin-driven cellular re-differentiation and migration inhibition in vascular smooth muscle cells via PTEN upregulation - Ming-Jer Hsieh; Dong-Yi Chen; Cheng-Hung Lee; Yu-Cih Liao; Miao‐Sui Lin; Jong-Hwei S. Pang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Pediatric Abdominal and Pelvic CT Scans and the Subsequent Risk of Malignancy and Benign Genital Tumors: A Retrospective Cohort Study - Feng-Yi Su; Chih-Feng Chen; Kevin Chih-Yang Huang; Cheng-Li Lin; Fuu-Jen Tsai; Jui-Ting Hsu; Shin-Lei Peng (Journal of Medical and Biological Engineering, 2025)

Deinococcus lichenicola sp. nov., A Bacterium Isolated from a Lichen Sample - Guo-Hua Chen; Lian-Shuang Xiong; Rui Yang; Shu-Ya Zuo; Qing Yuan; Li-Song Wang; Cheng-Lin Jiang; Xin-Yu Wang; Yi Jiang (Current Microbiology, 2025)

Integrating satellite information, land use regression, and machine learning to estimate the spatiotemporal variation of ionic composition in PM2.5 across Taiwan - Kang Lo; Tang-Huang Lin; Fu-Cheng Wang; Yi-Shiang Shiu; Chu-Chih Chen; Yuan-Chien Lin; Chun-Sheng Huang; Ho-Tang Liao; Yee-Lin Wu; Chang-Fu Wu (Science of The Total Environment, 2025)

First experiment using post-accelerated unstable ion beams at BRIF: angular distribution of the 21 , 22 Na elastic scattering from doubly magic 40 Ca - Wei Nan; Bing Guo; Cheng-Jian Lin; Dan-Yang Pang; Lei Yang; Dong-Xi Wang; Guo Yang; Yang-Ping Shen; Bing Tang; Qi-Wen Fan; Yi-Wen Bao; Lei Cao; et al. (Science Bulletin, 2025)

Alternative splicing of OsNPR3 promoted by the bacterial TAL effectors-targeted splicing regulator OsRBP11 antagonizes OsNPR1 function and enhances disease susceptibility in rice - Xiaochen Chen; Xiaohui Yao; Fang Yan; Shaofang Li; Zuo-Dong Wang; Fu-You Yin; Miao Zhou; Zhen Wang; Lina Qin; Baoguo Zhao; Kai Lu; Liyuan Zhang; et al. (Molecular Plant, 2025)

AhR-mediated histone lactylation drives cellular senescence during benzo[a]pyrene-evoked chronic obstructive pulmonary disease - Li-Hong Chen; Jun-Ping Wei; Meng-Die Li; Xiu Lu; Yi-Cheng Ma; Yu Wang; Ling Zheng; Jun Fei; Wei Cao; De-Xiang Xu; Jin Yang; Hui Zhao; et al. (Journal of Hazardous Materials, 2025)

Efficient removal of trace diazepam via enhanced peroxymonosulfate activation by 1T-phase and sulfur vacancy-rich MoS2-C-Fe - Jiawei Lin; Hongfeng Zhang; Jingyu Liu; Yongyou Hu; Jiaqi Peng; Feng Xu; Cheng Zhao; Qing Wang; Hao Zhou; Yi Yin (Journal of Cleaner Production, 2025)

Using speleothem 87Sr/86Sr variations tracking the controls on trace element (Sr-Mg) compositions - Rishui Chen; Shuyu Xue; Hongbin Zhang; Michael Griffiths; Yi Zhou; Xing Liu; Zhenli Zhu; Lin Chen; Wei Guo; Shitou Wu; Hai Cheng; Junhua Huang; et al. (Global and Planetary Change, 2025)

Multi-Scale study on combustion acceleration and Self-Catalytic mechanisms of Nickel-Based energetic complex [Ni(N2H4)2](N3)2 - Cheng Dong; Shiyong Chen; Lixiao Shen; Tu Xu; Yinning Zeng; Yan Li; Zhenxin Yi; Chenguang Zhu; Lin Zhang; Shunguan Zhu (Fuel, 2025)

The correlation of immunotoxicity with size and chemical properties of particulate matter within macrophages - Hsiang-Yu Kung; Yi-Shiuan Wang; Yung-Jui Chen; Ting-Hsuan Wu; Jai-Yu Chen; Yueh-Feng Wen; Yu-Cheng Chen; Hong-Lin Chan; Hsiu-Chuan Chou (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Recent progress in two-dimensional materials: From emerging structures and synthesis approaches to electronic and sensing applications - Jing Hao Zhuang; Zhong Li; Yi Liang; Tao Tang; Xin Yi Hu; Rui Ou; Qi Jie Ma; Bao Yue Zhang; Yin Fen Cheng; Wen Lin Feng; Jian Zhen Ou (Chemical Engineering Journal, 2025)

Five novel RNA viruses of the invasive big-headed ant (Pheidole megacephala) - Charly T. Hartle; Chih-Chi Lee; Hung-Wei Hsu; Chun-Yi Lin; Kuan-Ling Liu; Joey Yin-Xin Chang; John A. Lawrence; Jia-Wei Tay; Chin-Cheng Scotty Yang (Archives of Virology, 2025)
The African big-headed ant, Pheidole megacephala , is one of the most destructive invasive ant species, posing a significant threat to native biodiversity and ecosystem function, particularly in island ecosystems. Despite recent efforts to characterize pathogens in other major invasive ants, P . megacephala has received comparatively little attention. In this study, we characterized five novel RNA viruses actively replicating in P . megacephala , which we have named Pheidole megacephala virus 1–5 (PmV1-5), and examined viral diversity and prevalence in two invasive populations in Taiwan and Hawaii. This ant possesses a unique trait of true morphological worker dimorphism (major and minor), allowing us to test whether virus prevalence differs between the major and minor worker castes. Our findings indicate that all five novel viruses were present in both populations, but viral prevalence was higher in Hawaii than in Taiwan, potentially due to differences in supercolony structure. Multiple-virus infections were common, with coinfection by PmV1 and PmV5 being the most frequent. Notably, we found no significant difference in infection patterns between major and minor workers, suggesting that virus distribution is stable within colonies and that sampling different castes does not introduce bias in pathogen detection. This study represents the first characterization of viral pathogens in P . megacephala and may contribute to the development of microbial control strategies against this globally invasive ant.

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Geochemistry of sulfides from massive carbonate replacement type tin ore at Gaofeng, Dachang orefield: Insights into precipitation conditions and enrichment of critical metals - Yu-Pei Liu; Pei Ni; Jun-Yi Pan; Wen-Chao Su; Stefano Albanese; Jian-Ming Cui; Yuan-Feng Cai; Ming-Sen Fan; Zhi-Lin Cheng (Journal of Geochemical Exploration, 2025)

Synergistic effect of hollow n-Al/H-MoO3 in the gas-phase reaction zone of solid propellant - Shuping Li; Cheng Dong; Xuan Qi; Shiyong Chen; Lixiao Shen; Yinning Zeng; Yan Li; Zhenxin Yi; Lin Zhang; Shunguan Zhu (Fuel, 2025)

Antimicrobial properties and preservation potential of Allium sativum L-derived extracellular vesicle-like particles for food applications - Chenqi Zhu; Xiaoxiao Ke; Yi Gu; Chunmeng Wang; Shangyang Lin; Yijie Qian; Jiale Cheng; Yan Chen; Liu Xu; Zhipeng Chen (Food Chemistry, 2025)

Corrigendum to “Active and intelligent gellan gum-based packaging films for controlling anthocyanins release and monitoring food freshness” [Carbohydrate Polymers 254 (2021) 117410] - Li-Ting Wu; I-Lin Tsai; Yi-Cheng Ho; Yu-Hao Hang; Chi Lin; Min-Lang Tsai; Fwu-Long Mi (Carbohydrate Polymers, 2025)

P2 purinergic receptors regulate the progression of colorectal cancer - Wen-jun Zhang; Li-peng Zhang; Si-jian Lin; Cheng-yi Wang; Yi-guan Le (Purinergic Signalling, 2025)

Lactiplantibacillus plantarum GMNL-661 Ameliorates Clostridioides difficile Infection and Reconfigures Intestinal Microbiota in a Murine Model - Meng-Jia Li; Hong-Ming Chen; Yueh-Lin Chen; Yi-Hsin Lai; Cheng-Yu Lai; Jhen-Wei Ruan; Jenn-Wei Chen; Wan-Hua Tsai; Wen-Chien Ko; Pei-Jane Tsai (Probiotics and Antimicrobial Proteins, 2025)

Enhanced Hair Growth Through Transdermal Delivery of Bacopa Monnieri Extract Using a Needle-Free Supersonic Atomizer - Yu-Chiuan Wu; Yi-Ping Lin; Ching-Yi Chang; Hsia-Ying Cheng; Tien-Huei Chu; Chien-Chih Chen; Shyh-Ming Kuo (Journal of Medical and Biological Engineering, 2025)

Microplastic-induced hypertension in rats: A two-hit model exploring oxidative stress and gut microbiota - Yu-Chun Cheng; Wei-Ling Chen; Hong-Ren Yu; Ching-Yi Tsai; Jiunn-Ming Sheen; Mao-Meng Tiao; Chien-Ning Hsu; You-Lin Tain (NanoImpact, 2025)

A numerical study of NO removal from exhaust gas at low-temperature using metal Zeolite catalysts - Way Lee Cheng; Ding-Hui Wang; Yi-Chi Chang; Pei-Cheng Cheng; Yu-Zheng Wang; Yuan-Chung Lin (Fuel, 2025)

Characteristics of microbial carbon pump in the sediment of kelp aquaculture zone and its contribution to recalcitrant dissolved organic carbon turnover: insights into metabolic patterns and ecological functions - Jun-Yang Ma; Ji-Hua Liu; Cheng-Zhuang Chen; Yi-Ze Zhang; Zhan-Sheng Guo; Min-Peng Song; Feng Jiang; Zi-Tong Chai; Zhu Li; Su-Xian Lv; Yu-Jiao Zhen; Lu Wang; et al. (Environmental Research, 2025)

All-in-one and on-demand wound dressing based on a deep eutectic solvent ionic gel - Jia-Yu Yang; Yu-Lin Tsai; Ting-Hui Cheng; Yu-Lin Su; Yi-Kai Hong; Yu-Chen Lin; Da-Huei Lee; Chao-Chun Yang; Chao-Kai Hsu; Li-Chieh Kuo; Cheng-Hsin Chuang (Chemical Engineering Journal, 2025)

Changes in soil pH and nutrient stoichiometry alter the effects of litter addition on soil nitrogen transformations and nitrous oxide emissions - Jing Wang; Miaomiao Cao; Uwiragiye Yves; Meiqi Chen; Yi Cheng; Zezhong Lin; Renhua Zheng (Plant and Soil, 2025)

Searching for neutrinoless double-beta decay of 136 Xe with PandaX-4T - Shu Zhang; Zihao Bo; Wei Chen; Xun Chen; Yunhua Chen; Zhaokan Cheng; Xiangyi Cui; Yingjie Fan; Deqing Fang; Zhixing Gao; Lisheng Geng; Karl Giboni; et al. (Science Bulletin, 2025)

Geothermal gas geochemistry in Southeast Tibetan Plateau margin influenced by magma chambers and fractures - Jia-Yi Wu; Hai Gang Cao; Peng Cheng Zhao; Yu Ping Guo; Xue-Gang Chen; Xiaohu Li; Jui-Fen Tsai; Pei-Ling Wang; Li-Hung Lin (Journal of Volcanology and Geothermal Research, 2025)

Phenol-driven ammonium recovery from coal chemical wastewater in a bioelectrochemical system (BES) - Ran Zeng; Li-Hui Yang; Si-Yuan Zhai; Cheng-Yan Liu; Na Lin; Qing-Hua Ou-Yang; Yan-Hua Xu; Ai-Jie Wang; Hao-Yi Cheng (Journal of Hazardous Materials, 2025)

Synthesis optimization for α-MnO2 with high benzene oxidation potential: Role of chemisorbed oxygen in the successive adsorption and oxidation of benzene - Di Zhang; Lin Cheng; Hao-Yu Lian; Xianliang Yi; Hao Zhou; Yang Liu (Journal of Environmental Chemical Engineering, 2025)

Facile synthesis of trimetallic compounds based on cobalt and nickel with ammonium fluoride-based complex for energy storage applications - Tsai-Mu Cheng; Pei-Chen Kuo; Yi-Chun Lai; Pin-Yan Lee; Chutima Kongvarhodom; Muhammad Saukani; Sibidou Yougbaré; Hung-Ming Chen; Kuo-Chuan Ho; Lu-Yin Lin (Journal of Environmental Chemical Engineering, 2025)

Exploration of the structural features and anti-oxidative activity of whey protein hydrolysates produced by Lactiplantibacillus plantarum - Cuicui Duan; Shunan Hu; Cheng Wu; Yi Zhang; Lin Ma; Xiaolei Li; Fumin Ma; Dan Li (Food Research International, 2025)

Harnessing microalgae: Pioneering strategies for cost-effective EPA synthesis - Yi-Ting Shen; Zi-Xu Zhang; Xin Qi; Hong-Xuan Wu; Yan-Cheng Lin; Wang Ma; Guang Yang; Xiao-Man Sun (Food Bioscience, 2025)

An emulsion gel made by waxy maize starch hydrogel incorporated with tea polyphenols/exopolysaccharides: Structure and stability properties, antioxidant and delivery function - Cuicui Duan; Shunan Hu; Ran Wang; Cheng Wu; Yi Zhang; Lin Ma; Fumin Ma; Xiaolei Li; Dan Li (Food Bioscience, 2025)

Dynamic weather-based scheduling for achieving energy savings in factories - Kung-Yueh Camyale Chao; Yi-Ting Liu; Chia-Yi Lee; Ji-Hong Lin; Chia-Ping Cheng; Ming-Hao Lee; Hung-Chi Kuo; Tai-Jen George Chen (Energy and Buildings, 2025)

Computational design and efficacy assessment of Bufalin-Dendrimer nanoformulation for enhanced cancer therapy - Yurong Sun; Yinhua Lin; Huaitao Sun; Junfa Yang; Hui Cheng; Jia Yi; Wenqiang Li; Gen Lu; Cheng Zhao; Yuge Jiang; Xinyu Zhao; Qinglin Li; et al. (Chemical Engineering Journal, 2025)

The recruitment of alkaline phosphatase-positive endogenous neural stem cells enables robust neurogenesis and neural pathways reconstruction following spinal cord injury - Rong-Jie Wu; Jia-Lin Liu; Zheng-Hong Chen; Jing Xu; Ying Ding; Hai-Yang Yu; Chuang-Ran Wu; Shang-Bin Yang; Rui Liu; Yi-Nan Guo; Yue Yang; Ting-Ting Wu; et al. (Chemical Engineering Journal, 2025)

Epigenetics in the modern era of crop improvements - Yan Xue; Xiaofeng Cao; Xiangsong Chen; Xian Deng; Xing Wang Deng; Yong Ding; Aiwu Dong; Cheng-Guo Duan; Xiaofeng Fang; Lei Gong; Zhizhong Gong; Xiaofeng Gu; et al. (Science China Life Sciences, 2025)
Epigenetic mechanisms are integral to plant growth, development, and adaptation to environmental stimuli. Over the past two decades, our comprehension of these complex regulatory processes has expanded remarkably, producing a substantial body of knowledge on both locus-specific mechanisms and genome-wide regulatory patterns. Studies initially grounded in the model plant Arabidopsis have been broadened to encompass a diverse array of crop species, revealing the multifaceted roles of epigenetics in physiological and agronomic traits. With recent technological advancements, epigenetic regulations at the single-cell level and at the large-scale population level are emerging as new focuses. This review offers an in-depth synthesis of the diverse epigenetic regulations, detailing the catalytic machinery and regulatory functions. It delves into the intricate interplay among various epigenetic elements and their collective influence on the modulation of crop traits. Furthermore, it examines recent breakthroughs in technologies for epigenetic modifications and their integration into strategies for crop improvement. The review underscores the transformative potential of epigenetic strategies in bolstering crop performance, advocating for the development of efficient tools to fully exploit the agricultural benefits of epigenetic insights.

Research on digital twin-based dynamic evolution model for the reactor hull structure of an icebreaker - Yi Lin; Siyuan Liu; Lizhi Chen; Ruiqi Cheng; Zhiyong Pei (Ocean Engineering, 2025)

Enhancing antibiotic removal in constructed wetlands: A MgFe-LDHs-based strategy for optimizing microbial communities and metabolic functions - Yu-Quan Zhong; Xiang-Long He; Yi-Hao Li; Hui Zhu; Jing-Wen Li; Hao Xu; Can Liu; Liang-Cheng Lin; Jun-Feng Wang (Journal of Hazardous Materials, 2025)

Enhancing color conversion of perovskite quantum dot-based micro-light-emitting diodes via electrochemical etching and flow chemistry system - Wen-Tse Huang; Yen-Huei Lin; Po-Yi Tu; Loan Thi Ngo; Wei-Cheng Chen; Kai-Ling Liang; Yen-Hsiang Fang; Chaochin Su; Ru-Shi Liu (Chemical Engineering Journal, 2025)

Estimating and characterizing spatiotemporal distributions of elemental PM2.5 using an ensemble machine learning approach in Taiwan - Chun-Sheng Huang; Kang Lo; Yee-Lin Wu; Fu-Cheng Wang; Yi-Shiang Shiu; Chu-Chih Chen; Yuan-Chien Lin; Cheng-Pin Kuo; Ho-Tang Liao; Tang-Huang Lin; Chang-Fu Wu (Atmospheric Pollution Research, 2025)

Genotyping and antimicrobial susceptibility of Aeromonas veronii isolated from aquatic animals in Sichuan, China - Kun Peng; Silu Tian; Longjun Deng; Yu Yuan; Zixuan Cheng; Tiancai Li; Keyu Zhou; Jingyi Lin; Yi Geng (Antonie van Leeuwenhoek, 2025)

A genomic variation map provides insights into potato evolution and key agronomic traits - Qun Lian; Yingying Zhang; Jinzhe Zhang; Zhen Peng; Weilun Wang; Miru Du; Hongbo Li; Xinyan Zhang; Lin Cheng; Ran Du; Zijian Zhou; Zhenqiang Yang; et al. (Molecular Plant, 2025)

Synergistic properties of single-component hexagonal iron borate for superior and sustainable photo-Fenton catalysis - Po-Yi Wu; Jing-Cheng Hsu; Tsung-Yueh Lin; Yu-Lun Zhu; Yu-Rong Chang; Pei Yuin Keng (Journal of Environmental Chemical Engineering, 2025)

2-Mercapto-1,3,4-thiadiazole-functionalized gold nanoclusters as a comparable bactericidal nanoantibiotic to vancomycin in treating methicillin-resistant Staphylococcus aureus infections - Quan-Quan Zhuang; Jia-Xin Ma; Yi-Ming Zheng; Lin-Yan Lu; Jia-Lin Yang; Qing-Qing Chen; Xiao-Li Yan; Yan-Cheng Jiang; Hao-Hua Deng; Wei Chen; Gang Liu (Chemical Engineering Journal, 2025)

Mutation Screening of ATXN1, ATXN2, and ATXN3 in Amyotrophic Lateral Sclerosis - Tianmi Yang; Qianqian Wei; Dejiang Pang; Yangfan Cheng; Jingxuan Huang; Junyu Lin; Yi Xiao; Qirui Jiang; Shichan Wang; Chunyu Li; Huifang Shang (Molecular Neurobiology, 2025)

Terpenoids with Antiangiogenic Activity from Formosan Soft Coral Caementabunda hypotentaculata - Hsin Huang; Chen-Yu Yang; Shih-Wei Wang; Limbadri Salendra; Shu-Rong Chen; Tzi-Yi Ke; Yu-Liang Yang; Yu-Chi Lin; Yuan-Bin Cheng (Marine Biotechnology, 2025)

Exogenous mitochondria added on benefits for cellular prion protein overexpression in adipose-derived mesenchymal stem cells treatment on intracranial hemorrhage rat - Kun-Chen Lin; Jui-Ning Yeh; Pei‐Hsun Sung; Tsung-Cheng Yin; John Y. Chiang; Chi-Ruei Huang; Yi-Ling Chen; Yi-Ting Wang; Kuan-Hung Chen; Hon‐Kan Yip (Journal of Molecular Histology, 2025)

Genetic Analysis of Polyunsaturated Fatty Acids Biosynthesis Pathway Determines Four Distinct Thraustochytrid Types - Sou‐Yu Cheng; Yi‐Jing Chen; Hsiu‐Chin Lin; Hsin‐Yang Chang; Ming‐Der Huang (Environmental Microbiology, 2025)
Thraustochytrids, diverse marine unicellular protists encompassing over 10 recognised genera, are renowned for synthesising polyunsaturated fatty acids (PUFAs), with content and composition varying substantially across genera. While PUFAs are known to be produced via PUFA synthase (PUFA‐S) and/or elongase/desaturase (ELO/DES) pathways, the distinctions in genes involved remain unexplored. This study analysed PUFA biosynthetic genes in 19 thraustochytrid strains across six genera, categorising them into four types. Type I exclusively utilises the ELO/DES pathway, Type II employs both PUFA‐S and complete ELO/DES pathways, while Types III and IV primarily rely on PUFA‐S, with Type III lacking the canonical Δ9 desaturase and Type IV missing most desaturase and elongase enzymes. Notably, the Δ9 desaturase and ATP‐citrate lyase ( ACLY ) are exclusive to Types I and II, while β‐carotene hydroxylase ( CrtZ ) is absent in these types. ACLY absence suggests alternative acetyl‐CoA supply pathways in Types III and IV, whereas CrtZ absence implies either a lack of specific xanthophylls or alternative biosynthetic pathways in Types I and II. Synteny analysis revealed conserved genomic organisation of PUFA biosynthetic genes, indicating a shared evolutionary trajectory. This study provides insights into the genetic diversity underlying PUFA biosynthesis in thraustochytrids, while proposing putative evolutionary pathways for the four lineages.

Determination of pullout capacity for an inclined single-plate helical pile under combined loading in clay - Fei Liu; Po Cheng; Hongnan Lin; Jiangtao Yi; Yu Peng; Jun Hu; Ya-pei Chu (Marine Georesources & Geotechnology, 2025)

Digital infrastructure construction and urban industrial chain resilience: Evidence from the “Broadband China” strategy - Yi Chen; Cailou Jiang; Lin Peng; Shuang Zhao; Cheng Chen (Sustainable Cities and Society, 2025)

Degradation of naphthalene in aqueous solution using a microbial symbiotic system founded by degrading and ureolytic bacteria - Yi-Xin Xie; Wen-Chieh Cheng; Zhong-Fei Xue; Lin Wang; Md Mizanur Rahman (Environmental Research, 2025)

Advancements in rapid on-site detection of chemical oxygen demand: Insights into sensing mechanisms and practical applications - Xingyang Cheng; Jing Tang; Yu Chen; Yibo Liao; Zhigang Yi; Pansong Li; Lin Tang (Chemical Engineering Journal, 2025)

Indoxyl Sulfate Induces Ventricular Arrhythmias Attenuated by Secretoneurin in Right Ventricular Outflow Tract Cardiomyocytes - Yuan Hung; Chen-Chuan Cheng; Yen-Yu Lu; Shih-Yu Huang; Yao-Chang Chen; Fong-Jhih Lin; Wei-Shiang Lin; Yu-Hsun Kao; Yung-Kuo Lin; Shih-Ann Chen; Yi-Jen Chen (Cardiovascular Toxicology, 2025)

Corrigendum to “Differentiation of sow and mouse ovarian granulosa cells exposed to zearalenone in vitro using RNA-seq gene expression” [Toxicology and Applied Pharmacology, 350 (2018) 78–90] - Guo-Liang Zhang; Jun-Lin Song; Yi Zhou; Rui-Qian Zhang; Shun-Feng Cheng; Xiao-Feng Sun; Guo-Qing Qin; Wei Shen; Lan Li (Toxicology and Applied Pharmacology, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Plasma proteomics identifies proteins and pathways associated with incident depression in 46,165 adults - Jujiao Kang; Liu Yang; Tianye Jia; Wei Zhang; Lin-Bo Wang; Yu-Jie Zhao; Jia You; Yue-Ting Deng; Yi-Jun Ge; Wei-Shi Liu; Yi Zhang; Yi-Lin Chen; et al. (Science Bulletin, 2025)

Triptolide exposure triggers ovarian inflammation by activating cGAS-STING pathway and decrease oocyte quality in mouse - Si-Yao Cheng; Yi-Fan Yang; Ya-Long Wang; Zhao-Ping Yue; Yan-Zhu Chen; Wen-Ke Wang; Zhi-Ran Xu; Lin-Feng Li; Hao Shen; Zhi-Min Qi; Chang-Long Xu; Yu Liu (Food and Chemical Toxicology, 2025)

One new MOF with hierarchical pores achieving efficient one-step purifying C2H2, recycling CH4 and eliminating CO2 in C2H2 production - Lin Zhang; Ya-Li Bao; Rui-Cheng Gao; Wen-Juan Shi; Yi-Zhao Guo; Lei Hou; Yao-Yu Wang (Chemical Engineering Journal, 2025)

Analysis of serotype distribution and characteristics of nonhemolytic and nonpigmented strains among group B Streptococcus isolates in a southern Taiwan local hospital - Hui-Fang Cheng; Zhe-Yu Kuo; Ching-Chiang Lin; Ho-Feng Chen; Horng-Ren Lo; Huey-Wen Shyu; Yi-Fen Wang (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

Enhanced nano-LC-MS for analyzing dansylated oral cancer tissue metabolome dissolved in solvents with high elution strength - Ya-Ju Hsieh; Cheng-Yu Hung; Yi-Ting Chen; Yu-Tsun Lin; Kai-Ping Chang; Wei-Fan Chiang; Chih-Yen Chien; Chih-Ching Wu; Liang Li; Jau-Song Yu; Kun-Yi Chien (Analytica Chimica Acta, 2025)

Deciphering Trachinotus ovatus resistance to Streptococcus agalactiae:GWAS identification of key SNPs and candidate genes - Yi-Yao Sun; Jie Gao; Bao-Suo Liu; Nan Zhang; Hua-Yang Guo; Ke-Cheng Zhu; Lin Xian; Dian-Chang Zhang (Aquaculture, 2025)

Enhanced biodegradation of glyphosate by Chlorella sorokiniana engineered with exogenous purple acid phosphatase - Si-Fen Liu; Zhong-Chen Yi; Zi-Qiong Huang; Zhen-Dong Yuan; Yu-Cheng Yang; Yongteng Zhao; Qing-Yu He; Wei-Dong Yang; Hong-Ye Li; Carol Sze Ki Lin; Xiang Wang (Water Research, 2025)

Machine learning-assisted SERS sensor for fast and ultrasensitive analysis of multiplex hazardous dyes in natural products - Chengqi Lin; Cheng Zheng; Bo Fan; Chenchen Wang; Xiaoping Zhao; Yi Wang (Journal of Hazardous Materials, 2025)

Sulfur-functionalized sawdust biochar for enhanced cadmium adsorption and environmental remediation: A multidisciplinary approach and density functional theory insights - M.M.M. Ahmed; Chih-Hao Liao; S. Venkatesan; Yu-Ting Liu; Yu-Min Tzou; Shih-Hao Jien; Ming-Chang Lin; Yi-Cheng Hsieh; Ahmed I. Osman (Journal of Environmental Management, 2025)

Pitfalls in measuring solution toxicity using the level of bioluminescence inhibition in Aliivibrio fischeri - Cheng-Kun He; Ming-Chun Hung; Chong-Hao Hxu; Yi-Hsien Hsieh; Yung-Sheng Lin (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Leifsonia stereocauli sp. nov., Isolated from Stereocaulon tomentosum Fr. Lichen - Shu-Ya Zuo; Lian-Shuang Xiong; Qing Yuan; Guo-Hua Chen; Rui Yang; Li-Song Wang; Cheng-Lin Jiang; Xin-Yu Wang; Yi Jiang (Current Microbiology, 2025)

Performance of Convolutional Neural Network Models in Meningioma Segmentation in Magnetic Resonance Imaging: A Systematic Review and Meta-Analysis - Ting-Wei Wang; Jia-Sheng Hong; Wei-Kai Lee; Yi-Hui Lin; Huai-Che Yang; Cheng-Chia Lee; Hung-Chieh Chen; Hsiu-Mei Wu; Weir Chiang You; Yu-Te Wu (Neuroinformatics, 2024)
Background Meningioma, the most common primary brain tumor, presents significant challenges in MRI-based diagnosis and treatment planning due to its diverse manifestations. Convolutional Neural Networks (CNNs) have shown promise in improving the accuracy and efficiency of meningioma segmentation from MRI scans. This systematic review and meta-analysis assess the effectiveness of CNN models in segmenting meningioma using MRI. Methods Following the PRISMA guidelines, we searched PubMed, Embase, and Web of Science from their inception to December 20, 2023, to identify studies that used CNN models for meningioma segmentation in MRI. Methodological quality of the included studies was assessed using the CLAIM and QUADAS-2 tools. The primary variable was segmentation accuracy, which was evaluated using the Sørensen–Dice coefficient. Meta-analysis, subgroup analysis, and meta-regression were performed to investigate the effects of MRI sequence, CNN architecture, and training dataset size on model performance. Results Nine studies, comprising 4,828 patients, were included in the analysis. The pooled Dice score across all studies was 89% (95% CI: 87–90%). Internal validation studies yielded a pooled Dice score of 88% (95% CI: 85–91%), while external validation studies reported a pooled Dice score of 89% (95% CI: 88–90%). Models trained on multiple MRI sequences consistently outperformed those trained on single sequences. Meta-regression indicated that training dataset size did not significantly influence segmentation accuracy. Conclusion CNN models are highly effective for meningioma segmentation in MRI, particularly during the use of diverse datasets from multiple MRI sequences. This finding highlights the importance of data quality and imaging sequence selection in the development of CNN models. Standardization of MRI data acquisition and preprocessing may improve the performance of CNN models, thereby facilitating their clinical adoption for the optimal diagnosis and treatment of meningioma.

Protective Effects of Antcin H Isolated from Antrodia cinnamomea Against Neuroinflammation in Huntington’s Disease via NLRP3 Inflammasome Inhibition - Yu-Jun Chang; Cheng-Hsu Chen; Yi-Chen Chen; Ming-Tse Wu; Ting-Yu Lin; Kuo-Feng Hua; Tz-Chuen Ju (Journal of Neuroimmune Pharmacology, 2024)

How destination attributes affect mountain bikers’ behavioral intention: The mediating roles of enduring involvement and place attachment - Nien-Te Kuo; Lu-Ping Lin; Kuo-Chien Chang; Yi-Sung Cheng (Journal of Outdoor Recreation and Tourism, 2024)

Nanoplastics indirectly compromise lettuce growth in hydroponic systems via microbial extracellular vesicles derived from Curvibacter fontanus - Bao-Hong Lee; Yi-Ching Lin; Yu-Juan Zheng; Tang-Long Shen; Ting-Yu Cheng; Chih-Chia Huang; Wei-Hsuan Hsu (Journal of Hazardous Materials, 2024)

Estimating monthly NO2, O3, and SO2 concentrations via an ensemble three-stage procedure with downscaled satellite remote sensing data and ground measurements - Chu-Chih Chen; Yin-Ru Wang; Fu-Cheng Wang; Yi-Shiang Shiu; Chang-Fu Wu; Tang-Huang Lin (Journal of Hazardous Materials, 2024)

Immobilizing lead in aqueous solution and loess soil using microbially induced carbonate/phosphate precipitation (MICP/MIPP) under harsh pH environments - Zhong-Fei Xue; Wen-Chieh Cheng; Lin Wang; Yi-Xin Xie; Peng Qin; Cong Shi (Journal of Hazardous Materials, 2024)

Fluid inclusion LA-ICP-MS constraint on hydrothermal evolution of proximal cassiterite-bearing quartz veins in the giant Gejiu orefield: Implications for controls on metallogenic potential of granite-related skarn system - Zhi-Lin Cheng; Pei Ni; Jun-Yi Pan; Liang Han; Wen-Sheng Li; Stefano Albanese; Zhe Chi; Jun-Ying Ding; Jian-Ming Cui (Journal of Geochemical Exploration, 2024)

Corrigendum to “Response of sulfur-metabolizing biofilm to external sulfide in element sulfur-based denitrification packed-bed reactor” [Environ. Res. 231 (2023) 116061] - Hong-Xu Bao; Han-Lin Wang; Shu-Tong Wang; Yi-Lu Sun; Xue-Ning Zhang; Hao-Yi Cheng; Zhi-Min Qian; Ai-Jie Wang (Environmental Research, 2024)

Ultra-capacity and low-cost P3-type K0.5Mn0.96Fe0.04O2 cathode materials for K-ion batteries - Jun Cong; Shao-hua Luo; Yi-cheng Lin; Peng-yu Li; Li-xiong Qian; Sheng-xue Yan; Xin Liu; Xue-fei Lei (Chemical Engineering Journal, 2024)

Bio-inspired sustainable electrospun quantum nanostructures for high quality factor enabled face masks and self-powered intelligent theranostics - Loganathan Veeramuthu; Ren-Jie Weng; Wei-Hung Chiang; Archana Pandiyan; Fu-Jie Liu; Fang-Cheng Liang; G. Ranjith Kumar; Hua-Yi Hsu; Yu-Ci Chen; Wen-Yinn Lin; Yao-Chun Tang; Wan-Rong Lin; et al. (Chemical Engineering Journal, 2024)

Enhancing real-time PM2.5 forecasts: A hybrid approach of WRF-CMAQ model and CNN algorithm - Yi-Ju Lee; Fang-Yi Cheng; Hsiao-Chen Chien; Yuan-Chien Lin; Min-Te Sun (Atmospheric Environment, 2024)

The Complete Mitochondrial Genome of Chilo infuscatellus (Lepidoptera: Pyralidae), and Related Phylogenetic Analysis - Jiequn Yi; Jianbai Liu; Yongkai Mao; Yinjie Cheng; Minjiang Lin; Hanliang Xu; Yuxing An; Jihu Li; Han Wu (Biochemical Genetics, 2024)

Coral mariculture using abandoned abalone farming ponds in northeastern Taiwan - Shinya Shikina; Yin-Chu Cheng; Tzu-Chieh Lin; Yu-En Chang; Pin-Hsuan Tsai; Emma Chen; Yu-Chuan Chang; Yuen-Yi Leung; Yi-Chun Yu; Yi-Ling Chiu (Aquaculture, 2024)

In situ modification of ammonium perchlorate by energetic catalyst [Ni(N2H4)2](N3)2 — Achieving efficient catalysis for solid propellants - Cheng Dong; Zhiwen Wang; Yanbin Chen; Yan Li; Zhenxin Yi; Chenguang Zhu; Lin Zhang; Shunguan Zhu (Fuel, 2024)

Development of fermented Atemoya (Annona cherimola × Annona squamosa)-Amazake increased intestinal next-generation probiotics - Yeu-Ching Shi; She-Ching Wu; Yi-Ching Lin; Yu-Juan Zheng; Cheng-Hao Huang; Bao-Hong Lee (Food Chemistry, 2024)

Acrolein exposure affects ovarian function by interfering with glycolysis and mitochondrial energy metabolism in mouse - Yan-Zhu Chen; Wen-Ke Wang; Yi-Fan Yang; Si-Yao Cheng; Lin-Feng Li; Hao Shen; Zhi-Min Qi; Yu Liu (Environmental Pollution, 2024)

Fabrication of graphene oxide/ammonium molybdophosphate composite membrane for decontamination of cesium ions from seawater - Xiao-Yi Tang; Zi-Jie Li; Lin Wang; Peng-Cheng Zhang; Kong-Qiu Hu; Li-Rong Zheng; Zhi-Hui Zhang; Li-Yong Yuan; Wang-Suo Wu; Wei-Qun Shi (Chemical Engineering Journal, 2024)

Field performance of 15 rain gardens in different cities in Taiwan - Chi-Feng Chen; Yi-Wei Chen; Cheng-Han Lin; Jen-Yang Lin (Science of The Total Environment, 2024)

Corrigendum to “Euphpepluone S, a new lathyrane diterpenoid with anti-inflammatory activity from Euphorbia peplus L.” [Phytochem. Lett. 55 2023, 61–66] - Shi-Peng Guan; Ying Yang; Mao Sun; Min Cai; Xue-Xue Pu; Jian-Yi Huang; Ping Yi; Lin Liu; Ming-Rui Yuan; Yuan-Yuan Cheng; Ying-Tong Di (Phytochemistry Letters, 2024)

Synthesis of a novel double Z-scheme BiVO4/Cu2O/g-C3N4 sonocatalyst and research on sonocatalytic degradation of tetracycline - Yang-Cheng Liu; Ying-Di Ge; Hui-Li An; Wan-Ting Ju; Xin-Yi Zhou; Mei-Yi Xing; Yang Wang; Lin Zhang; Xin Wang; Liang Xu (Journal of Environmental Chemical Engineering, 2024)

Protective effects of nordalbergin against LPS-induced endotoxemia through inhibiting MAPK/NF-κB signaling pathway, NLRP3 inflammasome activation, and ROS production - Pin-Rong Chen; Chia-Yang Li; Taha Yazal; I-Chen Chen; Po-Len Liu; Yi-Ting Chen; Ching-Chih Liu; Jung Lo; Tzu-Chieh Lin; Ching-Tang Chang; Hsin-En Wu; Yuan-Ru Chen; et al. (Inflammation Research, 2024)

Identification of organic constituents on atmospheric particulate matter in the East Asian background air of free troposphere by GC×GC-TOFMS - Chang-Feng Ou-Yang; Yi-Jun Chen; Hsin-Cheng Hsieh; Chung-Te Lee; Kai-Hsien Chi; Neng-Huei Lin; Chih-Chung Chang; Jia-Lin Wang (Chemosphere, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Biofunctionalized hydrogel composed of genipin-crosslinked gelatin/hyaluronic acid incorporated with lyophilized platelet-rich fibrin for segmental bone defect repair - Er-Yuan Chuang; Yi-Cheng Lin; Yu-Min Huang; Chih-Hwa Chen; Yi-Yen Yeh; Lekha Rethi; Yu-Jen Chou; Pei-Ru Jheng; Jen-Ming Lai; Chang-Jung Chiang; Chin-Chean Wong (Carbohydrate Polymers, 2024)

Molecular Cloning and Functional Analysis of ScHAK10 Gene Promoter from Sugarcane (Saccharum officinarum L.) - Hai-Bin Luo; Cheng-Mei Huang; Hui-Qing Cao; Yuan-Wen Wei; Lin Xu; Kai-Chao Wu; Zhi-Nian Deng; Xing-Jian Wu; Li-Ping Ye; Xiao-Ping Yi (Tropical Plant Biology, 2024)

Dual-carbon isotope analysis of benzene polycarboxylic acids for tracking black carbon across different environments - Xin Yi; Guangcai Zhong; Xiaofei Geng; Jiao Tang; Boji Lin; Sanyuan Zhu; Shutao Gao; Chuxin Yao; Zhineng Cheng; Shizhen Zhao; Jun Li; Gan Zhang (Applied Geochemistry, 2024)

Performances of full-scale biological nitrogen pre-treatment process for drinking water source: Seasonal variations and microbial community - Hai-Hsuan Cheng; Yee Han Hew; Yi-Ju Wu; Tin-Yin Chen; Yi Ting Chiu; Li Ying Chen; Tsair-Fuh Lin; Liang-Ming Whang (Chemosphere, 2024)

The application of a high-density street-level air temperature observation network (HiSAN): Spatial and temporal variations of thermal and wind condition in different climatic condition types - Yu-Cheng Chen; Kai-Shan Hou; Yu-Jie Liao; Tsuyoshi Honjo; Fang-Yi Cheng; Tzu-Ping Lin (Sustainable Cities and Society, 2024)

Genomic profiling of biosynthetic potentials of medicinal secondary metabolites for ‘Aliisedimentitalea scapharcae’ KCTC 42119T, isolated from ark shell - Jin-Cheng Rong; Lin-Lin Cui; Na Li; Mao-Li Yi; Bo-Tao Huang; Qi Zhao (Marine Genomics, 2024)

Fe0-mediated mixotrophic denitrification enhanced by carbon fiber for secondary effluent with low C/N ratio - Yi-Mei Cheng; Lin-Chun Jia; Gang Xue; Xian-Ying Li (Journal of Environmental Chemical Engineering, 2024)

Large magnesium isotopic fractionation in lunar agglutinatic glasses caused by impact-induced chemical diffusion - Le Zhang; Cheng-Yuan Wang; Hai-Yang Xian; Jintuan Wang; Yan-Qiang Zhang; Zhian Bao; Mang Lin; Yi-Gang Xu (Geochimica et Cosmochimica Acta, 2024)

Screening and identification of selenium-enriched purine-lowering Lactobacillus plantarum and Lactococcus lactis with high stress tolerance and antioxidant capacity - Jia-Jun Liao; Cai-Yue Tan; Lan Liang; Yi-Zhen Luo; Hong-Lin Li; Yan-Yi Chen; Xiao-Dong Pei; Cheng-Hua Wang (Food Bioscience, 2024)

Fabrication of a label-free electrochemical immunosensor by functionalized nanofiber membrane for the ultrasensitive detection of quinalphos - Jian-cheng Hu; Peng Wen; Yu Wang; Jin-yi Yang; Zhi-li Xiao; Zhen-lin Xu; Yu-dong Shen; Hong Wang; Bruce D. Hammock (Food Control, 2024)

Immobilization of Pb(II) by Bacillus megaterium-based microbial-induced phosphate precipitation (MIPP) considering bacterial phosphorolysis ability and Ca-mediated alleviation of lead toxicity - Zhong-Fei Xue; Wen-Chieh Cheng; Md Mizanur Rahman; Lin Wang; Yi-Xin Xie (Environmental Pollution, 2024)

The relationship between landscape pattern and plant species diversity in east Dongting lake wetland based on different Eco-environment - Dongdong Zhang; Yang Lin; Wei Xiao; Deming Wang; Zihe Wang; Xingjian Jin; Tianzhuo Cheng; Jie Zhang; Peng Yi (Environmental Pollution, 2024)

Predicting ischemic stroke patients’ prognosis changes using machine learning in a nationwide stroke registry - Ching-Heng Lin; Yi-An Chen; Jiann-Shing Jeng; Yu Sun; Cheng-Yu Wei; Po-Yen Yeh; Wei-Lun Chang; Yang C. Fann; Kai-Cheng Hsu; Jiunn-Tay Lee (Medical & Biological Engineering & Computing, 2024)
Accurately predicting the prognosis of ischemic stroke patients after discharge is crucial for physicians to plan for long-term health care. Although previous studies have demonstrated that machine learning (ML) shows reasonably accurate stroke outcome predictions with limited datasets, to identify specific clinical features associated with prognosis changes after stroke that could aid physicians and patients in devising improved recovery care plans have been challenging. This study aimed to overcome these gaps by utilizing a large national stroke registry database to assess various prediction models that estimate how patients’ prognosis changes over time with associated clinical factors. To properly evaluate the best predictive approaches currently available and avoid prejudice, this study employed three different prognosis prediction models including a statistical logistic regression model, commonly used clinical-based scores, and a latest high-performance ML-based XGBoost model. The study revealed that the XGBoost model outperformed other two traditional models, achieving an AUROC of 0.929 in predicting the prognosis changes of stroke patients followed for 3 months. In addition, the XGBoost model maintained remarkably high precision even when using only selected 20 most relevant clinical features compared to full clinical datasets used in the study. These selected features closely correlated with significant changes in clinical outcomes for stroke patients and showed to be effective for predicting prognosis changes after discharge, allowing physicians to make optimal decisions regarding their patients’ recovery. Graphical Abstract

Research on Collapse Testing of Nuclear Icebreaker Reactor Hull Structure Based on Distortion Similarity Theory - Yi Lin; Ruiqi Cheng; Lizhi Chen; Xiangshao Kong; Zhiyong Pei (Journal of Marine Science and Engineering, 2024)
In this study, the finite element method combined with the model test method are used to investigate the ultimate strength of a target ship reactor hull structure under a pure bending load. Based on the distortion similarity theory and nonlinear similarity method, a scale model of the actual ship reactor hull structure is designed and the model collapse test is conducted. The ultimate bending moment obtained by the model test is transformed to the actual ship through the similarity transformation relationship and compared with the nonlinear finite element analysis result of the actual structure. The results are consistent with each other, which indicates that the collapse characteristics of the actual ship reactor hull structure can be better forecasted using the model test results when the test model is designed based on the nonlinear similarity method and distortion similarity theory.

Enhanced sensitivity of extracellular antibiotic resistance genes (ARGs) to environmental concentrations of antibiotic - Huai Lin; Ruiqing Li; Yuying Chen; Yuan Cheng; Qingbin Yuan; Yi Luo (Chemosphere, 2024)

Combined effects of cadmium and sulfamethoxazole on Eisenia fetida: Insights into accumulation, subcellular partitioning, biomarkers and toxicological responses - Sheng-Nan Zhang; Yi-Tong Zhou; Jun Xia; Yu-Meng Wang; Jun-Wei Ma; Li-Kun Wang; Kashif Hayat; Shan-shan Bai; Cheng-han Li; Ming-Rong Qian; Hui Lin (Science of The Total Environment, 2024)

Blending Saccharum bagasse and waste cooking oil for biofuel production via microwave co-torrefaction process - Yi-Li Lin; Nai-Yun Zheng; Hsin-Jou Cheng; Chao-Chin Chang (Fuel, 2024)

Tuning multiple enzyme-like activities by metal doping for identification and quantitation of antioxidants in cosmetics - Sheng-Tao Wu; Hui-Qi Su; Kai-Lin Shen; Ying Li; Yi Ge; Xiu-Fang Cheng; Chang-Ming Nie; Cong-Hui Wang; Ying-Wu Lin (Chemical Engineering Journal, 2024)

Erratum to: Cholesterol homeostasis regulated by ABCA1 is critical for retinal ganglion cell survival - Jialiang Yang; Yuhong Chen; Tongdan Zou; Bai Xue; Fang Yang; Xiangzhou Wang; Yibo Huo; Boyun Yan; Yuxia Xu; Shiyu He; Yi Yin; Jing Wang; et al. (Science China Life Sciences, 2024)

Characterization of a pangolin SARS-CoV-2-related virus isolate that uses the human ACE2 receptor - Luo-Yuan Xia; Xue-Feng Wang; Xiao-Ming Cui; Yi-Ming Zhang; Zhen-Fei Wang; En-Tao Li; Chang-Fa Fan; Ke Song; Yuan-Guo Li; Run-Ze Ye; Fang-Xu Li; Dai-Yun Zhu; et al. (Science China Life Sciences, 2024)

Assessment of PM2.5-associated mortality burden among the elderly: Insights into demographic, socio-economic, and geographic factors - Ayushi Sharma; Hsi-yu Hsiao; Jia-Yi Liu; Shih-Chun Candice Lung; Huey-Jen Su; Ching-Fen Shen; Nai-Tzu Chen; Pei-Chih Wu; Cheng-Yu Lin; Sheng-Fu Liang; Tain-Junn Cheng; Ta-Chien Chan; et al. (Air Quality, Atmosphere & Health, 2024)

Produce low-CO2 silica fume hybrid high-strength concrete using dry ice (solid CO2) as a CO2-utilized admixture - Mei-Yu Xuan; Run-Sheng Lin; Yi Han; Gui-yu Zhang; Cheng Guo; Xiao-Yong Wang (Journal of Cleaner Production, 2024)

Struvite and ethylenediaminedisuccinic acid (EDDS) enhance electrokinetic-biological permeable reactive barrier removal of copper and lead from contaminated loess - Lin Wang; Wen-Chieh Cheng; Zhong-Fei Xue; Md Mizanur Rahman; Yi-Xin Xie (Journal of Environmental Management, 2024)

Epigallocatechin-3-gallate stabilizes aqueous curcumin by generating nanoparticles and its application in beverages - Ruge Lin; Yi Wang; Huan Cheng; Xingqian Ye; Shiguo Chen; Haibo Pan (Food Chemistry, 2024)

The effects of repeated freezing and thawing on bovine sperm morphometry and function - Chang-Guo Min; Xin Ma; Yu-Chan Wang; Cheng-Kun Zhong; Chong-shan Yuan; Kai-Yan Zhang; Cheng-Lin Zhan; Sheng-Kui Hou; Xin-Hai Wang; Jun Wang; Jing Zhao; Yi Fang; et al. (Cryobiology, 2024)

Intrinsically stretchable jellyfish-like gold nanowires film as multifunctional wearable chemical and physical sensors - Heng Zhang; Fenge Lin; Gangsheng Chen; Cheng Yang; Hanqiang Zhang; Mengwen Yan; Heng Li; Xi Wang; Wenlong Cheng; Yi Chen (Chemical Engineering Journal, 2024)

Continuous microalgal culture module and method of culturing microalgae containing macular pigment - Meng-Wei Lin; Chih-Sheng Lin; Yu-Tso Chen; Shao-Qian Huang; Yi-Chun Yang; Wen-Xin Zhang; Wei-Hong Chiu; Cheng-Han Lin; Chiu-Mei Kuo (Bioresource Technology, 2024)

Correction to: P2 purinergic receptors regulate the progression of colorectal cancer - Wen‑jun Zhang; Li‑peng Zhang; Si‑jian Lin; Cheng‑yi Wang; Yi-guan Le (Purinergic Signalling, 2024)

An Automatic Approach of Video-Based Landmark Detection and Movement Analysis for Assessing Symptoms of Bradykinesia in Parkinson’s Disease - Ching-Fang Chien; Chen-Sen Ouyang; Yi-Hung Chiu; Lung-Chang Lin; Rei-Cheng Yang; Yang-Pei Chang; San-Yuan Wang; Li-Min Liou (Journal of Medical and Biological Engineering, 2024)

Fully automated learning and predict price of aquatic products in Taiwan wholesale markets using multiple machine learning and deep learning methods - Yi-Ting Lai; Yan-Tsung Peng; Wei-Cheng Lien; Yun-Chiao Cheng; Yi-Ting Lin; Chen-Jie Liao; Yu-Shao Chiu (Aquaculture, 2024)

Wavelength dependency and photosensitizer effects in UV-LED photodegradation of iohexol - Meng-Yuan Xu; Chao Zeng; Yi-Li Lin; Tian-Yang Zhang; Qi Fu; Heng-Xuan Zhao; Zhen-Ning Luo; Zheng-Xiong Zheng; Tong-Cheng Cao; Chen-Yan Hu; Bin Xu (Water Research, 2024)

Enhanced photodegradation of pentafluoropropionic acid (PFPA) via TiO2-synthetic zeolite composites: A sustainable approach for effective defluorination - Subham Halder; Feng-Chih Chou; Tsz-Kin Wan; Yi-Tien Tsai; Pei-Cheng Cheng; Yuan-Chung Lin (Journal of Water Process Engineering, 2024)

Deterioration phenomenon of Pb-contaminated aqueous solution remediation and enhancement mechanism of nano-hydroxyapatite-assisted biomineralization - Yi-Xin Xie; Wen-Chieh Cheng; Zhong-Fei Xue; Md Mizanur Rahman; Lin Wang (Journal of Hazardous Materials, 2024)

Stenotrophomonas maltophilia contributes to smoking-related emphysema through IRF1-triggered PANoptosis of alveolar epithelial cells - Haibo Xia; Jiaheng Lin; Yue Wang; Jinyan Yu; Hailan Wang; Cheng Cheng; Yi Yang; Tao Bian; Yan Wu; Qizhan Liu (Environmental Pollution, 2024)

A nonsynonymous mutation in BhLS, encoding an acyl-CoA N-acyltransferase leads to fruit and seed size variation in wax gourd (Benincasa hispida) - Jinqiang Yan; Jiaowen Cheng; Dasen Xie; Yi Wang; Min Wang; Songguang Yang; Biao Jiang; Lin Chen; Jinsen Cai; Wenrui Liu (Theoretical and Applied Genetics, 2024)

Short-term effects of exposure to cold spells on blood pressure among adults in Nanjing, China - Tian-Lin Li; Bei-Jing Cheng; Nan Jiang; Xing-Chen Meng; Chun Wang; Yang Huang; Ke Meng; Hui Li; Xin-Yi Zhu; Ran Liu (Air Quality, Atmosphere & Health, 2024)

Nucleocytoplasmic shuttling of BEFV M protein-modulated by lamin A/C and chromosome maintenance region 1 through a transcription-, carrier- and energy-dependent pathway - Yu-Kang Chang; Yi-Jyum Lin; Ching-Yuan Cheng; Pei-Chien Tsai; Chi-Young Wang; Brent L. Nielsen; Hung-Jen Liu (Veterinary Microbiology, 2024)

Molecular mechanism of efficient degradation of TPM dyes by Serratia species WKD at high temperature - Yi Wei; Xin-Jiao Dong; Gang Li; Huan Wu; Lin-Na Du; Jia-Cheng Zhou; Jun Zhang; Yan-Ping Xiao; Yue-Mei Shang; Hong-Xia Liu (International Biodeterioration & Biodegradation, 2024)

Diterpenoid alkaloids with chemotaxonomic significance from Aconitum polycarpum - Lin Chen; Jie Wen; Jia-Yi Ma; Ke Xu; Cheng-En Fu; Wen-Cheng Liang; Chen-Ying Zhu; Jin-Qiu Wang; Shuai Huang; Xian-Li Zhou (Biochemical Systematics and Ecology, 2024)

Exploring nanoparticle emissions and size distributions during incense burning and filtration in an indoor space - Hsi-Hsien Yang; Wei-Cheng Weng; Yong-Wen Chen; Xuan-Yi Lin; Ying I. Tsai (Air Quality, Atmosphere & Health, 2024)

Melatonin Enhanced Microglia M2 Polarization in Rat Model of Neuro-inflammation Via Regulating ER Stress/PPARδ/SIRT1 Signaling Axis - Hung-Chuan Pan; Cheng-Ning Yang; Wen-Jane Lee; Jason Sheehan; Sheng-Mao Wu; Hong-Shiu Chen; Mao-Hsun Lin; Li-Wei Shen; Shu-Hua Lee; Chin-Chang Shen; Liang-Yi Pan; Shing‑Hwa Liu; et al. (Journal of Neuroimmune Pharmacology, 2024)

Wind-driven hydrodynamic characteristics of Lake Taihu, a large shallow lake in China - Zongpu Xue; Wei Zhu; Lin Cheng; Yi Lv; Ganyu Feng (Environmental Science and Pollution Research, 2024)

Impact of occupational noise exposure on the hearing level in hospital staffs: a longitudinal study - Tang-Chuan Wang; You-Cheng Yu; Alan Hsu; Jia-Yi Lin; Yung-An Tsou; Chiu-Shong Liu; Kai-Jen Chuang; Wen-Chi Pan; Chin-An Yang; Sung-Lin Hu; Chien-Yi Ho; Tzu-Liang Chen; et al. (Environmental Science and Pollution Research, 2024)

Lacticaseibacillus chiayiensis mediate intestinal microbiome and microbiota-derived metabolites regulating the growth and immunity of chicks - Xin-Dong Li; Yao Lu; Cheng-Ying Luo; Wei-Gang Xin; Xin Kang; Yi-Cen Lin; Lian-Bing Lin (Veterinary Microbiology, 2024)

First insights into the bioaccumulation, biotransformation and trophic transfer of typical tetrabromobisphenol A (TBBPA) analogues along a simulated aquatic food chain - Chuan-Sheng Sun; Sheng-Wu Yuan; Rui Hou; Si-Qi Zhang; Qian-Yi Huang; Lang Lin; Heng-Xiang Li; Shan Liu; Yuan-Yue Cheng; Zhi-Hua Li; Xiang-Rong Xu (Journal of Hazardous Materials, 2024)

New insight into the bioaccumulation and trophic transfer of free and conjugated antibiotics in an estuarine food web based on multimedia fate and model simulation - Nian-Nian Wu; Shan Liu; Ru Xu; Qian-Yi Huang; Yun-Feng Pan; Heng-Xiang Li; Lang Lin; Rui Hou; Yuan-Yue Cheng; Xiang-Rong Xu (Journal of Hazardous Materials, 2024)

Anti-CD20 treatment attenuates Th2 cell responses: implications for the role of lung follicular mature B cells in the asthmatic mice - Jilong He; Jingling Li; Qibin Lin; Haiyang Ni; Sisi Huang; Hong Cheng; Xuhong Ding; Yi Huang; Hongying Yu; Yaqing Xu; Hanxiang Nie (Inflammation Research, 2024)

Pelagibacterium flavum sp. nov., Isolated from Soil Sample - Xue-Mei Chen; Zu-Zhen Yang; Si-Rong He; Lian-Shuang Xiong; Qing Yuan; Shu-Ya Zuo; Cheng-Lin Jiang; Yi Jiang (Current Microbiology, 2024)

Methionine redox regulation of actin-interacting proteins primarily governs antioxidative signaling and response to the salvianolic acid B treatment in EA.hy926 cells - Ai-Cheng Wang; Xiao-Ming Qi; Qing-Fang Li; Yi-Jia Feng; Yuan-Lin Zhang; Hui-Zhi Wei; Jin-Shan Li; Yuan-Biao Qiao; Qing-Shan Li (Toxicology and Applied Pharmacology, 2024)

Modification of cellulosic adsorbent via iron-based metal phenolic networks coating for efficient removal of chromium ion - Valentino Bervia Lunardi; Kuan-Chen Cheng; Shin-Ping Lin; Artik Elisa Angkawijaya; Alchris Woo Go; Felycia Edi Soetaredjo; Suryadi Ismadji; Hsien-Yi Hsu; Chang-Wei Hsieh; Shella Permatasari Santoso (Journal of Hazardous Materials, 2024)

Assessment of sources and health risks of heavy metals in metropolitan household dust among preschool children: The LEAPP-HIT study - Chi-Sian Kao; Ying-Lin Wang; Chuen-Bin Jiang; Pei-Ju Tai; Yi-Hua Chen; Hsing-Jasmine Chao; Yu-Chun Lo; Zeng-Yei Hseu; Hsing-Cheng Hsi; Ling-Chu Chien (Journal of Environmental Management, 2024)

Genome-wide identification of heat shock protein gene family and their responses to pathogen challenge in Trachinotus ovatus - Yi-Yao Sun; Hua-Yang Guo; Bao-Suo Liu; Nan Zhang; Ke-Cheng Zhu; Lin Xian; Peng-Hai Zhao; Hui-Yuan Yang; Dian-Chang Zhang (Fish & Shellfish Immunology, 2024)

Ozone containment through selective mitigation measures on precursors of volatile organic compounds - Sheng-Po Chen; Wen-Tzu Liu; Fang-Yi Cheng; Chieh-Heng Wang; Shih-Ming Huang; Jia-Lin Wang (Science of The Total Environment, 2024)

Steroid metabolites as overlooked emerging contaminants: Insights from multimedia partitioning and source–sink simulation in an estuarine environment - Ru Xu; Shan Liu; Yun-Feng Pan; Nian-Nian Wu; Qian-Yi Huang; Heng-Xiang Li; Lang Lin; Rui Hou; Xiang-Rong Xu; Yuan-Yue Cheng (Journal of Hazardous Materials, 2024)

The complexity of heatwaves impact on terrestrial ecosystem carbon fluxes: Factors, mechanisms and a multi-stage analytical approach - Lu-Ping Qu; Jiquan Chen; Jingfeng Xiao; Hans J. De Boeck; Gang Dong; Shi-Cheng Jiang; Ya-Lin Hu; Yi-Xuan Wang; Chang-Liang Shao (Environmental Research, 2024)

The role of oxide supports in constructing plasma-treated gold nanocatalysts for visible light photocatalytic oxidation of CO - Bin Zhu; Chong-Hua Zhong; Bang-You Jia; Tie Li; Jing-Lin Liu; Ye-Cheng Li; Yi-Min Zhu (Chemical Engineering Journal, 2024)

Estimating leaf age of maize seedlings using UAV-based RGB and multispectral images - Yi Bai; Liangsheng Shi; Yuanyuan Zha; Shuaibing Liu; Chenwei Nie; Honggen Xu; Hongye Yang; Mingchao Shao; Xun Yu; Minghan Cheng; Yadong Liu; Tao Lin; et al. (Computers and Electronics in Agriculture, 2023)

Clarification of the phosphorus release mechanism for recovering phosphorus from biofilm sludge in alternating aerobic/anaerobic biofilm system - Hao Zhang; Shuang-Shuang Zhang; Wei Zhang; Wu-Cheng Ma; Yang Pan; Lin Chen; Liang Zhu; Yi-Ping Li; Jing-Ru Li (Science of The Total Environment, 2023)

Evaluating the toxic mechanism of 1,2-diacetylbenzene in neural cells/tissues: The favorable impact of silibinin - Li-Yu Fay; Jun-Yi Chien; Ching-Feng Weng; Huai-Sheng Kuo; Dann-Ying Liou; Wei-Hao Weng; Chi-Hung Lin; Ya-Tzu Chen; Wen-Hung Huang; Wen-Cheng Huang; May-Jywan Tsai; Henrich Cheng (NeuroToxicology, 2023)

Complete genome analysis of type strain of a novel bacterial family Temperatibacteraceae fam. nov., isolated from surface seawater - Jin-Cheng Rong; Lin-Lin Cui; Xiao-Chen Yang; Mao-Li Yi; Qi Zhao (Marine Genomics, 2023)

Heterostructured YFeO3/CeO2 as efficient photoelectrode for photoelectrochemical degradation of organic pollutants under visible light irradiation - Yen-Shen Kuo; Mu-Jung Lin; Cheng-Liang Hsu; Yi-Hung Liu (Journal of Water Process Engineering, 2023)

Study on Cu- and Pb-contaminated loess remediation using electrokinetic technology coupled with biological permeable reactive barrier - Lin Wang; Wen-Chieh Cheng; Zhong-Fei Xue; Yi-Xin Xie; Xin-Jiang Lv (Journal of Environmental Management, 2023)

Inhibition of continuous cropping obstacle of celery by chemically modified biochar: An efficient approach to decrease bioavailability of phenolic allelochemicals - Chia-Chia Lin; Yu-Ting Liu; Po-Hsiang Chang; Yi-Cheng Hsieh; Yu-Min Tzou (Journal of Environmental Management, 2023)

A crosslinked waterborne poly(vinyl acetate) for greenhouse gas fixation with improved elastomeric properties, shape-memory ability, and recyclability - Yen-Chuan Chen; Ying-Chi Huang; Yi-Hua Huang; Ying-Feng Lin; Ho-Ching Huang; Ru-Jong Jeng; Yu-Wei Cheng; Chien-Hsin Wu (Journal of Environmental Chemical Engineering, 2023)

Species-specific primers in multiplex PCR for Bactrocera minax identification using an internal transcribed spacer - Prakriti Regmi; Cheng-Lung Tsai; Ming-Ying Lin; Yi-Yuan Chuang; Wen-Bin Yeh (Journal of Asia-Pacific Entomology, 2023)

Cannabidiol protects the liver from α-Amanitin-induced apoptosis and oxidative stress through the regulation of Nrf2 - Haowei Wang; Genmeng Yang; Xiaoxing Zhang; Huijie Zhang; Yan Liu; Chan Wang; Lin Miao; Yi Li; Yizhen Huang; Hanxin Teng; Shangwen Wang; Hao Cheng; et al. (Food and Chemical Toxicology, 2023)

Applying the first microcapsule-based self-healing microbial-induced calcium carbonate materials to prevent the migration of Pb ions - Zhong-Fei Xue; Wen-Chieh Cheng; Lin Wang; Peng Qin; Yi-Xin Xie; Wenle Hu (Environmental Research, 2023)

Joint effects of prenatal exposure to air pollution and pregnancy-related anxiety on birth weight: A prospective birth cohort study in Ma’anshan, China - Zhen-Hua Li; Yi-Cheng Mao; Yang Li; Sun Zhang; Hui-Yu Hu; Zhe-Ye Liu; Xue-Jie Liu; Jia-Wen Zhao; Kai Huang; Mao-Lin Chen; Guo-Peng Gao; Cheng-Yang Hu; et al. (Environmental Research, 2023)

Accumulated Hepatic Steatosis Grades Predicted by T2*-IDEAL Fat Fraction - Chang-Hsien Liu; Hing-Chiu Chang; Yi-Jui Liu; Wei-Ching Lin; Chi-Feng Hsieh; Te-Pao Lin; Cheng-Hsuan Juan; William Tzu-Liang; Chun-Jung Juan (Journal of Medical and Biological Engineering, 2023)

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

Joint full waveform inversion of multiple instantaneous attributes - Kai Zhang; Yi-peng Xu; Fei Xie; Cheng-hong Zhu; Zhen-chun Li; Zi-Lin He (Applied Geophysics, 2023)

Association of mono-2-ethylhexyl phthalate with adverse outcomes in chronic hemodialysis patients - Chia-Lin Wu; Yu-Wei Fang; Yi-Chou Hou; Kuo-Cheng Lu; Wen-Hsin Tsai; Ping-Hsun Lu; Tzong-Shyuan Lee; Ko-Lin Kuo (Environmental Science and Pollution Research, 2023)
Phthalate exposure is widespread and has a global impact. Growing evidence shows that mono-2-ethylhexyl phthalate (MEHP) exposure has a negative impact on human health. However, whether MEHP exposure is associated with mortality and other adverse outcomes in hemodialysis patients remains unknown. This study prospectively enrolled 217 patients on maintenance hemodialysis from June 30, 2021, to August 16, 2022. Baseline serum MEHP, di-2-ethylhexyl phthalate (DEHP), and indoxyl sulfate (IS) concentrations were measured. Primary endpoints were all-cause mortality or composite adverse outcomes, including all-cause death plus hospitalization due to cardiovascular disease, heart failure, stroke, infection, or cancer. Serum MEHP concentrations were positively associated with DEHP but not indoxyl sulfate concentrations in hemodialysis patients. Additionally, serum MEHP concentrations were significantly and independently associated with all-cause mortality and composite adverse outcomes (adjusted hazard ratios [HRs], 1.04 and 1.03 per ng/mL, 95% confidence intervals [CIs], 1.01–1.07 and 1.00–1.05; p = 0.016 and 0.015, respectively). We found a cutoff value of MEHP for predicting both endpoints. Patients with serum MEHP concentrations of ≥ 41.8 ng/mL had much higher risks for all-cause mortality and composite adverse outcomes (adjusted HRs, 39.2 and 13; 95% CIs, 2.44–65.7 and 2.74–61.4; p = 0.011 and 0.001, respectively). MEHP exposure is significantly associated with higher risks for all-cause mortality and composite adverse outcomes. Hemodialysis patients with serum MEHP concentrations above 41.8 ng/mL had much poorer prognoses regarding both outcomes.

Litter traps: A comparison of four marine habitats as sinks for anthropogenic marine macro-litter in Singapore - Jenny Fong; Samuel Hsien Rong Lee; Yuchen Sun; Cheng Ling Lim; Yean Ai Jolin Tan; Yi Hong Tan; Mei Lin Neo (Marine Pollution Bulletin, 2023)

Development and application of an interactive generic physiologically based pharmacokinetic (igPBPK) model for adult beef cattle and lactating dairy cows to estimate tissue distribution and edible tissue and milk withdrawal intervals for per- and polyfluoroalkyl substances (PFAS) - Wei-Chun Chou; Lisa A. Tell; Ronald E. Baynes; Jennifer L. Davis; Yi-Hsien Cheng; Fiona P. Maunsell; Jim E. Riviere; Zhoumeng Lin (Food and Chemical Toxicology, 2023)

Quantifying the potential effects of air pollution reduction on population health and health expenditure in Taiwan - Yi-Hsuan Roger Chen; Wan-Chen Lee; Bo-Chen Liu; Po-Chieh Yang; Chi-Chang Ho; Jing-Shiang Hwang; Tzu-Hsuan Huang; Hsien-Ho Lin; Wei-Cheng Lo (Environmental Pollution, 2023)

Unlocking the potential of elemental sulfur autotrophic denitrification through inorganic nutrient optimization - Yi-Lu Sun; Xue-Ning Zhang; Han-Lin Wang; Chen-Yang Shao; Wei-Qin Zhuang; Hao-Yi Cheng; Ji-Xian Yang; Ai-Jie Wang (Chemical Engineering Journal, 2023)

Response of topsoil Fe-bound organic carbon pool and microbial community to Spartina alterniflora invasion in coastal wetlands - Meifen Lin; Yu Chen; Liwen Cheng; Yi Zheng; Weiqi Wang; Jordi Sardans; Zhaoliang Song; Georg Guggenberger; Yuanchun Zou; Xueli Ding; Akash Tariq; Fanjiang Zeng; et al. (CATENA, 2023)

The disruption of blood-brain barrier induced by long-term arsenic exposure is associated with the increase of MMP-9 and MMP-2: The characteristics are similar to those caused by senescence - Man Lv; Xinbo Ma; Kunyu Zhang; Meichen Zhang; Yi Ji; Lin Cheng; Xinhua Shao; Ziqiao Guan; Jia Cui; Yanhui Gao; Yang Liu; Yanmei Yang; et al. (Chemico-Biological Interactions, 2023)

Biopolymer-assisted enzyme-induced carbonate precipitation for immobilizing Cu ions in aqueous solution and loess - Yi-Xin Xie; Wen-Chieh Cheng; Lin Wang; Zhong-Fei Xue; Yin-Long Xu (Environmental Science and Pollution Research, 2023)

The modification of meteorological factors on the relationship between air pollution and periodontal diseases: an exploration based on different interaction strategies - Kai Huang; Lin-Fei Feng; Zhe-Ye Liu; Zhen-Hua Li; Yi-Cheng Mao; Xin-Qiang Wang; Jia-Wen Zhao; Kang-Di Zhang; Ying-Qing Li; Jie Wang; Wen-Jie Yu; Xin Cheng; et al. (Environmental Geochemistry and Health, 2023)

Acoustic Field Radiation Prediction and Verification of Underwater Vehicles under a Free Surface - Yung-Wei Chen; Cheng-Cheng Pan; Yi-Hsien Lin; Chao-Feng Shih; Jian-Hong Shen; Chun-Ming Chang (Journal of Marine Science and Engineering, 2023)
This study aimed to examine the acoustic field radiated by propellers and underwater vehicles. For the verification of sound radiation in underwater vehicles, numerical methods are widely used in addition to experiments and propeller blade frequencies for calculation and validation. Numerical convergence and accuracy are more important for near-field and far-field problems. This paper uses the boundary element method (BEM) to assess the convergence of the finite volume method (FVM). In this study, the FVM, including the Reynolds-averaged Navier–Stokes method and the Ffowcs Williams–Hawkings (FW-H) acoustic model, is used to investigate the influence of various geometric inflows on the hydrodynamic and noise performance of the propeller. Then, the sound radiation of the FVM is compared with the BEM at the far field to determine the number of meshed elements. Furthermore, spectral analysis is being conducted to examine the noise generated by the underwater vehicle and propeller. The objective is to investigate the influence of the free surface on propeller efficiency. After verifying the numerical simulation, the results indicate that a relationship can be established between water pressure and propeller thrust under specific conditions. This relationship can be used to estimate the magnitude of propeller thrust at different water depths. The simulated results of propeller thrust, torque coefficient, propulsion efficiency, and sound radiation in this study are consistent with experimental values. This demonstrates the accuracy and practicality of the findings of numerical procedures in engineering applications.

Opportunities and challenges for ribosome-inactivating proteins in traditional Chinese medicine plants - Yi-xuan Yang; Xin-yi Wang; Tong Lin; Yu Sun; Yi-cheng Yu; Zhen-hong Zhu (Toxicon, 2023)

Recovering phosphorus and lithium separately from wastewater and brine using a novel coupled biofilm-precipitation system - Hao Zhang; Shuang-Shuang Zhang; Wei Zhang; Wu-Cheng Ma; Yi-Ping Li; Lin Chen; Liang Zhu; Yang Pan (Journal of Water Process Engineering, 2023)

High photocatalytic performance of ferroelectric AgNbO3 in a doping state - Lei Jiang; Xiaohua Huang; Yi Zhou; Shengli Huang; Yiwei Wang; Zijian Wang; Dong Sun; Hongyi Lin; Zaijun Cheng (Journal of Environmental Chemical Engineering, 2023)

Damage detection of bridges subjected to moving load based on domain-adversarial neural network considering measurement and model error - Zhi-Dong Li; Wen-Yu He; Wei-Xin Ren; Yi-Lin Li; Yi-Fan Li; Hua-Cai Cheng (Engineering Structures, 2023)

Combining HUMSC secretome and a conductive hydrogel enhances angiogenesis and electrical transmission at myocardial infarct sites to support cardiac repair - Shu-yi He; Lin-yu Long; Zhi-cun Wang; Wen-qi Liu; Wen Zhang; Cheng Hu; Xiao-feng Wu; Ruiqi Dong; Hong-song Fan; Qing-Jiang; Ying-ying Tong; Guang-hua Yang; et al. (Chemical Engineering Journal, 2023)

SERS-based rapid susceptibility testing of commonly administered antibiotics on clinically important bacteria species directly from blood culture of bacteremia patients - Yin-Yi Han; Jann-Tay Wang; Wei-Chih Cheng; Ko-Lun Chen; Yi Chi; Lee-Jene Teng; Juen-Kai Wang; Yuh-Lin Wang (World Journal of Microbiology and Biotechnology, 2023)
Bloodstream infections are a growing public health concern due to emerging pathogens and increasing antimicrobial resistance. Rapid antibiotic susceptibility testing (AST) is urgently needed for timely and optimized choice of antibiotics, but current methods require days to obtain results. Here, we present a general AST protocol based on surface-enhanced Raman scattering (SERS-AST) for bacteremia caused by eight clinically relevant Gram-positive and Gram-negative pathogens treated with seven commonly administered antibiotics. Our results show that the SERS-AST protocol achieves a high level of agreement (96% for Gram-positive and 97% for Gram-negative bacteria) with the widely deployed VITEK 2 diagnostic system. The protocol requires only five hours to complete per blood-culture sample, making it a rapid and effective alternative to conventional methods. Our findings provide a solid foundation for the SERS-AST protocol as a promising approach to optimize the choice of antibiotics for specific bacteremia patients. This novel protocol has the potential to improve patient outcomes and reduce the spread of antibiotic resistance.

NRF2 Antagonizes HIV-1 Tat and Methamphetamine-Induced BV2 Cell Ferroptosis by Regulating SLC7A11 - Shucheng Lin; Hao Cheng; Genmeng Yang; Chan Wang; Chi-Kwan Leung; Shuwei Zhang; Yi Tan; Huijie Zhang; Haowei Wang; Lin Miao; Yi Li; Yizhen Huang; et al. (Neurotoxicity Research, 2023)

Climatic Fluctuation of Marine Isotope Stage 9: A Case Study in the Southern Margin of the Chinese Loess Plateau - Tieniu Wu; Antai Cheng; Henry Lin; Hailin Zhang; Yi Jie (Journal of Earth Science, 2023)

Short-term effects of cold spells on hematocrit among adults in Nanjing, China: A distributed-lagged effect analysis - Bei-Jing Cheng; Tian-Lin Li; Hui Li; Ke Meng; Xing-Chen Meng; Jia Wang; Chun Wang; Lin-Sheng Yang; Xin-Yi Zhu; Ran Liu (Science of The Total Environment, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Loss of OsARF18 function confers glufosinate resistance in rice - Jin-Qiu Xia; Da-Yu He; Qin-Yu Liang; Zheng-Yi Zhang; Jie Wu; Zi-Sheng Zhang; Jing Zhang; Lin Wang; Cong-He Zhang; Ping-Xia Zhao; Cheng-Bin Xiang (Molecular Plant, 2023)

Tuning the intrinsic catalytic sites of magnetite to concurrently enhance the reduction of H2O2 and O2: Mechanism analysis and application potential evaluation - Ling Li; Min Cheng; Eydhah Almatrafi; Lei Qin; Shiyu Liu; Huan Yi; Lu Yang; Zhexin Chen; Dengsheng Ma; Mingming Zhang; Xuerong Zhou; Fuhang Xu; et al. (Journal of Hazardous Materials, 2023)

Simultaneous phosphorus recovery from wastewater and sludge by a novel denitrifying phosphorus removal system - Hao Zhang; Wei Zhang; Shuang-Shuang Zhang; Wu-Cheng Ma; Liang Zhu; Yi-Ping Li; Yang Pan; Lin Chen (Bioresource Technology, 2023)

Schizophrenia in the genetic era: a review from development history, clinical features and genomic research approaches to insights of susceptibility genes - Ye Lv; Lin Wen; Wen-Juan Hu; Chong Deng; Hui-Wen Ren; Ya-Nan Bao; Bo-Wei Su; Ping Gao; Zi-Yue Man; Yi-Yang Luo; Cheng-Jie Li; Zhi-Xin Xiang; et al. (Metabolic Brain Disease, 2023)

Quantifying effect of maize tassels on LAI estimation based on multispectral imagery and machine learning methods - Mingchao Shao; Chenwei Nie; Aijun Zhang; Liangsheng Shi; Yuanyuan Zha; Honggen Xu; Hongye Yang; Xun Yu; Yi Bai; Shuaibing Liu; Minghan Cheng; Tao Lin; et al. (Computers and Electronics in Agriculture, 2023)

Bidirectional crosstalk of the cAMP/ROS-dependent signaling pathways in inflammatory macrophage: An activation of formononetin - Lan-Fang Zhang; Xiao-Yan Zhang; Ai-Cheng Wang; Yi-Jia Feng; Xiao-Ming Qi; Yuan-Lin Zhang; Qing-Fang Li; Yuan-Biao Qiao; Qing-Shan Li (Toxicology and Applied Pharmacology, 2023)

Catalytically efficient Co-CoOx-Al2O3 interface for mild temperature fatty alcohol production via fatty acid transfer hydrogenation - Yi Chen; Yongsheng Zhang; Wei Lin; Xianglin Cheng; Jianshe Wang; Xiaolong Liu; Chunbao Charles Xu; Renfeng Nie (Fuel, 2023)

Response of sulfur-metabolizing biofilm to external sulfide in element sulfur-based denitrification packed-bed reactor - Hong-Xu Bao; Han-Lin Wang; Shu-Tong Wang; Yi-Lu Sun; Xue-Ning Zhang; Hao-Yi Cheng; Zhi-Min Qian; Ai-Jie Wang (Environmental Research, 2023)

Correction: Common Subtype of Small Renal Mass MR Imaging Characterisation: A Medical Center Experience in Taiwan - Ming-Cheng Liu; Yi-Jui Liu; Yen-Ting Lin; Siu-Wan Hung; Jyh-Wen Chai; Si-Wa Chan; Kun-Yuan Chiu; Ya-Ling Tsou (Journal of Medical and Biological Engineering, 2023)

Assessing Carbon Abatement Costs Considering Forest Carbon Sequestration and Carbon Offset Mechanism: Evidence from Taiwan - Wan-Yu Liu; Yi-Hsin Lu; Chun-Cheng Lin (Forest Science, 2023)
Based on the Greenhouse Gas Reduction and Management Act passed in 2015 and the carbon neutral target in 2050, Taiwan will most likely follow international trends by imposing carbon taxes and establishing carbon offset markets. The positive and negative effects of carbon taxes and carbon offset markets on the economy and the environment merit further investigation. Accordingly, this study adopted a carbon emission reduction (CER) cost prediction model to assess the carbon abatement costs under three scenarios: (1) a carbon offset market exists, and forest carbon sequestration can be used as carbon offsets; (2) a carbon offset market exists, but forest carbon sequestration cannot be used as carbon offsets; and (3) a carbon offset market does not exist. Forests in Taipei (with low carbon emissions) and Kaohsiung (with high carbon emissions) were selected as research sites to explore the benefits of carbon emissions trading and forest carbon sequestration. The results show that CER costs are the lowest in scenario 1 and are the highest in scenario 3. The CER costs of Kaohsiung are higher than those of Taipei. The higher the carbon price, the greater the difference in CER costs between the two cities. Study Implications: The objective of this study was to identify the optimal policy for Taiwan to effectively slow climate change. This study showed that the opening of carbon offset markets and the use of forest carbon sequestration as carbon offsets may prompt regions to increase their forest stock to lower their emission reduction costs. However, achieving 2050 carbon neutral target by solely using forest carbon sequestration is not sufficient in Taiwan.

Culturing reef-building corals on a laboratory dish: a simple experimental platform for stony corals - Shinya Shikina; Tzu-Chieh Lin; Yu-Ling Chu; Yin-Chu Cheng; Yu-En Chang; Naohisa Wada; Sen-Lin Tang; Yoshiyuki Iizuka; Yi-Ling Chiu (Frontiers in Marine Science, 2023)
Development and maintenance of coral reef ecosystems rely on daily micro-biological activities of healthy corals. Although a comprehensive understanding of coral biological properties, as well as factors negatively affecting coral growth, are essential to conserve existing corals, the current lack of a tractable culture and experimental platform has delayed acquisition of such knowledge. Here we show a highly versatile culture system, “coral-on-a-laboratory dish” (CLD), allowing long-term culturing of various corals in plastic/glass Petri dishes with maintenance of their biological properties. Under optimized conditions, coral microcolonies (~5 mm x 5 mm fragments) of Pocillopora damicornis were cultured for several months in dishes with high survivorship and characteristic growth. These microcolonies maintained their biological properties, such as reproduction, skeleton formation, coral-algal symbiosis, ingestion, and digestion. Thus far, CLD has been used to maintain at least 4 other coral species from 4 other families, including the Acroporidae, the Pocilloporidae, the Poritidae, and the Merulinidae for more than 2 months with 100% survivorship. CLD is applicable to a variety of biophysiological studies, including coral-algal symbiosis and impact assessment of marine pollutants, e.g., a sunscreen substance, oxybenzone, and an organic biocide, Irgarol 1051, at cellular-level resolution. The CLD platform, which allows easy and inexpensive coral maintenance in a laboratory incubator, represents a technological breakthrough that will greatly advance coral studies.

TRPC6 promotes daunorubicin-induced mitochondrial fission and cell death in rat cardiomyocytes with the involvement of ERK1/2-DRP1 activation - Li-Xia Xu; Rui-Xing Wang; Jian-Feng Jiang; Gao-Cheng Yi; Jin-Jin Chang; Rui-Lan He; Hai-Xia Jiao; Bin Zheng; Long-Xin Gui; Jun-Jin Lin; Zhi-Hong Huang; Mo-Jun Lin; et al. (Toxicology and Applied Pharmacology, 2023)

Applicability of carbonate clumped isotope thermometry in the Tuchang-Jentse geothermal field - Yi-Chia Lu; Sheng-Rong Song; Ling-Wen Liu; Tsung-Ren Peng; Bill Bing-Cheng Chen; Remy Kai-Cheng Tu; Li-Hung Lin; Pei-Ling Wang (Geothermics, 2023)

Updates on applications of low-viscosity grade Hydroxypropyl methylcellulose in coprocessing for improvement of physical properties of pharmaceutical powders - Cheng Jin; Fei Wu; Yanlong Hong; Lan Shen; Xiao Lin; Lijie Zhao; Yi Feng (Carbohydrate Polymers, 2023)

Chronology and critical metals enrichment mechanism of ferromanganese nodules from the Parece Vela Basin, Philippine Sea - Yulong Cheng; Yonghang Xu; Liang Yi; Dongyi Li; Fanyu Lin; Xijie Yin; Aijun Wang (Chemical Geology, 2023)

Ganglioside-focused Glycan Array Reveals Abnormal Anti-GD1b Auto-antibody in Plasma of Preclinical Huntington’s Disease - Tien-Wei Lin; Jung-Kai Chang; Yih-Ru Wu; Tsung-Hsien Sun; Yang-Yu Cheng; Chien-Tai Ren; Mei-Hung Pan; Jin-Lin Wu; Kuo-Hsuan Chang; Hwai-I Yang; Chiung-Mei Chen; Chung-Yi Wu; et al. (Molecular Neurobiology, 2023)

Influence of microclimate control on the growth of asparagus under greenhouse in tropical climates - Kuo-An Hung; Yi-Wei Hsu; Yu-Cheng Chen; Tzu-Ping Lin (International Journal of Biometeorology, 2023)

Exosomal MiR-381 from M2-polarized macrophages attenuates urethral fibroblasts activation through YAP/GLS1-regulated glutaminolysis - Ye-Hui Chen; Yi-Cheng Xu; Ting-Ting Lin; Hang Chen; Ru-Nan Dong; Feng-Ping Cai; Zhi-Bin Ke; Jia-Yin Chen; Yong Wei; Qing-Shui Zheng; Xue-Yi Xue; Ning Xu (Inflammation Research, 2023)

Euphpepluone S, a new lathyrane diterpenoid with anti-inflammatory activity from Euphorbia peplus L. - Shi-Peng Guan; Ying Yang; Mao Sun; Min Cai; Xue-Xue Pu; Jian-Yi Huang; Ping Yi; Lin Liu; Ming-Rui Yuan; Yuan-Yuan Cheng; Ying-Tong Di (Phytochemistry Letters, 2023)

Gestational cadmium exposure disrupts fetal liver development via repressing estrogen biosynthesis in placental trophoblasts - Yi-Ting Fu; Jin Zhang; Wei-Bo Liu; Yu-Feng Zhang; Shuang Zhang; Lu-Lu Tan; Qing Lin; Kong-Wen Ou-Yang; Yong-Wei Xiong; Wei Chang; Hao Li; Jun-Ying Yu; et al. (Food and Chemical Toxicology, 2023)

Epitomizing biohydrogen production from microbes: Critical challenges vs opportunities - Jia Min Woon; Kuan Shiong Khoo; Asla A. AL-Zahrani; Meznah M. Alanazi; Jun Wei Lim; Chin Kui Cheng; Nurul Tasnim Sahrin; Fatima Musa Ardo; Sun Yi-Ming; Kuen-Song Lin; John Chi-Wei Lan; Md Sohrab Hossain; et al. (Environmental Research, 2023)

Long-term DEHP/MEHP exposure promotes colorectal cancer stemness associated with glycosylation alterations - Pei-Chun Shih; Hsin-Pao Chen; Ching-Cheng Hsu; Chung-Hsien Lin; Chou-Yuan Ko; Chao-Wen Hsueh; Cheng-Yi Huang; Tian-Huei Chu; Cheng-Chun Wu; Yu-Cheng Ho; Ngoc Uyen Nhi Nguyen; Shih-Chung Huang; et al. (Environmental Pollution, 2023)

Rice OsHsp16.9A interacts with OsHsp101 to confer thermotolerance - Yi-Hsin Liu; Tong-Seung Tseng; Ching-Rong Wu; Shu-Ting Cho; Chih-Horng Kuo; Xin-Jie Huang; Jung-Yi Cheng; Kuo-Hsuan Hsu; Kung-Fu Lin; Chia-Chin Liu; Ching-Hui Yeh (Plant Science, 2023)

Feasibility study of applying electrokinetic technology coupled with enzyme-induced carbonate precipitation treatment to Cu- and Pb-contaminated loess remediation - Lin Wang; Wen-Chieh Cheng; Zhong-Fei Xue; Yi-Xin Xie; Xin-Jiang Lv (Journal of Cleaner Production, 2023)

Selective accumulation of ionic nanocrystal H2 storage system as an in situ H2/boric acid nanogenerator fights against ethanol-induced gastric ulcers - Chih-Wei Chou; Wei-Tso Chia; Cam-Hoa Mac; Cheng-Yu Wu; Chun-Chieh Chen; Hsiang-Lin Song; Yi-Hsuan Lin; Yu-Jung Lin; Hsing-Wen Sung (Chemical Engineering Journal, 2023)

Quercetin alleviates tubulointerstitial inflammation by inhibiting exosomes-mediated crosstalk between tubular epithelial cells and macrophages - Di Yin; Jing-Yuan Cao; Yan Yang; Zhong-Tang Li; Hong Liu; Tao-Tao Tang; Wei-Jie Ni; Yi-Lin Zhang; Wei Jiang; Yi Wen; Zuo-Lin Li; Jing Zhao; et al. (Inflammation Research, 2023)

In vitro and in vivo anti-tumor activity of Coenzyme Q0 against TWIST1-overexpressing HNSCC cells: ROS-mediated inhibition of EMT/metastasis and autophagy/apoptosis induction - Hsin-Ling Yang; Li-Wen Chiu; Yi-An Lin; Sudhir Pandey; Chithravel Vadivalagan; Jiunn-Wang Liao; Yugandhar Vudhya Gowrisankar; Hui-Jye Chen; Hui-Yi Lin; You-Cheng Hseu (Toxicology and Applied Pharmacology, 2023)

Toward sustainable inland aquaculture: Coastal subsidence monitoring in Taiwan - Wei-Chia Hung; Cheinway Hwang; Luigi Tosi; Shao-Hung Lin; Pei-Ching Tsai; Yi-An Chen; Wei-Ji Wang; En-Cheng Li; Sihao Ge (Remote Sensing Applications: Society and Environment, 2023)

Investigating immobilization efficiency of Pb in solution and loess soil using bio-inspired carbonate precipitation - Zhong-Fei Xue; Wen-Chieh Cheng; Yi-Xin Xie; Lin Wang; Wenle Hu; Bin Zhang (Environmental Pollution, 2023)

Cesium exposure and pulmonary function decline: Potential mediating role of oxidative stress in chronic obstructive pulmonary disease patients - Min-Min Tang; Xue-Feng Hou; Jing Sun; Jia-Yi Cheng; You-Peng Deng; Meng-Die Li; Ling Liu; Dong-Xu Hua; Jin Yang; Ya-Lin Jiang; Lin Fu; Hui Zhao (Atmospheric Pollution Research, 2023)

α7 nicotinic acetylcholine receptor agonist improved brain injury and impaired glucose metabolism in a rat model of ischemic stroke - Ya-Yu Wang; Shih-Yi Lin; Cheng-Yi Chang; Chih-Cheng Wu; Wen-Ying Chen; Wei-Chi Huang; Su-Lan Liao; Wen-Yi Wang; Chun-Jung Chen (Metabolic Brain Disease, 2023)

Coenzyme Q0 defeats NLRP3-mediated inflammation, EMT/metastasis, and Warburg effects by inhibiting HIF-1α expression in human triple-negative breast cancer cells - Hsin-Ling Yang; Ping-Yu Lin; Chithravel Vadivalagan; Yi-An Lin; Kai-Yuan Lin; You-Cheng Hseu (Archives of Toxicology, 2023)

Whole-genome sequencing reveals putative underlying mechanisms of biocontrol capability of IBFCBF-5 - Chen Luo; Ai-rong Shen; Ye-song Ren; Yang Zhai; Yi Cheng; Jianping Xu; Lin Wei; Ji-lie Li; Liang-bin Zeng (Acta Physiologiae Plantarum, 2023)

Pharmacokinetics and residue elimination of metalaxyl enantiomers in snakehead (Channa argus) - Hao Zhou; Meiyu Zhang; Qi Shan; Heqing Huang; Meiling Zhang; Shugui Liu; Jiawei Lin; Lisha Ma; Guangming Zheng; Lichun Li; Cheng Zhao; Xiaoxin Dai; et al. (Aquaculture, 2023)

Corrigendum to “Induction of core symptoms of autism spectrum disorders by in vivo CRISPR/Cas9-based gene editing in the brain of adolescent rhesus monkeys” [Sci. Bull. 66(9) (2021) 937–946] - Shi-Hao Wu; Xiao Li; Dong-Dong Qin; Lin-Heng Zhang; Tian-Lin Cheng; Zhi-Fang Chen; Bin-Bin Nie; Xiao-Feng Ren; Jing Wu; Wen-Chao Wang; Ying-Zhou Hu; Yi-lin Gu; et al. (Science Bulletin, 2023)

Rapid shifts in thermal reaction norms and tolerance of brooded coral larvae following parental heat acclimation - Lei Jiang; Cheng‐Yue Liu; Guoxin Cui; Lin‐Tao Huang; Xiao‐Lei Yu; You‐Fang Sun; Hao‐Ya Tong; Guo‐Wei Zhou; Xiang‐Cheng Yuan; Yi‐Si Hu; Wen‐Liang Zhou; Manuel Aranda; et al. (Molecular Ecology, 2023)
Thermal priming of reef corals can enhance their heat tolerance; however, the legacy effects of heat stress during parental brooding on larval resilience remain understudied. This study investigated whether preconditioning adult coral Pocillopora damicornis to high temperatures (29°C and 32°C) could better prepare their larvae for heat stress. Results showed that heat‐acclimated adults brooded larvae with reduced symbiont density and shifted thermal performance curves. Reciprocal transplant experiments demonstrated higher bleaching resistance and better photosynthetic and autotrophic performance in heat‐exposed larvae from acclimated adults compared to unacclimated adults. RNA‐seq revealed strong cellular stress responses in larvae from heat‐acclimated adults that could have been effective in rescuing host cells from stress, as evidenced by the widespread upregulation of genes involved in cell cycle and mitosis. For symbionts, a molecular coordination between light harvesting, photoprotection and carbon fixation was detected in larvae from heat‐acclimated adults, which may help optimize photosynthetic activity and yield under high temperature. Furthermore, heat acclimation led to opposing regulations of symbiont catabolic and anabolic pathways and favoured nutrient translocation to the host and thus a functional symbiosis. Notwithstanding, the improved heat tolerance was paralleled by reduced light‐enhanced dark respiration, indicating metabolic depression for energy saving. Our findings suggest that adult heat acclimation can rapidly shift thermal tolerance of brooded coral larvae and provide integrated physiological and molecular evidence for this adaptive plasticity, which could increase climate resilience. However, the metabolic depression may be maladaptive for long‐term organismal performance, highlighting the importance of curbing carbon emissions to better protect corals.

The extract from aerial part of Scutellaria baicalensis regulates gut microbiota in rabbit fish: Replacement of antibiotic fighting against pathogenic bacteria - Yi-Teng Xia; Edwin Hok-Chi Cheng; Huai-You Wang; Lynn Hoi-Lam Zhang; Sheng-Ying Lin; Tina Ting-Xia Dong; Ran Duan; Qi-Wei Qin; Wen-Xiong Wang; Karl Wah-Keung Tsim (Aquaculture, 2023)

Immobilizing copper in loess soil using microbial-induced carbonate precipitation: Insights from test tube experiments and one-dimensional soil columns - Yi-Xin Xie; Wen-Chieh Cheng; Lin Wang; Zhong-Fei Xue; Md Mizanur Rahman; Wenle Hu (Journal of Hazardous Materials, 2023)

Effect of species, muscle location, food processing and refrigerated storage on the fish allergens, tropomyosin and parvalbumin - Chia-Lin Tsai; Kristy Perng; Yu-Chen Hou; Cheng-Jou Shen; I-Ning Chen; Yi-Tien Chen (Food Chemistry, 2023)

In vitro and in vivo anti-tumor activity of Antrodia salmonea against twist-overexpressing HNSCC cells: Induction of ROS-mediated autophagic and apoptotic cell death - Hsin-Ling Yang; Yi-An Lin; Sudhir Pandey; Jiunn-Wang Liao; Tzong-Der Way; Yu-lyu Yeh; Siang-Jyun Chen; You-Cheng Hseu (Food and Chemical Toxicology, 2023)

Patterns of organic carbon and nitrogen stocks in soil particle-size fractions along an aridity gradient in Northern China’s deserts - Yan-gui Su; Gang Huang; Si-nuo Lin; Zheng-yi Huang; Guo-peng Wu; Hao Cheng (CATENA, 2023)

Short-Term Limited Water Irrigation Influences the Photosynthetic Pigments, Enzymatic and Non-Enzymatic Activities in Saccharum spontaneum L. at Vegetative Stage - Zhi-Nian Deng; Hai-Rong Huang; Cheng-Mei Huang; Krishan K. Verma; Hai-Bin Luo; Sheng-Li Jiang; Yi-Jie Li; Hui-Qing Cao; Kai-Chao Wu; Lin Xu (Sugar Tech, 2023)

Cholesterol homeostasis regulated by ABCA1 is critical for retinal ganglion cell survival - Jialiang Yang; Yuhong Chen; Tongdan Zou; Bai Xue; Fang Yang; Xiangzhou Wang; Yibo Huo; Boyun Yan; Yuxia Xu; Shiyu He; Yi Yin; Jing Wang; et al. (Science China Life Sciences, 2023)

Two new chromones and a new coumarin from the fruit of Cnidium monnieri (L.) Cusson - Hui-Chi Huang; Chun-Hsiang Lin; Ching-Chuan Kuo; Ming-Der Wu; Ming-Jen Cheng; Jih-Jung Chen; Che-Yi Chao; Guan-Jhong Huang; Yueh-Hsiung Kuo (Natural Product Research, 2023)

Combined effects of prenatal phthalate exposure on cardiometabolic risk score among 4- to 7-year-old children: MABC study - Hui Gao; Meng-long Geng; Juan Tong; Bao-lin Wang; Kun Huang; Yi Zhang; Hong Gan; Bei-bei Zhu; Peng Ding; Qu-nan Wang; Jian-qing Wang; Cheng Zhang; et al. (Chemosphere, 2023)

Assessing consumer perceptions of chemical leasing business models and possibilities for adoption by Taiwanese manufacturers - Chen-Fu Lu; Chia-Yi Cheng; Ying-Lin Hung (Sustainable Production and Consumption, 2023)

Mapping Chinese annual gross primary productivity with eddy covariance measurements and machine learning - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Shi-Ping Chen; Shao-Min Liu; Hui-Min Wang; Jun-Hua Yan; Jun-Lei Tan; Fa-Wei Zhang; et al. (Science of The Total Environment, 2023)

Corrigendum to “Comparative efficacy of omega-3 polyunsaturated fatty acids on major cardiovascular events: A network meta-analysis of randomized controlled trials” [Progress in Lipid Research. 2022 Oct 28;88:101196. doi: 10.1016/j.plipres.2022.101196] - Bo Yang; Ping-Tao Tseng; Xiang Hu; Bing-Yan Zeng; Jane Pei-Chen Chang; Yang Liu; Wei-Jie Chu; Shuang-Shuang Zhang; Zhi-Liang Zhou; Chih-Sheng Chu; Cheng-Ho Chang; Yu-Kang Tu; et al. (Progress in Lipid Research, 2023)

Online evaluation of catalytic co-pyrolysis of hemicellulose and polypropylene over CaO catalyst - Junjie Weng; Zhanjun Cheng; Yi Zhang; Chao Jiang; Lin Long; Jian Wang; Jianfeng Pan (Fuel, 2023)

Spatial and seasonal variations in the carbon and lead isotopes of PM2.5 in air of residential buildings and their applications for source identification - Chien-Cheng Jung; Yang-Hsueh Chen; Charles C.-K. Chou; Yi-Tang Huang; Kuan-Ting Lin (Environmental Pollution, 2023)

Intelligent films of marine polysaccharides and purple cauliflower extract for food packaging and spoilage monitoring - Han-Lun Huang; I-Lin Tsai; Chi Lin; Yu-Hao Hang; Yi-Cheng Ho; Min-Lang Tsai; Fwu-Long Mi (Carbohydrate Polymers, 2023)

Acinetobacter faecalis Sp. Nov., Isolated from Elephant Faeces - Xue-Mei Chen; De-Feng An; Si-Rong He; Shao-Juan Yang; Zu-Zhen Yang; Lian-Shuang Xiong; Gui-Ding Li; Ming-Guo Jiang; Cheng-Lin Jiang; Yi Jiang (Current Microbiology, 2023)

A symbiosis between Euploea butterflies and yeasts - Wan-Rou Lin; Yi-Ping Chang; Hui-Lin Wu; I-Cheng Hsu; Pi-Han Wang (Symbiosis, 2023)

Prediction of Groundwater Quality Using Seven Types of First-Order Univariate Grey Model in the Chishan Basin, Taiwan - Tzu-Yi Pai; Ray-Shyan Wu; Ching-Ho Chen; Huang-Mu Lo; Terng-Jou Wan; Min-Hsin Liu; Wei-Cheng Chen; Yi-Ping Lin; Chun-Tse Hsu (Water, Air, & Soil Pollution, 2022)

Behavioral and transcriptomic changes in butenolide treated larvae of the cosmopolitan fouling bryozoan Bugulina (Bugula) neritina - Jin-You Liang; Yi-Fan Cheng; Xiao-Lin Huang; Ying Xu; Yue Him Wong; Yu Zhang (Frontiers in Marine Science, 2022)
The arborescent bryozoan Bugulina neritina is a cosmopolitan fouling species in sub-tropical to sub-temperate waters. The butenolide compound 5-octylfuran-2(5H)-one (hereafter named butenolide) reportedly inhibits larval settlement of B. neritina , but its effect on the larval behavioral and transcriptomic responses remained unclear. We report that 10 μg mL -1 or higher concentration of butenolide and/or prolonged treatment (10 h or longer) resulted in significant increase in larval mortality and prominent spiral larval swimming behavior. The transcriptomic analyses not only revealed up-regulation of typical stress-related protein genes in response to 10 mg mL -1 butenolide treatment, but also indicated up-regulation of mucin , synaptic genes and nitric oxide signaling genes. In addition, the expression of developmental genes and lipid biosynthesis genes were also affected. Overall, our larval behavior and transcriptome analyses reflected the impact of butenolide on the metabolism, neuronal and molecular signaling in B. neritina larvae.

Surfactin isoforms isolated from a mushroom derived Bacillus halotolerans DMG-7-2 - Guo-Feng Zhou; Lin Yang; Shu-Hua Zhang; Yi Wang; Yu Yang; Rui Xu; Xue Zhao; Dan Nie; Junjie Shan; Cheng-Bin Cui; Chang-Wei Li (Natural Product Research, 2022)

Predicting Lumbar Vertebral Osteopenia Using LvOPI Scores and Logistic Regression Models in an Exploratory Study of Premenopausal Taiwanese Women - Chun-Wen Chen; Yi-Jui Liu; Shao-Chieh Lin; Chien-Yuan Wang; Wu-Chung Shen; Der-Yang Cho; Tung-Yang Lee; Cheng-Hsuan Juan; Cheng-En Juan; Kai-Yuan Cheng; Chun-Jung Juan (Journal of Medical and Biological Engineering, 2022)
Purpose To propose hybrid predicting models integrating clinical and magnetic resonance imaging (MRI) features to diagnose lumbar vertebral osteopenia (LvOPI) in premenopausal women. Methods This prospective study enrolled 101 Taiwanese women, including 53 before and 48 women after menopause. Clinical information, including age, body height, body weight and body mass index (BMI), were recorded. Bone mineral density (BMD) was measured by the dual-energy X-ray absorptiometry. Lumbar vertebral fat fraction (LvFF) was measured by MRI. LvOPI scores (LvOPISs) comprising different clinical features and LvFF were constructed to diagnose LvOPI. Statistical analyses included normality tests, linear regression analyses, logistic regression analyses, group comparisons, and diagnostic performance. A P value less than 0.05 was considered as statistically significant. Results The post-menopausal women had higher age, body weight, BMI, LvFF and lower BMD than the pre-menopausal women (all P < 0.05). The lumbar vertebral osteoporosis group had significantly higher age, longer MMI, and higher LvFF than the LvOPI group (all P < 0.05) and normal group (all P < 0.005). LvOPISs (AUC, 0.843 to 0.864) outperformed body weight (0.747; P = 0.0566), BMI (0.737; P < 0.05), age (0.649; P < 0.05), and body height (0.5; P < 0.05) in diagnosing LvOPI in the premenopausal women. Hybrid predicting models using logistic regression analysis (0.894 to 0.9) further outperformed all single predictors in diagnosing LvOPI in the premenopausal women ( P < 0.05). Conclusion The diagnostic accuracy of the LvOPI can be improved by using our proposed hybrid predicting models in Taiwanese premenopausal women.

Theranostic Radiolabeled Nanomaterials for Molecular Imaging and potential Immunomodulation Effects - Chao-Cheng Chen; Yang-Hsiang Chan; Syue-Liang Lin; Huihua Kenny Chiang; Yi-Jang Lee; Hui-Yen Chuang (Journal of Medical and Biological Engineering, 2022)

Process Performance and Microbial Communities in Anaerobic Co-digestion of Sewage Sludge and Food Waste with a Lower Range of Carbon/Nitrogen Ratio - Yi Zheng; Pan Wang; Xinyu Yang; Peiru Lin; Yongjing Wang; Mengmeng Cheng; Lianhai Ren (BioEnergy Research, 2022)

Integrated Analyses of miRNome and Transcriptome Reveal the Critical Role of miRNAs Toward Heat Stress Response in Isochrysis galbana - Jia-Yi Cao; Si-Min Xu; Ying-Ying Wang; Xie-Dan Long; Shuo-Nan Ma; Cheng-Xu Zhou; Ji-Lin Xu; Xiao-Jun Yan (Marine Biotechnology, 2022)

A multi-isotope analysis on human and pig tooth enamel from prehistoric Sichuan, China, and its archaeological implications - Kuei-chen Lin; Cheng-Yi Lee; Pei-Ling Wang (Archaeological and Anthropological Sciences, 2022)

Use of piggyBac Transposon System Constructed Murine Breast Cancer Model for Reporter Gene Imaging and Characterization of Metastatic Tumor Cells - Ying-Ling Chen; Yung-Cheng Wang; Kuei-Yuan Hou; Min-Ying Lin; Yu-Chuan Lin; Hui-Yen Chuang; Yi-Jang Lee (Journal of Medical and Biological Engineering, 2022)

Detection of bloom-forming dinoflagellates Karenia mikimotoi and Prorocentrum donghaiense using qPCR assays - Xiao-Kun Hu; Zhuo-Ru Lin; Qing-Chun Zhang; Fan-Zhou Kong; Jing-Yi Cen; Yu-Lan Zeng; Ren-Cheng Yu (Journal of Applied Phycology, 2022)

Estrogen Deficiency Aggravates Fluoride-Induced Liver Damage and Lipid Metabolism Disorder in Rats - Ya-ming Yu; Bian-hua Zhou; Yi-lin Yang; Cheng-Xiang Guo; Jing Zhao; Hong-wei Wang (Biological Trace Element Research, 2022)

Flow-slide characteristics and failure mechanism of shallow landslides in granite residual soil under heavy rainfall - Hui-lin Bai; Wen-kai Feng; Shuang-quan Li; Long-zhen Ye; Zhong-teng Wu; Rui Hu; Hong-chuan Dai; Yun-peng Hu; Xiao-yu Yi; Peng-cheng Deng (Journal of Mountain Science, 2022)

Exploiting Sentinel-1 data and machine learning–based random forest for collectively mapping rice fields in Taiwan - Nguyen-Thanh Son; Chi-Farn Chen; Cheng-Ru Chen; Youg-Sin Cheng; Piero Toscano; Chein-Hui Syu; Horng-Yuh Guo; Shu-Ling Chen; Tsang-Sen Liu; Yi-Ting Zhang; Huan-Sheng Lin; Shih-Hsiang Chen; et al. (Applied Geomatics, 2022)

Cracking and Photo-Oxidation of Polyoxymethylene Degraded in Terrestrial and Simulated Marine Environments - Chih-Cheng Tang; Ying-Ting Chen; Yi-Ming Zhang; Huey-Ing Chen; Peter Brimblecombe; Chon-Lin Lee (Frontiers in Marine Science, 2022)
Marine plastic debris is an environmental problem, and its degradation into microplastics (1-5000 μm) introduces them into the food chain. In this study, small polyoxymethylene (global production ~3000 Tg per year) pellets were exposed in terrestrial and simulated marine environments to heat and light, resulting in cracking during decay with increasing IR absorption (OH-bonds). Furthermore, sunlight over three years reduced pellet mass and diameter (~10% and ~40%), initially yielding 100-300 μm fragments. Changes under UV irradiation were smaller as it could not penetrate into particle interiors. Characteristic spacing of surface striations (100-300 µm) initiated radial cracks to pellet interiors, and breakdown ultimately meant 95% of particles were <300 µm, which are potentially incorporated in marine turbidites.

Identification of PDXDC1 as a novel pleiotropic susceptibility locus shared between lumbar spine bone mineral density and birth weight - Yu-Qian Song; Shi-Di Hu; Xu Lin; Xiang-He Meng; Xiao Wang; Yin-Hua Zhang; Cheng Peng; Rui Gong; Tao Xu; Tong Zhang; Chen-Zhong Li; Dao-Yan Pan; et al. (Journal of Molecular Medicine, 2022)
An increasing number of epidemiological studies have suggested that birth weight (BW) may be a determinant of bone health later in life, although the underlying genetic mechanism remains unclear. Here, we applied a pleiotropic conditional false discovery rate (cFDR) approach to the genome-wide association study (GWAS) summary statistics for lumbar spine bone mineral density (LS BMD) and BW, aiming to identify novel susceptibility variants shared between these two traits. We detected 5 novel potential pleiotropic loci which are located at or near 7 different genes ( NTAN1 , PDXDC1 , CACNA1G , JAG1 , FAT1P1 , CCDC170 , ESR1 ), among which PDXDC1 and FAT1P1 have not previously been linked to these phenotypes. To partially validate the findings, we demonstrated that the expression of PDXDC1 was dramatically reduced in ovariectomized (OVX) mice in comparison with sham-operated (SHAM) mice in both the growth plate and trabecula bone. Furthermore, immunohistochemistry assay with serial sections showed that both osteoclasts and osteoblasts express PDXDC1 , supporting its potential role in bone metabolism. In conclusion, our study provides insights into some shared genetic mechanisms for BMD and BW as well as a novel potential therapeutic target for the prevention of OP in the early stages of the disease development. Key messages We investigated pleiotropy-informed enrichment between LS BMD and BW. We identified genetic variants related to both LS BMD and BW by utilizing a cFDR approach. PDXDC1 is a novel pleiotropic gene which may be related to both LS BMD and BW. Elevated expression of PDXDC1 is related to higher BMD and lower ratio n-6/n-3 PUFA indicating a bone protective effect of PDXDC1.

The significance of riparian communities in the energy flow of subtropical stream ecosystems - Yi-Chang Liao; An-Cheng Lin; Han-Ni Tsai; Yu-Ting Yen; Chyng-Shyan Tzeng; Man-Miao Yang; Hsing-Juh Lin (Aquatic Sciences, 2022)

MoOpy2 is essential for fungal development, pathogenicity, and autophagy in Magnaporthe oryzae - Ying‐Ying Cai; Jing‐Yi Wang; Xi‐Yu Wu; Shuang Liang; Xue‐Ming Zhu; Lin Li; Jian‐Ping Lu; Xiao‐Hong Liu; Fu‐Cheng Lin (Environmental Microbiology, 2022)
Summary The development and pathogenicity of the fungus Magnaporthe oryzae , the causal agent of destructive rice blast disease, require it to perceive external environmental signals. Opy2, an overproduction‐induced pheromone‐resistant protein 2, is a crucial protein for sensing external signals in Saccharomyces cerevisiae . However, the biological functions of the homologue of Opy2 in M. oryzae are unclear. In this study, we identified that MoOPY2 is involved in fungal development, pathogenicity, and autophagy in M. oryzae . Deletion of MoOPY2 resulted in pleiotropic defects in hyphal growth, conidiation, germ tube extension, appressorium formation, appressorium turgor generation, and invasive growth, therefore leading to attenuated pathogenicity. Furthermore, MoOpy2 participates in the Osm1 MAPK pathway and the Mps1 MAPK pathway by interacting with the adaptor protein Mst50. The interaction sites of Mst50 and MoOpy2 colocalized with the autophagic marker protein MoAtg8 in the preautophagosomal structure sites (PAS). Notably, the Δ Moopy2 mutant caused cumulative MoAtg8 lipidation and rapid GFP‐MoAtg8 degradation in response to nitrogen starvation, showing that MoOpy2 is involved in the negative regulation of autophagy activity. Taken together, our study revealed that MoOpy2 of M. oryzae plays an essential role in the orchestration of fungal development, appressorium penetration, autophagy and pathogenesis.

L-Theanine Ameliorated Rotenone-Induced Parkinsonism-like Symptoms in Rats - Cheng-Neng Chen; Mao-Hsien Wang; Hung-Sheng Soung; Shu-Mei Chen; Chih-Hsiang Fang; Yi-Wen Lin; Hsiang-Chien Tseng (Neurotoxicity Research, 2022)

Common Subtype of Small Renal Mass MR Imaging Characterisation: A Medical Center Experience in Taiwan - Ming-Cheng Liu; Yi-Jui Liu; Yen-Ting Lin; Siu-Wan Hung; Jyh-Wen Chai; Si-Wa Chan; Kun-Yuan Chiu; Ya-Ling Tsou (Journal of Medical and Biological Engineering, 2022)
Purpose Many studies have shown that multiparametric magnetic resonance imaging (MRI) may be helpful for differentiating malignant renal cell carcinomas (RCCs) from benign lesions. However, the key imaging characteristics that differ between malignant and benign tumors still require further discussion. Methods We analyzed 60 adult patients diagnosed with 72 small renal masses (SRMs) who received preoperative MRI from 2014 to 2019 at a hospital in Taiwan. The MRI features included conventional MRI parameters, diffusion-weighted imaging (DWI) data, and dynamic contrast-enhanced (DCE) patterns, which were documented and compared among the four common subtypes: clear cell RCC (ccRCC), papillary RCC (pRCC), angiomyolipoma (AML) and other types of RCC. The apparent diffusion coefficient (ADC) values of high- and low-grade RCCs were also analyzed. Results The results show that ccRCC had higher T2-weighted signal intensity than the other three subgroups, a higher arterial wash-in index (AWI) and ADC value than AML and pRCC, and manifested a plateau ( n = 9, 25%) or washout (n = 27, 75%) enhancement pattern. AMLs exhibited more intravoxel fat than the other three subtype groups, and half of the AMLs (6 in 12) contained bulk fat. pRCC demonstrated a more progressive (n = 3, 60%) enhancement pattern than the other three subgroups. The ADC value of high-grade RCCs was significantly lower than that of low-grade RCCs. Conclusion These findings may indicate that multiparametric MRI is useful in differentiating among four common pathological types of SRMs, and the ADC value may be helpful in evaluating the histological grade of malignancy.

Dissipation and residue of fosthiazate in tomato and cherry tomato and a risk assessment of dietary intake - Sukun Lin; Yi Zhou; Jiyingzi Wu; Zhixiang Zhang; Dongmei Cheng (Environmental Science and Pollution Research, 2022)

miRNA–mRNA Integrative Analysis Reveals the Roles of miRNAs in Hypoxia-Altered Embryonic Development- and Sex Determination-Related Genes of Medaka Fish - Keng Po Lai; Nathan Yi Kan Tam; Yuelong Chen; Chi Tim Leung; Xiao Lin; Chau Fong Tsang; Yin Cheung Kwok; William Ka Fai Tse; Shuk Han Cheng; Ting Fung Chan; Richard Yuen Chong Kong (Frontiers in Marine Science, 2022)
Recent studies have shown hypoxia to be an endocrine disruptor that impairs sex differentiation and reproductive function, leading to male-biased F1 populations in fish. However, the molecular mechanisms through which hypoxia alters fish sex differentiation and therefore sex ratios remain poorly understood. In order to understand the potential role of miRNAs in mediating hypoxia-altered sex determination and differentiation in fish, we conducted small RNA sequencing and transcriptome sequencing on marine medaka ( Oryzias melastigma ) embryos that were exposed to hypoxia (2.0 ± 0.2 mg O 2 L – 1) for 40 h (encompassing a critical window of sex determination). We identified dysregulated miRNAs and mRNAs in the hypoxia-exposed embryo, and bioinformatic analysis of the integrative small RNA sequencing and transcriptome sequencing results revealed hypoxia to cause alterations of genes related to embryonic development through miRNA regulation. Importantly, we have identified miRNA-mRNA pairs that were reported to play roles in gonad development (novel miR-145-col9a3 and novel miRNA-94- arid5b), in sex hormone response (novel miRNA-210-ca2, novel miRNA-106-nr2f2, nbr-miR-29c-nr4a1, and ola-miR-92b-akr1d1), and in sex characteristic development (novel miRNA-145-mns1, nle-miR-20-sord, and ipu-miR-219b-abcc8). Our findings highlighted the possible roles of miRNA–mRNA in regulation of embryonic development and sex determination in response to hypoxic stress.

Distribution of Coomassie Blue Stainable Particles in the Pearl River Estuary, China, Insight Into the Nitrogen Cycling in Estuarine System - Cui-Ci Sun; Wei-Zhong Yue; You-Shao Wang; Wei-Hong He; Yi-Guo Hong; Fu-Lin Sun; Hao Cheng; Mei-Lin Wu; Zhao-Yu Jiang; Fei Jiao; Yu-Tu Wang (Frontiers in Marine Science, 2022)
Distributions of Coomassie Blue stainable particles (CSP), the sources and transports, as well as their implications for nitrogen biogeochemical cycles in the Pearl River estuary (PRE) were investigated during two cruises in August 2016 and January 2017. CSP color concentrations (CSP concentration determined spectrophotometrically) were 73.7–685.3 μg BSA eq L –1 [μg Bovine serum albumin (BSA) equivalent liter –1 ] in August 2016 and 100.6–396.4 μg BSA eq L –1 in January 2017, respectively. CSP concentrations were high in low-salinity waters (<5), and declined from the river to the middle estuary by 80% in the wet season and 55.6% in the dry season, respectively, then increased again in the lower estuary due to high primary production. CSP concentrations were mainly associated with chlorophyll a (Chl a ) concentration except for the turbid mixing zone, suggesting that autochthonous phytoplankton production served as the primary source of CSP in the PRE. The concentrations of nitrogen (N) as CSP in the PRE were comparable to the nitrogen content of particulate hydrolysable amino acids (PHAA). Pictures of CSP taken by microscopy and the correlation between composition of PHAA and the ratio of Chl a /CSP color showed that CSP were relatively degraded due to delivery of old terrestrial protein to river section and extensive microbial degradation during mixing at the upper and middle parts of the estuary, whereas CSP in lower estuary appeared to be more labile due to higher fresh algal production. The contribution of CSP nitrogen (CSP-N) to the particulate nitrogen (PN) pool was 34.98% in summer and 30.8% in winter. The conservative estimate of CSP-N input flux in the Pearl River Delta was about 6 × 10 6 mol N d –1 . These results suggested that CSP was a significant pool of organic nitrogen in the PRE. The study of CSP composition in terms of nitrogen provides new insight into the roles of CSP on nitrogen biogeochemical processes in the turbid and productive estuarine system.

Nakamurella leprariae sp. nov., isolated from a lichen sample - De-Feng An; Shao-Juan Yang; Long-Qian Jiang; Xin-Yu Wang; Xiao-Yu Huang; Lei Lang; Xue-Mei Chen; Ming-Qun Fan; Gui-Ding Li; Ming-Guo Jiang; Li-Song Wang; Cheng-Lin Jiang; et al. (Archives of Microbiology, 2022)

Does the smart city policy promote the green growth of the urban economy? Evidence from China - Yu Qian; Jun Liu; Zhonghua Cheng; Jeffrey Yi-Lin Forrest (Environmental Science and Pollution Research, 2021)

The r-X1 deletion induces terminal deficiencies in the maize B chromosome - Yen-Hua Huang; Tzu-Che Lin; Wan-Yi Chiou; Ya-Ming Cheng (Chromosome Research, 2021)

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

Paternal exposure to microcystin-LR induces fetal growth restriction partially through inhibiting cell proliferation and vascular development in placental labyrinth - Lan Gao; An-Qi Cui; Jing Wang; Jing Chen; Xiao-Yi Zhang; Zhi-Jing Lin; Yuan-Hua Chen; Cheng Zhang; Hua Wang; De-Xiang Xu (Environmental Science and Pollution Research, 2021)

Effects of Fatigue on Inter-joint Coordination in Ballet Dancers During a Ballet Jumping Movement (petit échappé sauté) - Chai-Wei Lin; Jeng-Feng Yang; Yi-An Chen; Cheng-Feng Lin (Journal of Medical and Biological Engineering, 2021)

Experimental study on integrated and autonomous conductivity-temperature-depth (CTD) sensor applied for underwater glider - Bin Lv; Hai-lin Liu; Yi-fan Hu; Cheng-xuan Wu; Jie Liu; Hai-jing He; Jie Chen; Jian Yuan; Zhao-wen Zhang; Lin Cao; Hui Li (Marine Georesources & Geotechnology, 2021)

Applying Artificial Intelligence (AI) Techniques to Implement a Practical Smart Cage Aquaculture Management System - Chung-Cheng Chang; Jung-Hua Wang; Jenq-Lang Wu; Yi-Zeng Hsieh; Tzong-Dar Wu; Shyi-Chy Cheng; Chin-Chun Chang; Jih-Gau Juang; Chyng-Hwa Liou; Te-Hua Hsu; Yii-Shing Huang; Cheng-Ting Huang; et al. (Journal of Medical and Biological Engineering, 2021)
Purpose This paper presents our team’s results to establish an AIoT smart cage culture management system. Methods According to the built system, the farmed field information is transmitted to the data platform of Ocean Cloud, and all collected data and analysis results can be applied to the cage culture field after the bigdata analysis. Results This management system successfully integrates AI and IoT technologies and is applied in cage culture. Using underwater biological analysis images and AI feeding as examples, this paper explains how the system integrates AI and IoT into a feasible framework that can constantly acquire information about the health status of fish, survival rate of fish, as well as the feed residuals. Conclusion The results of our research enable the aquaculture operators or owners to efficiently reduce the feed residual, monitor the growth of fish, and increase fish survival rate, thereby increasing the feed conversion rate.

Viable and Heat-Killed Probiotic Strains Improve Oral Immunity by Elevating the IgA Concentration in the Oral Mucosa - Wen-Yang Lin; Yi-Wei Kuo; Ching-Wei Chen; Yu-Fen Huang; Chen-Hung Hsu; Jia-Hung Lin; Cheng-Ruei Liu; Jui-Fen Chen; Ko-Chiang Hsia; Hsieh-Hsun Ho (Current Microbiology, 2021)
Oral-nasal mucosal immunity plays a crucial role in protecting the body against bacterial and viral invasion. Safe probiotic products have been used to enhance human immunity and oral health. In this study, we verified the beneficial effects of mixed viable probiotic tablets, consisting of Lactobacillus salivarius subsp. salicinius AP-32, Bifidobacterium animalis subsp. lactis CP-9, and Lactobacillus paracasei ET-66, and heat-killed probiotic tablets, consisting of L. salivarius subsp. salicinius AP-32 and L. paracasei ET-66, on oral immunity among 45 healthy participants. Participants were randomly divided into viable probiotic, heat-killed probiotic, and placebo groups. The administration of treatment lasted for 4 weeks. Saliva samples were collected at Weeks 0, 2, 4, and 6, and Lactobacillus , Bifidobacterium and Streptococcus mutans populations and IgA concentration were measured. IgA concentrations, levels of TGF-beta and IL-10 in PBMCs cells were quantified by ELISA method. Results showed that salivary IgA levels were significantly increased on administration of both the viable (119.30 ± 12.63%, *** P < 0.001) and heat-killed (116.78 ± 12.28%, *** P < 0.001) probiotics for 4 weeks. Among three probiotic strains, AP-32 would effectively increase the levels of TGF-beta and IL-10 in PBMCs. The oral pathogen Streptococcus mutans was significantly reduced on viable probiotic tablet administration (49.60 ± 31.01%, *** P < 0.001). The in vitro antibacterial test confirmed that viable probiotics effectively limited the survival rate of oral pathogens. Thus, this clinical pilot study demonstrated that oral probiotic tablets both in viable form or heat-killed form could exert beneficial effects on oral immunity via IL-10, TGB-beta mediated IgA secretion. The effective dosage of viable probiotic content in the oral tablet was 10 9 CFUs/g and the heat-killed oral tablet was 1 × 10 10 cells/g.

Proteomics provides individualized options of precision medicine for patients with gastric cancer - Wenwen Huang; Dongdong Zhan; Yazhuo Li; Nairen Zheng; Xin Wei; Bin Bai; Kecheng Zhang; Mingwei Liu; Xuefei Zhao; Xiaotian Ni; Xia Xia; Jinwen Shi; et al. (Science China Life Sciences, 2021)

The major photoprotective role of anthocyanins in leaves of Arabidopsis thaliana under long-term high light treatment: antioxidant or light attenuator? - Xiao-Ting Zheng; Zheng-Chao Yu; Jun-Wei Tang; Min-Ling Cai; Yi-Lin Chen; Cheng-Wei Yang; Wah Soon Chow; Chang-Lian Peng (Photosynthesis Research, 2021)

Aestuariibaculum sediminum sp. nov., a marine bacterium isolated from a tidal flat in Zhoushan - Zhi-Cheng Wu; Xin-Yin Zhang; Cong Sun; Lin Xu; Ge-Yi Fu; Xue-Wei Xu (Archives of Microbiology, 2021)

Glaciibacter flavus sp. nov., isolated from a lichen sample - De-Feng An; Long-Qian Jiang; Kun Zhang; Gui-Ding Li; Xin-Yu Wang; Ming-Guo Jiang; Lei Lang; Li-Song Wang; Johannes F. Imhoff; Cheng-Lin Jiang; Yi Jiang (Archives of Microbiology, 2021)

Detection of Vestibular Schwannoma on Triple-parametric Magnetic Resonance Images Using Convolutional Neural Networks - Tzu-Hsuan Huang; Wei-Kai Lee; Chih-Chun Wu; Cheng-Chia Lee; Chia-Feng Lu; Huai-Che Yang; Chun-Yi Lin; Wen-Yuh Chung; Po-Shan Wang; Yen-Ling Chen; Hsiu-Mei Wu; Wan-You Guo; et al. (Journal of Medical and Biological Engineering, 2021)
Purpose The first step in typical treatment of vestibular schwannoma (VS) is to localize the tumor region, which is time-consuming and subjective because it relies on repeatedly reviewing different parametric magnetic resonance (MR) images. A reliable, automatic VS detection method can streamline the process. Methods A convolutional neural network architecture, namely YOLO-v2 with a residual network as a backbone, was used to detect VS tumors from MR images. To heighten performance, T1-weighted–contrast-enhanced, T2-weighted, and T1-weighted images were combined into triple-channel images for feature learning. The triple-channel images were cropped into three sizes to serve as input images of YOLO-v2. The VS detection effectiveness levels were evaluated for two backbone residual networks that downsampled the inputs by 16 and 32. Results The results demonstrated the VS detection capability of YOLO-v2 with a residual network as a backbone model. The average precision was 0.7953 for a model with 416 × 416-pixel input images and 16 instances of downsampling, when both the thresholds of confidence score and intersection-over-union were set to 0.5. In addition, under an appropriate threshold of confidence score, a high average precision, namely 0.8171, was attained by using a model with 448 × 448-pixel input images and 16 instances of downsampling. Conclusion We demonstrated successful VS tumor detection by using a YOLO-v2 with a residual network as a backbone model on resized triple-parametric MR images. The results indicated the influence of image size, downsampling strategy, and confidence score threshold on VS tumor detection.

First report of cucurbit chlorotic yellows virus infecting melon, watermelon and wild melon in the Philippines - Hsin-Yi Chang; Li-Cheng Chen; Chung-Cheng Lin; Wen-Shi Tsai (Journal of Plant Pathology, 2021)

Microbiological profiles and antimicrobial resistance patterns of pediatric bloodstream pathogens in China, 2016–2018 - Yue Qiu; Junwen Yang; Yiping Chen; Jinhong Yang; Qingxiong Zhu; Chunhui Zhu; Shuangjie Li; Jing Liu; Chaomin Wan; Yu Zhu; Minxia Chen; Yi Xu; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Crenobacter intestini sp. nov., Isolated from the Intestinal Tract of Konosirus punctatus - Song-Biao Shi; Jia-Fa Wu; Li-Fang Yang; Ming-Guo Jiang; Cai-Mi Gao; Cheng-Lin Jiang; Yi Jiang (Current Microbiology, 2021)

Effects of degradation succession of alpine wetland on soil organic carbon and total nitrogen in the Yellow River source zone, west China - Chun-ying Lin; Xi-lai Li; Jing Zhang; Hua-fang Sun; Juan Zhang; Hui-bang Han; Qi-hua Wang; Cheng-biao Ma; Cheng-yi Li; Yu-xing Zhang; Xue-qian Ma (Journal of Mountain Science, 2021)

Small RNA Sequencing Analysis of Germinating Single-bud Seedcane Sett in Sugarcane - Kai-Chao Wu; Lin Xu; Zhi-Nian Deng; Tian Pang; Rong-Hua Zhang; Yi-Jie Li; Xiao-Yan Liu; Cheng-Feng Huang; Wen-Xian Qin; Jian-Feng Wei; Li-Ping Wei; Yang-Rui Li; et al. (Sugar Tech, 2021)

Assisted selection of eating quality progeny of indica (O. sativa L. ssp. indica) and japonica (O. sativa L. ssp. japonica) hybrids using rice starch properties - Ting Mao; Zhan Zhang; Shan Jun Ni; Yi Zhou Zhao; Xin Li; Li Li Zhang; Yan Liu; Cheng Shun Zhong; He Huang; Shao Lin Wang; Xu Li (Genetic Resources and Crop Evolution, 2021)

Paracoccus lichenicola sp. nov., Isolated from Lichen - Lei Lang; De-Feng An; Long-Qian Jiang; Gui-Ding Li; Li-Song Wang; Xin-Yu Wang; Qin-Yuan Li; Cheng-Lin Jiang; Yi Jiang (Current Microbiology, 2021)

Rapid assessment of landslide risk level based on deep learning - Fei Tan; Jin Yu; Yu-Yong Jiao; Dawei Lin; Jiahe Lv; Yi Cheng (Arabian Journal of Geosciences, 2021)

Improving the observation and prediction capabilities for Arctic marine environment: from the perspective of Arctic Shipping - Hui Wang; Qizhen Sun; Lin Zhang; Xi Liang; Qinghua Yang; Na Liu; Chunhua Li; Qingsheng Liu; Bingrui Li; Qian Feng; Xiao Cheng; Yi Yu (Acta Oceanologica Sinica, 2021)

Concurrent increases in post-pacing action potential duration and contractility predict occurrence of ventricular arrhythmia - Chih-Min Liu; Feng-Zhi Lin; Yao-Chang Chen; Yung-Kuo Lin; Yen-Yu Lu; Cheng-I Wu; Satoshi Higa; Shih-Ann Chen; Yi-Jen Chen (Pflügers Archiv - European Journal of Physiology, 2020)

Melatonin ameliorates spatial memory and motor deficits via preserving the integrity of cortical and hippocampal dendritic spine morphology in mice with neurotrauma - Xiao-Jing Lin; Ruoxu Liu; Chenyi Li; Xueqing Yi; Bo Fu; M. J. Walker; Xiao-Ming Xu; Gang Sun; Cheng-Hsien Lin (Inflammopharmacology, 2020)

Structural insights into Arabidopsis ethylene response factor 96 with an extended N-terminal binding to GCC box - Chun-Yen Chen; Pei-Hsuan Lin; Kun-Hung Chen; Yi-Sheng Cheng (Plant Molecular Biology, 2020)
The phytohormone ethylene is widely involved in many developmental processes and is a crucial regulator of defense responses against biotic and abiotic stresses in plants. Ethylene-responsive element binding protein, a member of the APETALA2/ethylene response factor (AP2/ERF) superfamily, is a transcription factor that regulates stress-responsive genes by recognizing a specific cis -acting element of target DNA. A previous study showed only the NMR structure of the AP2/ERF domain of AtERF100 in complex with a GCC box DNA motif. In this report, we determined the crystal structure of AtERF96 in complex with a GCC box at atomic resolution. We analyzed the binding residues of the conserved AP2/ERF domain in the DNA recognition sequence. In addition to the AP2/ERF domain, an N-terminal α-helix of AtERF96 participates in DNA interaction in the flanking region. We also demonstrated the structure of AtERF96 EDLL motif, a unique conserved motif in the group IX of AP2/ERF family, might involve in the transactivation of defense-related genes. Our study establishes the structural basis of the AtERF96 transcription factor in complex with the GCC box, as well as the DNA binding mechanisms of the N-terminal α-helix and AP2/ERF domain.

One-pot synthesis of substituted pyrrole–imidazole derivatives with anticancer activity - Ming Zhang; Yong Ding; Hong-Xia Qin; Zhi-Gang Xu; Hai-Tao Lan; Dong-Lin Yang; Cheng Yi (Molecular Diversity, 2020)

Correction to: Complete genome sequences of two novel dicistroviruses detected in yellow crazy ants (Anoplolepis gracilipes) - Chih-Chi Lee; Chun-Yi Lin; Hung-Wei Hsu; Chin-Cheng Scotty Yang (Archives of Virology, 2020)

Complete genome sequences of two novel dicistroviruses detected in yellow crazy ants (Anoplolepis gracilipes) - Chih-Chi Lee; Chun-Yi Lin; Hung-Wei Hsu; Chin-Cheng Scotty Yang (Archives of Virology, 2020)

Upregulation of miR-133a-3p in the Sciatic Nerve Contributes to Neuropathic Pain Development - Lin-Li Chang; Hung-Chen Wang; Kuang-Yi Tseng; Miao-Pei Su; Jaw-Yuan Wang; Yi-Ta Chuang; Yi-Hsuan Wang; Kuang-I Cheng (Molecular Neurobiology, 2020)

Potential probiotic of Lactobacillus strains isolated from the intestinal tracts of pigs and feces of dogs with antibacterial activity against multidrug-resistant pathogenic bacteria - Chuen-Fu Lin; Meng-Yi Lin; Chao-Nan Lin; Ming-Tang Chiou; Jia-Wen Chen; Kai-Chieh Yang; Ming-Cheng Wu (Archives of Microbiology, 2020)

The Health Promoting Mindfulness or Qigong Educational Programs for Beneficial Lifestyle Changes of Cancer Survivors - Tse-Chou Cheng; Yi-Hua Lee; Chun-Lin Mar; Wen-Tsung Huang; Yuan-Ping Chang (Journal of Cancer Education, 2020)

Nakamurella albus sp. nov.: A Novel Actinobacterium Isolated from a Lichen Sample - Long-Qian Jiang; De-Feng An; Kun Zhang; Gui-Ding Li; Xin-Yu Wang; Lei Lang; Ming-Guo Jiang; Li-Song Wang; Cheng-Lin Jiang; Yi Jiang (Current Microbiology, 2020)

Reconnaissance and learning after the February 6, 2018, earthquake in Hualien, Taiwan - Jui-Liang Lin; Chun-Hsiang Kuo; Yu-Wen Chang; Shu-Hsien Chao; Yi-An Li; Wen-Cheng Shen; Chung-Han Yu; Cho-Yen Yang; Fan-Ru Lin; Hsiao-Hui Hung; Chun-Chung Chen; Chin-Kuo Su; et al. (Bulletin of Earthquake Engineering, 2020)

Relationship Between Seismic Moment and Source Duration for Seismogenic Earthquakes in Taiwan: Implications for the Product of Static Stress Drop and the Cube of Rupture Velocity - Ruey-Der Hwang; Cheng-Ying Ho; Tzu-Wei Lin; Wen-Yen Chang; Yi-Ling Huang; Cai-Yi Lin; Chiung-Yao Lin (Pure and Applied Geophysics, 2020)

Metabolomics analysis of nitrogen-containing metabolites between two Dendrobium plants - Cheng Song; Chunyan Jiao; Qing Jin; Cunwu Chen; Yongping Cai; Yi Lin (Physiology and Molecular Biology of Plants, 2020)

Toxicity assessment of electrochemical advanced oxidation process-treated groundwater from a gas station with petrochemical contamination - How-Ran Chao; Danielle E. Que; Alisha C. Aquino; Yan-You Gou; Lemmuel L. Tayo; Yi-Hsien Lin; Ming-Hsien Tsai; Fu-Lin Hsu; I-Cheng Lu; Sheng-Lun Lin; Natwat Srikhao; Cherng-Gueih Shy; et al. (Environmental Monitoring and Assessment, 2020)

Population Genetic Analysis for Stock Enhancement of Silver Sea Bream (Rhabdosargus sarba) in Taiwan - Te-Hua Hsu; Chang-Wen Huang; Hung-Tai Lee; Yi-Hsuan Kuo; Kwang-Ming Liu; Cheng-Hui Lin; Hong-Yi Gong (Fishes, 2020)
Stock enhancement is a method for replenishing depleted wild finfish populations by supplementing them with hatchery-raised fish. In Taiwan, silver sea bream (Rhabdosargus sarba) is a predominant commercial species involved in stock enhancement projects. Although management agencies conduct stock enhancement projects, there are a lot of private releases without records. Stock enhancement is performed by the private aquaculture sector without accurate genetic records, potentially leading to unintended consequences for wild populations. We analyzed the genetics of 459 wild and 701 hatchery-reared specimens from nine batches produced by various hatcheries. Wild and hatchery-reared samples could be considered two separate clades by using a set of stable and informative microsatellite markers including type I (from gene introns and 3′UTR) and type II markers (randomly picked up from genome). Type I microsatellite markers could more sensitively reflect the loss of genetic diversity more than type II markers in the domestication process. All specimens were considered native by using mtDNA COI and microsatellites. The genetic composition of the wild population is relatively simple, and the estimated low contribution rate of the hatchery stock (1.3–10.9%; 6–50/459) indicated a weak but significant genetic effect of stock enhancement. Therefore, establishing standards for the stock enhancement of silver sea bream for more effective supplementation of wild populations is imperative.

Outflow sediment concentration forecasting by integrating machine learning approaches and time series analysis in reservoir desilting operation - Ming-Jui Chang; Gwo-Fong Lin; Fong-Zuo Lee; Yi-Cheng Wang; Peng-An Chen; Ming-Chang Wu; Jihn-Sung Lai (Stochastic Environmental Research and Risk Assessment, 2020)

Hispidulin Inhibits Neuroinflammation in Lipopolysaccharide-Activated BV2 Microglia and Attenuates the Activation of Akt, NF-κB, and STAT3 Pathway - Chung-I Yu; Cheng-I Cheng; Ya-Fei Kang; Po-Chih Chang; In-Pin Lin; Yu-His Kuo; An-Jie Jhou; Mei-Ying Lin; Chung-Yi Chen; Chien-Hsing Lee (Neurotoxicity Research, 2020)

Reversal of Social Recognition Deficit in Adult Mice with MECP2 Duplication via Normalization of MeCP2 in the Medial Prefrontal Cortex - Bin Yu; Bo Yuan; Jian-Kun Dai; Tian-lin Cheng; Sheng-Nan Xia; Ling-Jie He; Yi-Ting Yuan; Yue-Fang Zhang; Hua-Tai Xu; Fu-Qiang Xu; Zhi-Feng Liang; Zi-Long Qiu (Neuroscience Bulletin, 2020)

Cognitive Load of Exercise Influences Cognition and Neuroplasticity of Healthy Elderly: An Exploratory Investigation - Yi-Ping Chao; Changwei W. Wu; Li-Jung Lin; Cheng-Hung Lai; Hong-Yi Wu; Ai-Ling Hsu; Chiao-Nan Chen (Journal of Medical and Biological Engineering, 2020)
This study explored the effects of exercise with either high cognitive load or low cognitive load on cognitive performance and neuroplasticity in healthy elderly. Twenty-eight sedentary community-dwelling seniors participated in this study. Participants were assigned to one of three groups: the control group (C), low-cognitive load exercise group (LE), or high-cognitive load exercise group (HE). Individuals in both exercise groups engaged in moderate-intensity aerobic exercise for 4 months. Resting-state functional MRI and diffusion MRI were used to investigate the effects of intervention on functional and structural connectivity, respectively. Analysis of covariance with baseline, age and the education year as covariates was used to determine the effects of intervention. We found 4 months of exercise with high-cognitive load, but not exercise with low-cognitive load, improved the overall cognitive function of healthy elderly. Additionally, the HE group showed increased resting-state functional connectivity of superior frontal gyrus and anterior cingulate cortex and decreased functional connectivity of middle occipital gyrus and postcentral gyrus. The age-related alterations in local efficiency and betweenness were protected by exercise. Our findings might suggest that exercise with greater cognitive load likely results in greater training effects on cognition and brain connectivity than exercise requiring lower cognitive loads for healthy elderly.

Statistical Analysis on Heart Rate Variability for Graded Cardiopulmonary Groups with Different Exercise Intensities - Ching-Kun Chen; Shyan-Lung Lin; Cheng-Yi Huang; Tasi-Chu Wang; Ting-Yen Yao; Chieh-Liang Wu (Journal of Medical and Biological Engineering, 2020)

Short-term associations between ambient fine particulate matter pollution and hospital visits for chronic obstructive pulmonary disease in Yinzhou District, China - Cheng-yi Lin; Die Li; Jie-ming Lu; Zhe-bin Yu; Yao Zhu; Peng Shen; Meng-ling Tang; Ming-juan Jin; Hong-bo Lin; Li-ming Shui; Kun Chen; Jian-bing Wang (Environmental Science and Pollution Research, 2020)

Effects of Hyperbaric Oxygen Therapy on Acute Myocardial Infarction Following Carbon Monoxide Poisoning - Chien-Cheng Huang; Chung-Han Ho; Yi-Chen Chen; Chien-Chin Hsu; Hung-Jung Lin; Jhi-Joung Wang; Shih-Bin Su; How-Ran Guo (Cardiovascular Toxicology, 2020)

Anti-phytopathogenic Bacterial Metabolites From the Seaweed-Derived Fungus Aspergillus sp. D40 - Rui-Huan Huang; Wei Lin; Peng Zhang; Jian-Yang Liu; Dan Wang; Yi-Qiang Li; Xiao-Qiang Wang; Cheng-Sheng Zhang; Wei Li; Dong-Lin Zhao (Frontiers in Marine Science, 2020)

Multiple genetic factors affecting the pharmacokinetic and pharmacodynamic processes of tacrolimus in Chinese myasthenia gravis patients - Huan-Yu Meng; Xi Li; Wan-Lin Jin; Cheng-Kai Yan; Xiao-Hua Dong; Qiu Xu; Yu-Yao Peng; Zhi-Bin Li; Yi Li; Zhao-Hui Luo; Li-Qun Xu; Huan Yang (European Journal of Clinical Pharmacology, 2020)

Protective Effect of (−)Epigallocatechin-3-gallate on Rotenone-Induced Parkinsonism-like Symptoms in Rats - Hsiang-Chien Tseng; Mao-Hsien Wang; Kuo-Chi Chang; Hung-Sheng Soung; Chih-Hsiang Fang; Yi-Wen Lin; Keng-Yuan Li; Chih-Chuan Yang; Cheng-Chia Tsai (Neurotoxicity Research, 2020)

Exploration of expression activity of subgenomic RNA promoter of coat protein gene from Odontoglossum ringspot virus - Cheng-Ku Lin; Pung-Ling Huang; Yi-Yin Do (Journal of Plant Biochemistry and Biotechnology, 2020)

MicroRNA-mediated responses to colchicine treatment in barley - Fang-Yao Sun; Lin Liu; Yi Yu; Xin-Ming Ruan; Cheng-Yu Wang; Qun-Wen Hu; De-Xiang Wu; Genlou Sun (Planta, 2020)

Aureimonas leprariae sp. nov., Isolated from a Lepraria sp. Lichen - Kun Zhang; Long-Qian Jiang; Li-Song Wang; De-Feng An; Lei Lang; Gui-Ding Li; Xin-Yu Wang; Song-Biao Shi; Qin-Yuan Li; Cheng-Lin Jiang; Yi Jiang (Current Microbiology, 2020)

Rubellimicrobium rubrum sp. nov., a novel bright reddish bacterium isolated from a lichen sample - Long-Qian Jiang; Kun Zhang; Gui-Ding Li; Xin-Yu Wang; Song-Biao Shi; Qin-Yuan Li; De-Feng An; Lei Lang; Li-Song Wang; Cheng-Lin Jiang; Yi Jiang (Antonie van Leeuwenhoek, 2019)

Implementation of the Land Surface Processes into a Vector Vorticity Equation Model (VVM) to Study its Impact on Afternoon Thunderstorms over Complex Topography in Taiwan - Chien-Ming Wu; Hsiao-Chun Lin; Fang-Yi Cheng; Mu-Hua Chien (Asia-Pacific Journal of Atmospheric Sciences, 2019)

Aflatoxin B1 enhances pyroptosis of hepatocytes and activation of Kupffer cells to promote liver inflammatory injury via dephosphorylation of cyclooxygenase-2: an in vitro, ex vivo and in vivo study - Li-Yin Zhang; Deng-Lin Zhan; Yuan-Yuan Chen; Wei-Hua Wang; Cheng-Yong He; Yi Lin; Yu-Chun Lin; Zhong-Ning Lin (Archives of Toxicology, 2019)

Ottowia flava sp. nov., isolated from fish intestines - Song-Biao Shi; Gui-Ding Li; Li-Fang Yang; Cong Liu; Ming-Guo Jiang; Qin-Yuan Li; Jia-Fa Wu; Kun Zhang; Long-Qian Jiang; Nai-Kun Shen; Cheng-Lin Jiang; Yi Jiang (Antonie van Leeuwenhoek, 2019)

Self-rooted grafting influences the growth and cadmium accumulation characteristics in the post generation of Cosmos sulphureus - Jin Wang; Yumei Tan; Ming’an Liao; Lijin Lin; Yi Tang; Huifen Zhang; Hui Xia; Dong Liang; Qunxian Deng; Xiulan Lv; Cheng Chen; Wei Ren (Environmental Science and Pollution Research, 2019)

The Ribosomal Protein RPLP0 Mediates PLAAT4-induced Cell Cycle Arrest and Cell Apoptosis - Chun-Hua Wang; Lu-Kai Wang; Chang-Chieh Wu; Mao-Liang Chen; Ming-Cheng Lee; Yi-Ying Lin; Fu-Ming Tsai (Cell Biochemistry and Biophysics, 2019)

Preparation of AgCl/TNTs nanocomposites for organic dyes and inorganic heavy metal removal - Cheng-Yen Tsai; Chen-Wuing Liu; Hsing-Cheng Hsi; Kuen-Song Lin; Yi-Wen Lin; Li-Chi Lai; Tsung-Nan Weng (Environmental Science and Pollution Research, 2019)

Integration of Food Animal Residue Avoidance Databank (FARAD) empirical methods for drug withdrawal interval determination with a mechanistic population-based interactive physiologically based pharmacokinetic (iPBPK) modeling platform: example for flunixin meglumine administration - Miao Li; Yi-Hsien Cheng; Jason T. Chittenden; Ronald E. Baynes; Lisa A. Tell; Jennifer L. Davis; Thomas W. Vickroy; Jim E. Riviere; Zhoumeng Lin (Archives of Toxicology, 2019)

PARK14 (D331Y) PLA2G6 Causes Early-Onset Degeneration of Substantia Nigra Dopaminergic Neurons by Inducing Mitochondrial Dysfunction, ER Stress, Mitophagy Impairment and Transcriptional Dysregulation in a Knockin Mouse Model - Ching-Chi Chiu; Chin-Song Lu; Yi-Hsin Weng; Ying-Ling Chen; Ying-Zu Huang; Rou-Shayn Chen; Yi-Chuan Cheng; Yin-Cheng Huang; Yu-Chuan Liu; Szu-Chia Lai; Kun-Jun Lin; Yan-Wei Lin; et al. (Molecular Neurobiology, 2019)

Cutting after grafting affects the growth and cadmium accumulation of Nasturtium officinale - Xingyu Zhang; Fenqin Zhang; Jin Wang; Lijin Lin; Ming’an Liao; Yi Tang; Guochao Sun; Xun Wang; Xiulan Lv; Qunxian Deng; Cheng Chen; Wei Ren (Environmental Science and Pollution Research, 2019)

A novel SGNH family hydrolase Ali5 with thioesterase activity and a GNSL motif but without a classic GDSL motif from Altererythrobacter ishigakiensis - Li-Guo Hong; Shu-Ling Jian; Ying-Yi Huo; Hong Cheng; Xiao-Jian Hu; Jixi Li; Heng-Lin Cui; Xue-Wei Xu (Biotechnology Letters, 2019)

Family-1 UDP glycosyltransferases in pear (Pyrus bretschneideri): Molecular identification, phylogenomic characterization and expression profiling during stone cell formation - Xi Cheng; Abdullah Muhammad; Guohui Li; Jingyun Zhang; Jun Cheng; Jingxiang Qiu; Taoshan Jiang; Qing Jin; Yongping Cai; Yi Lin (Molecular Biology Reports, 2019)

Risk of Myocardial Infarction After Carbon Monoxide Poisoning: A Nationwide Population-Based Cohort Study - Chien-Cheng Huang; Chung-Han Ho; Yi-Chen Chen; Hung-Jung Lin; Chien-Chin Hsu; Jhi-Joung Wang; Shih-Bin Su; How-Ran Guo (Cardiovascular Toxicology, 2019)

Neonatal Dexamethasone Treatment Suppresses Hippocampal Estrogen Receptor α Expression in Adolescent Female Rats - Hui-Fang Chiu; Michael W. Y. Chan; Chiung-Yin Cheng; Jian-Liang Chou; Jora Meng-Ju Lin; Yi-Ling Yang; Kwok-Tung Lu (Molecular Neurobiology, 2019)

Genome-wide analysis identified 17 new loci influencing intraocular pressure in Chinese population - Lulin Huang; Yuhong Chen; Ying Lin; Pancy O. S. Tam; Yilian Cheng; Yi Shi; Bo Gong; Fang Lu; Jialiang Yang; Haixin Wang; Yi Yin; Yong Cao; et al. (Science China Life Sciences, 2019)

Immune Cells After Ischemic Stroke Onset: Roles, Migration, and Target Intervention - Lu-yao Ao; Yun-Yi Yan; Lin Zhou; Cheng-yuan Li; Wan-Ting Li; Wei-rong Fang; Yun-man Li (Journal of Molecular Neuroscience, 2018)

Response to “Letter to the editor re: Cheng YH, Chou WC, Yang YF, et al. Environ Sci Pollut Res (2018). https://doi.org/10.107/s11356-017-0875-4” - Yi-Hsien Cheng; Wei-Chun Chou; Ying-Fei Yang; Chi-Wei Huang; Chun Ming How; Szu-Chieh Chen; Wei-Yu Chen; Nan-Hung Hsieh; Yi-Jun Lin; Shu-Han You; Chung-Min Liao (Environmental Science and Pollution Research, 2018)

Integrating CNVs into meta-QTL identified GBP4 as positional candidate for adult cattle stature - Xiu-Kai Cao; Yong-Zhen Huang; Yi-Lei Ma; Jie Cheng; Zhen-Xian Qu; Yun Ma; Yue-Yu Bai; Feng Tian; Feng-Peng Lin; Yu-Lin Ma; Hong Chen (Functional & Integrative Genomics, 2018)

Effects of antiepileptic drugs on lipogenic gene regulation and hyperlipidemia risk in Taiwan: a nationwide population-based cohort study and supporting in vitro studies - Yi-Wen Li; Chung-Hsing Wang; Chao-Jung Chen; Charles C. N. Wang; Cheng-Li Lin; Wai-Kok Cheng; Hsin-Yi Shen; Yun-Ping Lim (Archives of Toxicology, 2018)

Acetaminophen Poisoning May Increase Coronary Artery Disease Risk: A Nationwide Cohort Study - Yu-Ting Chung; Che-Yi Chou; Wen-Chen Tsai; Wei-Kung Chen; Cheng-Li Lin; Wei-Sheng Chung (Cardiovascular Toxicology, 2018)

c.835-5T>G Variant in SMN1 Gene Causes Transcript Exclusion of Exon 7 and Spinal Muscular Atrophy - Shuang Wu; Yun-Lu Li; Ning-Yi Cheng; Chong Wang; En-Lin Dong; Ying-Qian Lu; Jin-Jing Li; Xin-Xin Guo; Xiang Lin; Lu-Lu Lai; Zhi-Wei Liu; Ning Wang; et al. (Journal of Molecular Neuroscience, 2018)

Peri-Therapeutic Quantitative Flow Analysis of Endovascular Revascularization for Ischemic Stroke Patients on Digital Subtraction Angiography - Shih-Neng Yang; Yu-Yi Lin; Tsung-Jung Ho; Shi-Yann Cheng; Yu-Rou Chiou; Chun-Han Liao; Geoffrey G. Zhang; Tzung-Chi Huang (Journal of Medical and Biological Engineering, 2018)

Effects of indole-3-butytric acid on lead and zinc accumulations in Pseudostellaria maximowicziana - Zhi Ran; Cheng Chen; Fabo Chen; Ming’an Liao; Lijin Lin; Xiulan Lv; Qunxian Deng; Xun Wang; Jin Wang; Yi Tang; Huaxiong Li (Environmental Monitoring and Assessment, 2018)

Combination Therapy with Low-Dose IVIG and a C1-esterase Inhibitor Ameliorates Brain Damage and Functional Deficits in Experimental Ischemic Stroke - Xinzhi Chen; Thiruma V. Arumugam; Yi-Lin Cheng; Jong-Hwan Lee; Srinivasulu Chigurupati; Mark P. Mattson; Milan Basta (NeuroMolecular Medicine, 2018)

Analysis of fecal microbiota in patients with functional constipation undergoing treatment with synbiotics - Lin Sheng Huang; Cheng Kong; Ren Yuan Gao; Xuebing Yan; Hong Jing Yu; Bin Wen; Qi Zhu; Tong Yi Shen; Zhen Liang Sun; Huan Long Qin (European Journal of Clinical Microbiology & Infectious Diseases, 2018)

Effects of melatonin on the growth and cadmium characteristics of Cyphomandra betacea seedlings - Lijin Lin; Jianhua Li; Fabo Chen; Ming’an Liao; Yi Tang; Dong Liang; Hui Xia; Yunsong Lai; Xun Wang; Cheng Chen; Wei Ren (Environmental Monitoring and Assessment, 2018)

Role of the meridional dipole of SSTA and associated cross-equatorial flow in the tropical eastern Pacific in terminating the 2014 El Niño development - Yi-Kai Wu; Lin Chen; Chi-Cherng Hong; Tim Li; Cheng-Ta Chen; Lu Wang (Climate Dynamics, 2018)

Evidence that NF-κB and MAPK Signaling Promotes NLRP Inflammasome Activation in Neurons Following Ischemic Stroke - David Yang-Wei Fann; Yun-An Lim; Yi-Lin Cheng; Ker-Zhing Lok; Prasad Chunduri; Sang-Ha Baik; Grant R. Drummond; S. Thameem Dheen; Christopher G. Sobey; Dong-Gyu Jo; Christopher Li-Hsian Chen; Thiruma V. Arumugam (Molecular Neurobiology, 2018)

PBPK/PD assessment for Parkinson’s disease risk posed by airborne pesticide paraquat exposure - Yi-Hsien Cheng; Wei-Chun Chou; Ying-Fei Yang; Chi-Wei Huang; Chun Ming How; Szu-Chieh Chen; Wei-Yu Chen; Nan-Hung Hsieh; Yi-Jun Lin; Shu-Han You; Chung-Min Liao (Environmental Science and Pollution Research, 2018)

The Distal Gut Bacterial Community of Some Primates and Carnivora - Xiu Chen; Qin-Yuan Li; Gui-Ding Li; Fang-Ji Xu; Li Han; Yi Jiang; Xue-Shi Huang; Cheng-Lin Jiang (Current Microbiology, 2018)

Effects of mutual intercropping on the cadmium accumulation in accumulator plants Stellaria media, Malachium aquaticum, and Galium aparine - Qiyu Lu; Jianhua Li; Fabo Chen; Ming’an Liao; Lijin Lin; Yi Tang; Dong Liang; Hui Xia; Yunsong Lai; Xun Wang; Cheng Chen; Wei Ren (Environmental Monitoring and Assessment, 2017)

Hyperaccumulator straw improves the cadmium phytoextraction efficiency of emergent plant Nasturtium officinale - Keqiang Li; Lijin Lin; Jin Wang; Hui Xia; Dong Liang; Xun Wang; Ming’an Liao; Li Wang; Li Liu; Cheng Chen; Yi Tang (Environmental Monitoring and Assessment, 2017)

Delayed Treatment with Green Tea Polyphenol EGCG Promotes Neurogenesis After Ischemic Stroke in Adult Mice - Jian-Cheng Zhang; Hang Xu; Yin Yuan; Jia-Yi Chen; Yu-Jing Zhang; Yun Lin; Shi-Ying Yuan (Molecular Neurobiology, 2017)

Cloning and characterization of DoMYC2 from Dendrobium officinale - Yanfang Zhu; Cancan Meng; Liqin Zhu; Dahui Li; Qing Jin; Cheng Song; Yongping Cai; Honghong Fan; Yi Lin (Plant Cell, Tissue and Organ Culture (PCTOC), 2017)

Mixture risk assessment due to ingestion of arsenic, copper, and zinc from milkfish farmed in contaminated coastal areas - Yi-Jun Lin; Min-Pei Ling; Szu-Chieh Chen; Wei-Yu Chen; Nan-Hung Hsieh; Yi-Hsien Cheng; Shu-Han You; Wei-Chun Chou; Ming-Chao Lin; Chung-Min Liao (Environmental Science and Pollution Research, 2017)

A meta‐analysis of fertilizer‐induced soil NO and combined NO +N 2 O emissions - Shuwei Liu; Feng Lin; Shuang Wu; Cheng Ji; Yi Sun; Yaguo Jin; Shuqing Li; Zhaofu Li; Jianwen Zou (Global Change Biology, 2017)
Soils are among the important sources of atmospheric nitric oxide ( NO ) and nitrous oxide (N 2 O), acting as a critical role in atmospheric chemistry. Updated data derived from 114 peer‐reviewed publications with 520 field measurements were synthesized using meta‐analysis procedure to examine the N fertilizer‐induced soil NO and the combined NO +N 2 O emissions across global soils. Besides factors identified in earlier reviews, additional factors responsible for NO fluxes were fertilizer type, soil C/N ratio, crop residue incorporation, tillage, atmospheric carbon dioxide concentration, drought and biomass burning. When averaged across all measurements, soil NO ‐N fluxes were estimated to be 4.06 kg ha −1 yr −1 , with the greatest (9.75 kg ha −1 yr −1 ) in vegetable croplands and the lowest (0.11 kg ha −1 yr −1 ) in rice paddies. Soil NO emissions were more enhanced by synthetic N fertilizer (+38%), relative to organic (+20%) or mixed N (+18%) sources. Compared with synthetic N fertilizer alone, synthetic N fertilizer combined with nitrification inhibitors substantially reduced soil NO emissions by 81%. The global mean direct emission factors of N fertilizer for NO ( EF NO ) and combined NO +N 2 O ( EF c ) were estimated to be 1.16% and 2.58%, with 95% confidence intervals of 0.71–1.61% and 1.81–3.35%, respectively. Forests had the greatest EF NO (2.39%). Within the croplands, the EF NO (1.71%) and EF c (4.13%) were the greatest in vegetable cropping fields. Among different chemical N fertilizer varieties, ammonium nitrate had the greatest EF NO (2.93%) and EF c (5.97%). Some options such as organic instead of synthetic N fertilizer, decreasing N fertilizer input rate, nitrification inhibitor and low irrigation frequency could be adopted to mitigate soil NO emissions. More field measurements over multiyears are highly needed to minimize the estimate uncertainties and mitigate soil NO emissions, particularly in forests and vegetable croplands.

Cytoplasmic aryl hydrocarbon receptor regulates glycogen synthase kinase 3 beta, accelerates vimentin degradation, and suppresses epithelial–mesenchymal transition in non-small cell lung cancer cells - Ching-Hao Li; Chen-Wei Liu; Chi-Hao Tsai; Yi-Jen Peng; Yu-Hsuan Yang; Po-Lin Liao; Chen-Chen Lee; Yu-Wen Cheng; Jaw-Jou Kang (Archives of Toxicology, 2017)

Identification of the Genetic Cause for Childhood Disintegrative Disorder by Whole-Exome Sequencing - Zhu Wen; Tian-Lin Cheng; Da-Zhi Yin; Shi-Bang Sun; Zheng Wang; Shun-Ying Yu; Yi Zhang; Zilong Qiu; Ya-Song Du (Neuroscience Bulletin, 2017)

Follistatin-like protein 1 suppressed pro-inflammatory cytokines expression during neuroinflammation induced by lipopolysaccharide - Kai-Yuan Cheng; Yi Liu; Ying-Guang Han; Jing-Kun Li; Jia-Lin Jia; Bin Chen; Zhi-Xiao Yao; Lin Nie; Lei Cheng (Journal of Molecular Histology, 2017)

Platelet receptor Gene (P2Y12, P2Y1) and platelet glycoprotein Gene (GPIIIa) polymorphisms are associated with antiplatelet drug responsiveness and clinical outcomes after acute minor ischemic stroke - Xingyang Yi; Qiang Zhou; Chun Wang; Jing Lin; Ping Liu; Cheng Fu (European Journal of Clinical Pharmacology, 2017)

Anti-apoptotic and Pro-survival Effects of Food Restriction on High-Fat Diet-Induced Obese Hearts - Yi-Yuan Lin; Po-Shiuan Hsieh; Yu-Jung Cheng; Shiu-Min Cheng; Chiao-nan Chen; Chih-Yang Huang; Chia-Hua Kuo; Chung-Lan Kao; Woei-Cherng Shyu; Shin-Da Lee (Cardiovascular Toxicology, 2017)

Enterovirga rhinocerotis gen. nov., sp. nov., isolated from Rhinoceros unicornis faeces - Xiu Chen; Qin-Yuan Li; Gui-Ding Li; Hui Lei; Yi Jiang; Li Han; Xue-Shi Huang; Cheng-Lin Jiang (Antonie van Leeuwenhoek, 2017)

Retraction Note to: Effect of Anti-Sticking Nanostructured Surface Coating on Minimally Invasive Electrosurgical Device in Brain - Han-Yi Cheng; Keng-Liang Ou; Hsi-Jen Chiang; Li-Hsiang Lin (Annals of Biomedical Engineering, 2017)

miRNA Expression Change in Dorsal Root Ganglia After Peripheral Nerve Injury - Hsueh-Ling Chang; Hung-Chen Wang; Yi-Ta Chunag; Chao-Wen Chou; I-Ling Lin; Chung-Sheng Lai; Lin-Li Chang; Kuang-I Cheng (Journal of Molecular Neuroscience, 2017)

ApoA-I induces S1P release from endothelial cells through ABCA1 and SR-BI in a positive feedback manner - Xing Liu; Kun Ren; Rong Suo; Sheng-Lin Xiong; Qing-Hai Zhang; Zhong-Cheng Mo; Zhen-Li Tang; Yue Jiang; Xiao-Shan Peng; Guang-Hui Yi (Journal of Physiology and Biochemistry, 2016)

Identification of Vibrio parahaemolyticus in Seafood by Multiplex PCR - Chung-Saint Lin; Tser-Sheng Lin; Din-Yuan Yu; Yi-Cheng Su; Yung-Hsiang Tsai (Journal of Aquatic Food Product Technology, 2016)

Identification of susceptibility gene associated with female primary Sjögren’s syndrome in Han Chinese by genome-wide association study - I-Wen Song; Hsiang-Cheng Chen; Yuh-Feng Lin; Jenn-Hwai Yang; Chi-Ching Chang; Chung-Tei Chou; Ming-Ta Michael Lee; Yi-Chun Chou; Chien-Hsiun Chen; Yuan-Tsong Chen; Chen-Hung Chen; Jer-Yuarn Wu (Human Genetics, 2016)

Mineral constituents of a prized edible mushroom (Tricholoma matsutake) and soils beneath the fruiting bodies from the production areas across China - Qiang Li; Shu-hong Li; Wen-li Huang; Cheng-yi Liu; Chuan Xiong; Xiao-lin Li; Lin-yong Zheng (Journal of Mountain Science, 2016)

Controlling effects of surface crusts on water infiltration in an arid desert area of Northwest China - Jin-Ling Yang; Gan-Lin Zhang; Fei Yang; Ren-Min Yang; Chen Yi; De-Cheng Li; Yu-Guo Zhao; Feng Liu (Journal of Soils and Sediments, 2016)

Betaine enhances antidepressant-like, but blocks psychotomimetic effects of ketamine in mice - Jen-Cheng Lin; Mei-Yi Lee; Ming-Huan Chan; Yi-Chyan Chen; Hwei-Hsien Chen (Psychopharmacology, 2016)

Allergy symptoms, serum total immunoglobulin E, and risk of head and neck cancer - Hsiao-Chen Liao; Shang-Yin Wu; Chun-Yen Ou; Jenn-Ren Hsiao; Jehn-Shyun Huang; Sen-Tien Tsai; Cheng-Chih Huang; Tung-Yiu Wong; Wei-Ting Lee; Ken-Chung Chen; Sheen-Yie Fang; Jiunn-Liang Wu; et al. (Cancer Causes & Control, 2016)

Microbacterium gilvum sp. nov., isolated from civet faeces - Xiu Chen; Qin-Yuan Li; Gui-Ding Li; Fang-Ji Xu; Yi Jiang; Li Han; Cheng-Lin Jiang; Xue-Shi Huang (Antonie van Leeuwenhoek, 2016)

Assessing exposure risks for freshwater tilapia species posed by mercury and methylmercury - Yi-Hsien Cheng; Yi-Jun Lin; Shu-Han You; Ying-Fei Yang; Chun Ming How; Yi-Ting Tseng; Wei-Yu Chen; Chung-Min Liao (Ecotoxicology, 2016)

A pilot study on using chlorine dioxide gas for disinfection of gastrointestinal endoscopes - Ying Yi; Li-mei Hao; Shu-ren Ma; Jin-hui Wu; Tao Wang; Song Lin; Zong-xing Zhang; Jian-cheng Qi (Journal of Zhejiang University-SCIENCE B, 2016)

Gene structure and expression characteristics of the auxin receptor TIR1 ortholog in Momordica charantia and developmental analysis of its promoter in transgenic plants - Cheng-Ku Lin; Nien-Ying Lee; Pung-Ling Huang; Yi-Yin Do (Journal of Plant Biochemistry and Biotechnology, 2016)

G2 rotavirus within an emergent VP7 evolutionary lineage circulating in children with acute diarrhea in Guangxi Province of China, 2014 - Hui Jin Dong; Yuan Qian; You Zhang; Lin Qing Zhao; Ru Nan Zhu; Yi Nong; Zhao Jun Mo; Rong Cheng Li (Archives of Virology, 2016)

Imperatorin inhibits the expression of alpha-hemolysin in Staphylococcus aureus strain BAA-1717 (USA300) - Ping Ouyang; Junjie Chen; Mao Sun; Zhongqiong Yin; Juchun Lin; Hualin Fu; Gang Shu; Changliang He; Cheng Lv; Xuming Deng; Kaiyu Wang; Yi Geng; et al. (Antonie van Leeuwenhoek, 2016)

SSR-based genetic mapping and QTL analysis for timing of spring bud flush, young shoot color, and mature leaf size in tea plant (Camellia sinensis) - Li-Qiang Tan; Li-Yuan Wang; Li-Yi Xu; Li-Yun Wu; Min Peng; Cheng-Cai Zhang; Kang Wei; Pei-Xian Bai; Hai-Lin Li; Hao Cheng; Gui-Nian Qi (Tree Genetics & Genomes, 2016)

Curcumin downregulates p38 MAPK-dependent X-ray repair cross-complement group 1 (XRCC1) expression to enhance cisplatin-induced cytotoxicity in human lung cancer cells - Chun-Liang Tung; Yi-Jun Jian; Jyh-Cheng Chen; Tai-Jing Wang; Wen-Ching Chen; Hao-Yu Zheng; Po-Yuan Chang; Kai-Sheng Liao; Yun-Wei Lin (Naunyn-Schmiedeberg's Archives of Pharmacology, 2016)

Paraquat Induces Cell Death Through Impairing Mitochondrial Membrane Permeability - Chuen-Lin Huang; Chih-Chang Chao; Yi-Chao Lee; Mei-Kuang Lu; Jing-Jy Cheng; Ying-Chen Yang; Vin-Chi Wang; Wen-Chang Chang; Nai-Kuei Huang (Molecular Neurobiology, 2016)

Serotonin Receptor 2B Mediates Mechanical Hyperalgesia by Regulating Transient Receptor Potential Vanilloid 1 - Yeu-Shiuan Su; Yuan-Yi Chiu; Shih-Yuan Lin; Chih-Cheng Chen; Wei-Hsin Sun (Journal of Molecular Neuroscience, 2016)

A new phenylethanoid glycoside from Orobanche cernua Loefling - Zheng-yi Qu; Yu-wei Zhang; Si-wen Zheng; Chun-lin Yao; Yin-ping Jin; Pei-he Zheng; Cheng-he Sun; Ying-ping Wang (Natural Product Research, 2016)

Review of studies on land use and land cover change in Nepal - Basanta Paudel; Yi-li Zhang; Shi-cheng Li; Lin-shan Liu; Xue Wu; Narendra Raj Khanal (Journal of Mountain Science, 2016)

Six new metabolites produced by Colletotrichum aotearoa 09F0161, an endophytic fungus isolated from Bredia oldhamii - Yi Hsiao; Ming-Jen Cheng; Hsun-Shuo Chang; Ming-Der Wu; Sung-Yuan Hsieh; Ta-Wei Liu; Chu-Hung Lin; Gwo-Fang Yuan; Ih-Sheng Chen (Natural Product Research, 2016)

Production of CCL20 on nucleus pulposus cells recruits IL-17-producing cells to degenerated IVD tissues in rat models - Yuanqiang Zhang; Lian Liu; Shuaishuai Wang; Yunpeng Zhao; Yi Liu; Jingkun Li; Lin Nie; Lei Cheng (Journal of Molecular Histology, 2016)

Transplantation of Cerebral Dopamine Neurotrophic Factor Transducted BMSCs in Contusion Spinal Cord Injury of Rats: Promotion of Nerve Regeneration by Alleviating Neuroinflammation - Hua Zhao; Lei Cheng; Xinwen Du; Yong Hou; Yi Liu; Zhaoqiang Cui; Lin Nie (Molecular Neurobiology, 2016)

G206D Mutation of Presenilin-1 Reduces Pen2 Interaction, Increases Aβ42/Aβ40 Ratio and Elevates ER Ca2+ Accumulation - Wei-Ting Chen; Yi-Fang Hsieh; Yan-Jing Huang; Che-Ching Lin; Yen-Tung Lin; Yu-Chao Liu; Cheng-Chang Lien; Irene Han-Juo Cheng (Molecular Neurobiology, 2015)

IL-17A enhances ADAMTS-7 expression through regulation of TNF-α in human nucleus pulposus cells - Shuai-Shuai Wang; Wei Zhang; Yuan-Qiang Zhang; Yunpeng Zhao; Yi Liu; Jing-kun Li; Hao-xuan Zhang; Lei Cheng; Lin Nie (Journal of Molecular Histology, 2015)

Enteractinococcus lamae sp. nov. and Enteractinococcus viverrae sp. nov., isolated from animal faeces - Xiu Chen; Gui-Ding Li; Qin-Yuan Li; Cai-Juan Hu; Shu-Mei Qiu; Yi Jiang; Cheng-Lin Jiang; Li Han; Xue-Shi Huang (Antonie van Leeuwenhoek, 2015)

Sphingobacterium rhinocerotis sp. nov., isolated from the faeces of Rhinoceros unicornis - Gui-Ding Li; Xiu Chen; Qin-Yuan Li; Fang-Ji Xu; Shu-Mei Qiu; Yi Jiang; Cheng-Lin Jiang (Antonie van Leeuwenhoek, 2015)

Mitoflash altered by metabolic stress in insulin-resistant skeletal muscle - Yi Ding; Huaqiang Fang; Wei Shang; Yao Xiao; Tao Sun; Ning Hou; Lin Pan; Xueting Sun; Qi Ma; Jingsong Zhou; Xianhua Wang; Xiuqin Zhang; et al. (Journal of Molecular Medicine, 2015)

Ceramics manufacturing contributes to ambient silica air pollution and burden of lung disease - Chung-Min Liao; Bo-Chun Wu; Yi-Hsien Cheng; Shu-Han You; Yi-Jun Lin; Nan-Hung Hsieh (Environmental Science and Pollution Research, 2015)

RETRACTED ARTICLE: Effect of Anti-Sticking Nanostructured Surface Coating on Minimally Invasive Electrosurgical Device in Brain - Han-Yi Cheng; Keng-Liang Ou; Hsi-Jen Chiang; Li-Hsiang Lin (Annals of Biomedical Engineering, 2015)

Calreticulin Regulates VEGF-A in Neuroblastoma Cells - Wen-Chin Weng; Kuan-Hung Lin; Pei-Yi Wu; Yi-Chien Lu; Yi-Cheng Weng; Bo-Jeng Wang; Yung-Feng Liao; Wen-Ming Hsu; Wang-Tso Lee; Hsinyu Lee (Molecular Neurobiology, 2015)

Two new macrosporin dimers from the fungus Alternaria sp. XZSBG-1 - Bin Chen; Lan Liu; Xun Zhu; Jun Wang; Yi Long; Si-Ping Jiang; Ai-Guo Xu; Yong-Cheng Lin (Natural Product Research, 2015)

Altitudinal and latitudinal dependence of future warming in Taiwan simulated by WRF nested with ECHAM5/MPIOM - Chuan‐Yao Lin; Ying‐Jea Chua; Yang‐Fan Sheng; Huang‐Hsiung Hsu; Chao‐Tzuen Cheng; Yi‐Yin Lin (International Journal of Climatology, 2015)
It is difficult and inadequate to use a global model alone for projecting future climate changes in areas such as Taiwan, a complex geographic nature island, due to its coarse resolution. In this study, we have performed dynamic downscaling of Taiwan's climate in the recent past (1979–2003) and climate change projection for the near and distant future (2015–2039 and 2075–2099, respectively) by using the Weather Research Forecasting (WRF) model. The simulation is forced by the Max Plank Institute Hamburg, global model, ECHAM5/MPIOM. Simulation results showed close correlation between fine‐resolution downscaling by WRF nested with ECHAM5/MPIOM and the actual observation data for the period 1979–2003. Projection of future climate changes revealed both altitudinal and latitudinal variations in warming trend, with more significant temperature increase in mountain areas than in plain areas towards the end of the 21st century and more obvious warming in the north than in the south of Taiwan. The results obtained in this study can be applied to other regions of similar latitudes and with comparable relief.

Rapid detection of copper chlorophyll in vegetable oils based on surface-enhanced Raman spectroscopy - Wei-Nan Lian; Jessie Shiue; Huai-Hsien Wang; Wei-Chen Hong; Po-Han Shih; Chao-Kai Hsu; Ching-Yi Huang; Cheng-Rong Hsing; Ching-Ming Wei; Juen-Kai Wang; Yuh-Lin Wang (Food Additives & Contaminants: Part A, 2015)

Chalcone synthase EaCHS1 from Eupatorium adenophorum functions in salt stress tolerance in tobacco - Chen Lijuan; Guo Huiming; Lin Yi; Cheng Hongmei (Plant Cell Reports, 2015)

Diacylglycerol Kinase (DGK) Inhibitor II (R59949) Could Suppress Retinal Neovascularization and Protect Retinal Astrocytes in an Oxygen-Induced Retinopathy Model - Lu Yang; Yue Xu; Weihua Li; Boyu Yang; Shanshan Yu; Huanjiao Zhou; Cheng Yang; Fan Xu; Jun Wang; Yi Gao; Yongsheng Huang; Lin Lu; et al. (Journal of Molecular Neuroscience, 2015)

Lysobacter lycopersici sp. nov., isolated from tomato plant Solanum lycopersicum - Shih-Yao Lin; Asif Hameed; Cheng-Zhe Wen; You-Cheng Liu; Yi-Han Hsu; Wei-An Lai; Chiu-Chung Young (Antonie van Leeuwenhoek, 2015)

Regional response of dengue fever epidemics to interannual variation and related climate variability - Chung-Min Liao; Tang-Luen Huang; Yi-Jun Lin; Shu-Han You; Yi-Hsien Cheng; Nan-Hung Hsieh; Wei-Yu Chen (Stochastic Environmental Research and Risk Assessment, 2015)

Oricola cellulosilytica gen. nov., sp. nov., a cellulose-degrading bacterium of the family Phyllobacteriaceae isolated from surface seashore water, and emended descriptions of Mesorhizobium loti and Phyllobacterium myrsinacearum - Asif Hameed; Mariyam Shahina; Wei-An Lai; Shih-Yao Lin; Li-Sen Young; You-Cheng Liu; Yi-Han Hsu; Chiu-Chung Young (Antonie van Leeuwenhoek, 2015)

Rhizobium capsici sp. nov., isolated from root tumor of a green bell pepper (Capsicum annuum var. grossum) plant - Shih-Yao Lin; Mei-Hua Hung; Asif Hameed; You-Cheng Liu; Yi-Han Hsu; Cheng-Zhe Wen; A. B. Arun; Hans-Jürgen Busse; Stefanie P. Glaeser; Peter Kämpfer; Chiu-Chung Young (Antonie van Leeuwenhoek, 2015)

Genetic association study between INSULIN pathway related genes and high myopia in a Han Chinese population - Xiaoqi Liu; Pu Wang; Chao Qu; Hong Zheng; Bo Gong; Shi Ma; He Lin; Jing Cheng; Zhenglin Yang; Fang Lu; Yi Shi (Molecular Biology Reports, 2015)

Trace levels of mitomycin C disrupt genomic integrity and lead to DNA damage response defect in long-term-cultured human embryonic stem cells - Di Zhou; Ge Lin; Si-Cong Zeng; Bo Xiong; Ping-Yuan Xie; De-Hua Cheng; Qing Zheng; Qi Ouyang; Xiao-Ying Zhou; Wei-Ling Tang; Yi Sun; Guang-Ying Lu; et al. (Archives of Toxicology, 2015)

Two new truffles species, Tuber alboumbilicum and Tuber pseudobrumale from China - Shu-Hong Li; Lin-Yong Zheng; Cheng-Yi Liu; Yun Wang; Lin Li; Yong-Chang Zhao; Xiao-Lei Zhang; Mei Yang; Hai-Kuan Xiong; Yuan Qing; Li Wang; De-Qun Zhou (Mycological Progress, 2014)

Denbinobin upregulates miR-146a expression and attenuates IL-1β-induced upregulation of ICAM-1 and VCAM-1 expressions in osteoarthritis fibroblast-like synoviocytes - Chia-Ron Yang; Kao-Shang Shih; Jing-Ping Liou; Yi-Wen Wu; I-Ni Hsieh; Hsueh-Yun Lee; Tzu-Cheng Lin; Jyh-Horng Wang (Journal of Molecular Medicine, 2014)

Experiments on channel evolution due to dam removal in Taiwan - Hsiao-Wen Wang; Ying-Che Cheng; Chung-Yi Lin (Journal of Mountain Science, 2014)

Typhoon-enhanced upwelling and its influence on fishing activities in the southern East China Sea - Yi Chang; Jui-Wen Chan; Yuan-Chao Angelo Huang; Wei-Quan Lin; Ming-An Lee; Kuo-Tien Lee; Cheng-Hsin Liao; Kae-Yih Wang; Yi-Chun Kuo (International Journal of Remote Sensing, 2014)

Different Visible Colors and Green Fluorescence Were Obtained from the Mutated Purple Chromoprotein Isolated from Sea Anemone - Cheng-Yi Chiang; Yi-Lin Chen; Huai-Jen Tsai (Marine Biotechnology, 2014)

Gordonia jinhuaensis sp. nov., a novel actinobacterium, isolated from a VBNC (viable but non-culturable) state in pharmaceutical wastewater - Shan-Hui Li; Yi Jin; Juan Cheng; Dong-Jin Park; Chang-Jin Kim; Wael N. Hozzein; Mohammed A. M. Wadaan; Wen-Sheng Shu; Lin-Xian Ding; Wen-Jun Li (Antonie van Leeuwenhoek, 2014)

Description of Niveispirillum fermenti gen. nov., sp. nov., isolated from a fermentor in Taiwan, transfer of Azospirillum irakense (1989) as Niveispirillum irakense comb. nov., and reclassification of Azospirillum amazonense (1983) as Nitrospirillum amazonense gen. nov - Shih-Yao Lin; Asif Hameed; Fo-Ting Shen; You-Cheng Liu; Yi-Han Hsu; Mariyam Shahina; Wei-An Lai; Chiu-Chung Young (Antonie van Leeuwenhoek, 2014)

Cingulum Correlates of Cognitive Functions in Patients with Mild Cognitive Impairment and Early Alzheimer’s Disease: A Diffusion Spectrum Imaging Study - Yi-Cheng Lin; Yao-Chia Shih; Wen-Yih I. Tseng; Yu-Hsiu Chu; Meng-Tien Wu; Ta-Fu Chen; Pei-Fang Tang; Ming-Jang Chiu (Brain Topography, 2014)

Mechanisms of Anti-inflammatory Property of Conserved Dopamine Neurotrophic Factor: Inhibition of JNK Signaling in Lipopolysaccharide-Induced Microglia - Hua Zhao; Lei Cheng; Yi Liu; Wen Zhang; Sailendra Maharjan; Zhaoqiang Cui; Xingli Wang; Dongqi Tang; Lin Nie (Journal of Molecular Neuroscience, 2014)

The roles of two transcription factors, ABI4 and CBFA, in ABA and plastid signalling and stress responses - Zhong-Wei Zhang; Ling-Yang Feng; Jian Cheng; He Tang; Fei Xu; Feng Zhu; Zhong-Yi Zhao; Ming Yuan; Yang-Er Chen; Jian-Hui Wang; Shu Yuan; Hong-Hui Lin (Plant Molecular Biology, 2013)

Design, synthesis, and evaluation of fluorescent cell-penetrating peptidic antagonists of Grb2-SH2 for targeting MCF-7 breast cancer cells - Yu-Cheng Hsiao; Chen-Yu Lee; Yi-Jhen Lin; Shu-Huai Tsai; Kee-Ching G. Jeng; Wei-Ting Chao; Feng-Di T. Lung (Medicinal Chemistry Research, 2013)

Mesencephalic Astrocyte-Derived Neurotrophic Factor Inhibits Oxygen–Glucose Deprivation-Induced Cell Damage and Inflammation by Suppressing Endoplasmic Reticulum Stress in Rat Primary Astrocytes - Hua Zhao; Yi Liu; Lei Cheng; Ben Liu; Wen Zhang; Ying-Jun Guo; Lin Nie (Journal of Molecular Neuroscience, 2013)

Hesperetin protects against cardiac remodelling induced by pressure overload in mice - Wei Deng; Duan Jiang; Yi Fang; Heng Zhou; Zhihong Cheng; Yafen Lin; Rui Zhang; Jieyu Zhang; Peng Pu; Yuan Liu; Zhouyan Bian; Qizhu Tang (Journal of Molecular Histology, 2013)

Niche Divergence Among Sex and Age Classes in Black-and-White Snub-nosed Monkeys (Rhinopithecus bieti) - Yi Wan; Rui-Chang Quan; Guo-Peng Ren; Lin Wang; Yong-Cheng Long; Xiao-Hu Liu; Jian-Guo Zhu (International Journal of Primatology, 2013)

A low-pH medium in vitro or the environment within a macrophage decreases the transcriptional levels of fimA, fimZ and lrp in Salmonella enterica serovar Typhimurium - Ke-Chuan Wang; Yuan-Hsun Hsu; Yi-Ning Huang; Ter-Hsin Chen; Jiunn-Horng Lin; Shih-Ling Hsuan; Maw-Sheng Chien; Wei-Cheng Lee; Kuang-Sheng Yeh (Journal of Biosciences, 2013)

Monascusazaphilones A–C, three new azaphilone analogues isolated from the fungus Monascus purpureus BCRC 38108 - Ming-Der Wu; Ming-Jen Cheng; Yi-Jen Yech; Yen-Lin Chen; Kai-Ping Chen; Ping-Hsun Yang; Ih-Sheng Chen; Gwo-Fang Yuan (Natural Product Research, 2013)

Warnstorfia exannulata, an aquatic moss in the Arctic: seasonal growth responses - Cai-Qing Guo; Ryszard Ochyra; Peng-Cheng Wu; Rodney D. Seppelt; Yi-Feng Yao; Lin-Gen Bian; Su-Ping Li; Cheng-Sen Li (Climatic Change, 2013)

Reduction of connexin43 in human endothelial progenitor cells impairs the angiogenic potential - Hsueh-Hsiao Wang; Cheng-Huang Su; Yih-Jer Wu; Jiun-Yi Li; Ya-Ming Tseng; Yi-Chun Lin; Chin-Ling Hsieh; Cheng-Ho Tsai; Hung-I Yeh (Angiogenesis, 2013)

Application of a web-based remote agro-ecological monitoring system for observing spatial distribution and dynamics of Bactrocera dorsalis in fruit orchards - Joe-Air Jiang; Tzu-Shiang Lin; En-Cheng Yang; Chwan-Lu Tseng; Chia-Pang Chen; Chung-Wei Yen; Xiang-Yao Zheng; Chun-Yi Liu; Ren-Hau Liu; Yu-Fan Chen; Wan-Yi Chang; Cheng-Long Chuang (Precision Agriculture, 2013)

Application of a feature-based approach to debris flow detection by numerical simulation - Chih-Wei Lin; Cheng-Wu Chen; Wen-Ko Hsu; Chia-Yen Chen; Chung-Hung Tsai; Yi-Ping Hung; Wei-Ling Chiang (Natural Hazards, 2013)

Predictors of First-Week Mortality in Patients with Acute Spontaneous Cerebellar Hemorrhage - Yung-Tsan Wu; Tsung-Ying Li; Shang-Lin Chiang; Heng-Yi Chu; Shin-Tsu Chang; Liang-Cheng Chen (The Cerebellum, 2013)

Spatial patterns and climate drivers of carbon fluxes in terrestrial ecosystems of China - Gui‐Rui Yu; Xian‐Jin Zhu; Yu‐Ling Fu; Hong‐Lin He; Qiu‐Feng Wang; Xue‐Fa Wen; Xuan‐Ran Li; Lei‐Ming Zhang; Li Zhang; Wen Su; Sheng‐Gong Li; Xiao‐Min Sun; et al. (Global Change Biology, 2013)
Understanding the dynamics and underlying mechanism of carbon exchange between terrestrial ecosystems and the atmosphere is one of the key issues in global change research. In this study, we quantified the carbon fluxes in different terrestrial ecosystems in China, and analyzed their spatial variation and environmental drivers based on the long‐term observation data of China FLUX sites and the published data from other flux sites in China. The results indicate that gross ecosystem productivity ( GEP ), ecosystem respiration ( ER ), and net ecosystem productivity ( NEP ) of terrestrial ecosystems in China showed a significantly latitudinal pattern, declining linearly with the increase of latitude. However, GEP , ER , and NEP did not present a clear longitudinal pattern. The carbon sink functional areas of terrestrial ecosystems in China were mainly located in the subtropical and temperate forests, coastal wetlands in eastern China, the temperate meadow steppe in the northeast China, and the alpine meadow in eastern edge of Qinghai‐Tibetan Plateau. The forest ecosystems had stronger carbon sink than grassland ecosystems. The spatial patterns of GEP and ER in China were mainly determined by mean annual precipitation ( MAP ) and mean annual temperature ( MAT ), whereas the spatial variation in NEP was largely explained by MAT . The combined effects of MAT and MAP explained 79%, 62%, and 66% of the spatial variations in GEP , ER , and NEP , respectively. The GEP , ER , and NEP in different ecosystems in China exhibited ‘positive coupling correlation’ in their spatial patterns. Both ER and NEP were significantly correlated with GEP , with 68% of the per‐unit GEP contributed to ER and 29% to NEP . MAT and MAP affected the spatial patterns of ER and NEP mainly by their direct effects on the spatial pattern of GEP .

Iron plaque formation and its effect on arsenic uptake by different genotypes of paddy rice - Chia-Hsing Lee; Yi-Cheng Hsieh; Tzu-Huei Lin; Dar-Yuan Lee (Plant and Soil, 2013)

The construction of a high-resolution visual monitoring for hazard analysis - Chi-Wei Lin; Yi-Ping Hung; Wen-Ko Hsu; Wei-Ling Chiang; Cheng-Wu Chen (Natural Hazards, 2013)

Two new triterpenoid saponins from Caragana microphylla seeds - Cheng-Jian Zheng; Gui-Lin Jin; Jing-Ping Zou; Yi-Ping Jiang; Pei-Xin Sun; Lu-Ping Qin (Journal of Natural Medicines, 2013)

First record of wild ephyrae of the giant jellyfish Nemopilema nomurai - Masaya Toyokawa; Masashi Shibata; Jia-Hua Cheng; Hui-Yu Li; Jian-Zhong Ling; Nan Lin; Zun-Lei Liu; Yi Zhang; Manabu Shimizu; Hideki Akiyama (Fisheries Science, 2012)

Potential hazard analysis and risk assessment of debris flow by fuzzy modeling - Jeng-Wen Lin; Cheng-Wu Chen; Cheng-Yi Peng (Natural Hazards, 2012)

Association between polymorphisms of the CYP11A1 gene and polycystic ovary syndrome in Chinese women - Cheng-wei Zhang; Xin-lin Zhang; Yan-jie Xia; Yun-xia Cao; Wen-jun Wang; Pei Xu; Ye-na Che; Xiao-ke Wu; Long Yi; Qian Gao; Yong Wang (Molecular Biology Reports, 2012)

Occurrence of diarrheagenic Escherichia coli genes in raw water of water treatment plants - Shih-Wei Huang; Bing-Mu Hsu; Yen-Jui Su; Dar-Der Ji; Wei-Chen Lin; Jyh-Larng Chen; Feng-Cheng Shih; Po-Min Kao; Yi-Chou Chiu (Environmental Science and Pollution Research, 2012)

Disruption of Bombyx mori nucleopolyhedrovirus ORF71 (Bm71) results in inefficient budded virus production and decreased virulence in host larvae - Min-Juan Zhang; Ruo-Lin Cheng; Yi-Han Lou; Wan-Lu Ye; Tao Zhang; Xiao-Ying Fan; Hai-Wei Fan; Chuan-Xi Zhang (Virus Genes, 2012)

Bombyx mori nucleopolyhedrovirus ORF54, a viral desmoplakin gene, is associated with the infectivity of budded virions - Min-Juan Zhang; Cai-Hong Tian; Xiao-Ying Fan; Yi-Han Lou; Ruo-Lin Cheng; Chuan-Xi Zhang (Archives of Virology, 2012)

Hyperglycemia as a Predictor of Poor Outcome at Discharge in Patients with Acute Spontaneous Cerebellar Hemorrhage - Yung-Tsan Wu; Tsung-Ying Li; Shao-Chi Lu; Liang-Cheng Chen; Heng-Yi Chu; Shang-Lin Chiang; Shin-Tsu Chang (The Cerebellum, 2012)

Cloning and expression of the two new variants of Nav1.5/SCN5A in rat brain - Cheng-Tao Ren; Dong-Mei Li; Shao-Wu Ou; Yun-Jie Wang; Yi Lin; Zhi-Hong Zong; Masaki Kameyama; Asako Kameyama (Molecular and Cellular Biochemistry, 2012)

Acute effects of plyometric jumping and intermittent running on serum bone markers in young males - Che-Fu Lin; Tsang-hai Huang; Kuo-Cheng Tu; Linda L. Lin; Yi-Hsuan Tu; Rong-Sen Yang (European Journal of Applied Physiology, 2012)

Determination of critical power in trained rowers using a three-minute all-out rowing test - Ching-Feng Cheng; Yi-Shan Yang; Hui-Mei Lin; Chia-Lun Lee; Chun-Yi Wang (European Journal of Applied Physiology, 2012)

MicroRNA- 1 represses Cx43 expression in viral myocarditis - Hong-Fei Xu; Yu-Jie Ding; Yi-Wen Shen; Ai-Min Xue; Hong-Mei Xu; Cheng-Liang Luo; Bei-Xu Li; Yue-Lin Liu; Zi-Qin Zhao (Molecular and Cellular Biochemistry, 2012)

Kalman filter decision systems for debris flow hazard assessment - Jeng-Wen Lin; Cheng-Wu Chen; Cheng-Yi Peng (Natural Hazards, 2012)

An upstream regulatory element confers orientation-independent enhancement of the TSG101 promoter activity in transformed cells - Shih-Fang Hsu; Yih-Gang Goan; Hsien-Yu Tsai; Yi-Ru Lin; Rue-Tsuan Liu; Jiin-Tsuey Cheng (Molecular Biology Reports, 2012)

Molecular and morphological evidences reveal a cryptic species in the Vinaceous Rosefinch Carpodacus vinaceus (Fringillidae; Aves) - Hsu‐Chun Wu; Rong‐Chien Lin; Hsin‐Yi Hung; Chia‐Fen Yeh; Jui‐Hua Chu; Xiao‐Jun Yang; Chiou‐Ju Yao; Fa‐Sheng Zou; Cheng‐Te Yao; Shou‐Hsien Li; Fu‐Min Lei (Zoologica Scripta, 2011)
Wu, H.‐C., Lin, R.‐C., Hung, H.‐Y., Yeh, C.‐F., Chu, J.‐H., Yang, X.‐J., Yao, C.‐J., Zou, F.‐S., Yao, C.‐T., Li, S.‐H. & Lei, F.‐M. (2011). Molecular and morphological evidences reveal a cryptic species in the Vinaceous Rosefinch Carpodacus vinaceus (Fringillidae; Aves). — Zoologica Scripta, 40 , 468–478. The Vinaceous Rosefinch ( Carpodacus vinaceus ) is endemic in East Asia with two recognized subspecies – C. v. vinaceus , distributed along the eastern edge of the Tibetan Plateau and the Himalayas, and C. v. formosanus , restricted to Taiwan’s Central Mountain Range. As reflected in a controversial taxonomic history, this vastly disjunctive distribution pattern suggests that the subspecies, having been isolated from each other for a long time, might have diverged, challenging the current taxonomic treatment and calling for possible species delimitation. Sequences of two mitochondrial fragments (mtDNA) and two Z‐linked nuclear loci (zDNA) were used to reconstruct the intraspecific phylogeny of C. vinaceous . The mtDNA tree shows that the two subspecies of the vinaceous rosefinch form two exclusively monophyletic clades. All but one zDNA sequences from the nominate subspecies and C. v. formosanus also formed exclusively monophyletic clades (the exceptional zDNA sequence from C. v. vinaceous formed a weakly supported clade with two outgroup species). Moreover, by conducting quantitative comparisons of morphometric traits and male plumage coloration, we found that the two subspecies exhibit distinguishable morphological differences. All the evidence therefore suggests that C. v. formosanus is a cryptic species and that its taxonomic status should be restored to full species. Molecular dating suggests that the two sibling rosefinches split 1.7 ± 0.2 million years ago, providing a point estimate for the historical connectivity of biota between eastern Tibet‐Himalayas and montane Taiwan.

Fast Cleanup System Combined with a Dioxin-responsive Element-driven Luciferase Bioassay for Analysis of Polychlorinated Dibenzo-p-dioxins/furans in Sediments and Soils - How-Ran Chao; Ya-Fen Wang; Ding-Yan Lin; Yi-Ting Cheng; Tsui-Chun Tsou (Bulletin of Environmental Contamination and Toxicology, 2011)

Methylobacterium soli sp. nov. a methanol-utilizing bacterium isolated from the forest soil - Yan-Ru Cao; Qian Wang; Rong-Xian Jin; Shu-Kun Tang; Yi Jiang; Wen-Xiang He; Hang-Xian Lai; Li-Hua Xu; Cheng-Lin Jiang (Antonie van Leeuwenhoek, 2011)

Phylogeny of Arachis based on internal transcribed spacer sequences - Chuan Tang Wang; Xiu Zhen Wang; Yue Yi Tang; Dian Xu Chen; Feng Gao Cui; Jian Cheng Zhang; Shan Lin Yu (Genetic Resources and Crop Evolution, 2011)

Point patterns of tree distribution determined by habitat heterogeneity and dispersal limitation - Yi-Ching Lin; Li-Wan Chang; Kuoh-Cheng Yang; Hsiang-Hua Wang; I-Fang Sun (Oecologia, 2011)

Molecular characterization of a phenylalanine ammonia-lyase gene (BoPAL1) from Bambusa oldhamii - Lu-Sheng Hsieh; Yi-Lin Hsieh; Chuan-Shan Yeh; Chieh-Yang Cheng; Chien-Chih Yang; Ping-Du Lee (Molecular Biology Reports, 2011)

Molecular phylogeny of Ranunculaceae based on rbc L sequences - Ying-fan Cai; Sheng-wei Li; Min Chen; Ming-feng Jiang; Yi Liu; Yong-fang Xie; Quan Sun; Huai-zhong Jiang; Neng-wen Yin; Ling Wang; Rui Zhang; Cheng-lin Huang; et al. (Biologia, 2010)

Rubellimicrobium roseum sp. nov., a Gram-negative bacterium isolated from the forest soil sample - Yan-Ru Cao; Yi Jiang; Qian Wang; Shu-Kun Tang; Wen-Xiang He; Quan-Hong Xue; Li-Hua Xu; Cheng-Lin Jiang (Antonie van Leeuwenhoek, 2010)

The envelope glycoprotein domain III of dengue virus type 2 induced the expression of anticoagulant molecules in endothelial cells - Lien-Cheng Chen; Trai-Ming Yeh; Yi-Ying Lin; Yi-Fen Wang; Shu-Jem Su; Chang-Yu Chen; Kuan-Hua Lin; Miao-Chen Chou; Huey-Wen Shyu (Molecular and Cellular Biochemistry, 2010)

Roles of cysteines Cys115 and Cys201 in the assembly and thermostability of grouper betanodavirus particles - Chun-Hsiung Wang; Chi-Hsin Hsu; Yi-Min Wu; Yu-Chun Luo; Mei-Hui Tu; Wei-hau Chang; R. Holland Cheng; Chan-Shing Lin (Virus Genes, 2010)

The second prolactin receptor in Nile tilapia (Oreochromis niloticus): molecular characterization, tissue distribution and gene expression - Yong Zhang; Zijie Long; Yangyuan Li; Shibai Yi; Yu Shi; Xilan Ma; Weiren Huang; Danqi Lu; Pei Zhu; Xiaochun Liu; Zining Meng; Xigui Huang; et al. (Fish Physiology and Biochemistry, 2010)

A Meteorological Potential Forecast Model for Acid Rain in Fujian Province, China - Yi Yong Cai; Chang Cheng Lin; Jing Xiong Liu; De Hui Wu; Dong Ying Lian; Bin Bin Chen (Bulletin of Environmental Contamination and Toxicology, 2010)

Assessment of the role of brine shrimp Artemia in white spot syndrome virus (WSSV) transmission - Jia-Song Zhang; Shuang-Lin Dong; Yun-Wei Dong; Xiang-Li Tian; Yi-Cheng Cao; Zuo-Jia Li; Dong-Chun Yan (Veterinary Research Communications, 2010)

Chemical constituents from the leaves of Machilus zuihoensis Hayata var. mushaensis (Lu) Y.C. Liu - Chung-Yi Chen; Ming-Jen Cheng; Yi-Jung Chiang; Jia-Chi Bai; Chih-Tsao Chiu; Rong-Jyh Lin; Yen-Ray Hsui; Wen-Li Lo (Natural Product Research, 2009)

Effect of calmidazolium on [Ca2+]i and viability in human hepatoma cells - Wei-Chuan Liao; Chorng-Chih Huang; He-Hsiung Cheng; Jue-Long Wang; Ko-Long Lin; Jin-Shiung Cheng; Kuo-Liang Chai; Pei-Te Hsu; Jeng-Yu Tsai; Yi-Chien Fang; Yih-Chau Lu; Hong-Tai Chang; et al. (Archives of Toxicology, 2009)

Compositions and source apportionments of atmospheric aerosol during Asian dust storm and local pollution in central Taiwan - Man-Ting Cheng; Wei-Chun Chou; Chia-Pin Chio; Shih-Chieh Hsu; Yi-Ru Su; Pei-Hsuan Kuo; Ben-Jei Tsuang; Shuen-Hsin Lin; Charles C.-K. Chou (Journal of Atmospheric Chemistry, 2008)

Pravastatin attenuates carboplatin-induced cardiotoxicity via inhibition of oxidative stress associated apoptosis - Ching-Feng Cheng; Shu-Hui Juan; Jin-Jer Chen; Ying-Chi Chao; His-Hsien Chen; Wei-Shiung Lian; Chun-Yi Lu; Chung-I Chang; Ted-H Chiu; Heng Lin (Apoptosis, 2008)

Gene expression variation increase in trisomy 21 tissues - Ching Yu Chou; Li Yu Liu; Chien Yu Chen; Cheng Hsien Tsai; Hsiao Lin Hwa; Li Yun Chang; Yi Shing Lin; Fon Jou Hsieh (Mammalian Genome, 2008)

Hypoxia-induced compensatory effect as related to Shh and HIF-1α in ischemia embryo rat heart - Jin-Ming Hwang; Yi-Jiun Weng; James A. Lin; Da-Tian Bau; Fu-Yang Ko; Fuu-Jen Tsai; Chang-Hai Tsai; Chieh-Hsi Wu; Pei-Cheng Lin; Chih-Yang Huang; Wei-Wen Kuo (Molecular and Cellular Biochemistry, 2008)

Salinicoccus salitudinis sp. nov., a new moderately halophilic bacterium isolated from a saline soil sample - Yi-Guang Chen; Xiao-Long Cui; Wen-Jun Li; Li-Hua Xu; Meng-Liang Wen; Qian Peng; Cheng-Lin Jiang (Extremophiles, 2008)

Exsolution lamellae in a clinopyroxene megacryst aggregate from Cenozoic basalt, Leizhou Peninsula, South China: petrography and chemical evolution - Xiao-Long Huang; Yi-Gang Xu; Ching-Hua Lo; Ru-Cheng Wang; Chuan-Yong Lin (Contributions to Mineralogy and Petrology, 2007)

A new cytotoxic cholesterol sulfate from marine sponge Halichondria rugosa - Hong-Jun Zhang; Jing-Bo Sun; Hou-Wen Lin; Zeng-Lei Wang; Hua Tang; Ping Cheng; Wan-Sheng Chen; Yang-Hua Yi (Natural Product Research, 2007)

Changes of Src-suppressed C kinase substrate expression in cytokine induced reactive C6 glioma cells - Lin-Lin Sun; Chun Cheng; Hai-Ou Liu; Feng Xiao; Jing Qin; Xiao-Yi Shao; Ai-Guo Shen (Neuroscience Bulletin, 2007)

A rice gene activation/knockout mutant resource for high throughput functional genomics - Yue-Ie Hsing; Chyr-Guan Chern; Ming-Jen Fan; Po-Chang Lu; Ku-Ting Chen; Shuen-Fang Lo; Peng-Kai Sun; Shin-Lon Ho; Kuo-Wei Lee; Yi-Chieh Wang; Wen-Lii Huang; Swee-Suak Ko; et al. (Plant Molecular Biology, 2007)

Biodegradation Kinetics and Effects of Operating Parameters on the Performance of a Methyl Tert-Butyl Ether Degrading Biofilter - Yi-Cheng Chiu; Chi-Wen Lin; Tsang-Chih Kao; Xiao-Yan Tang (Water, Air, & Soil Pollution, 2006)

Over-expressed estrogen receptor-α up-regulates hTNF-α gene expression and down-regulates β-catenin signaling activity to induce the apoptosis and inhibit proliferation of LoVo colon cancer cells - Hsi-Hsien Hsu; Sue-Fei Cheng; Li-Mien Chen; Jer-Yu Liu; Chun-Hsien Chu; Yi-Jiun Weng; Zih-Ying Li; Chung-Sheng Lin; Shin-Da Lee; Wei-Wen Kuo; Chih-Yang Huang (Molecular and Cellular Biochemistry, 2006)

OsGLU1, A Putative Membrane-bound Endo-1,4-ß-D-glucanase from Rice, Affects Plant Internode Elongation - Hua-Lin Zhou; Si-Jie He; Yang-Rong Cao; Tao Chen; Bao-Xing Du; Cheng-Cai Chu; Jin-Song Zhang; Shou-Yi Chen (Plant Molecular Biology, 2006)

A fine physical map of the rice chromosome 5 - Chia-Hsiung Cheng; Mei-Chu Chung; Shu-Mei Liu; Shi-Kuang Chen; Fang-Yi Kao; Shu-Jen Lin; Shin-Hsin Hsiao; I-Chieh Tseng; Yue-Ie C. Hsing; Hong-Pang Wu; Ching-San Chen; Jei-Fu Shaw; et al. (Molecular Genetics and Genomics, 2005)

Streptomyces nanningensis sp. nov. a novel Streptomycete from forest soil - Yi Jiang; Wen-Jun Li; Ping Xu; Ming-Gang Li; Meng-Liang Wen; Guan-Hua Du; Li-Hua Xu; Cheng-Lin Jiang (Antonie van Leeuwenhoek, 2005)

Streptomyces roseoalbus sp. nov., an actinomycete isolated from soil in Yunnan, China - Li-Hua Xu; Yi Jiang; Wen-Jun Li; Meng-Lang Wen; Ming-Gang Li; Cheng-Lin Jiang (Antonie van Leeuwenhoek, 2005)

Analysis of heat-shock protein70 gene polymorphisms and the risk of Parkinson?s disease - Chiung-Mei Chen; Yuying Hsu; Sih-Jing Lin; Kuo-Hsuan Chang; Guey-Jen Lee-Chen; Cheng-Kuang Wang; Yi-Ying Lin; Yih-Ru Wu; Hon-Chung Fung (Human Genetics, 2004)

Diverse apoptotic pathways in enterovirus 71–infected cells - Shih-Cheng Chang; Jing-Yi Lin; Lily Yen-Cheng Lo; Mei-Ling Li; Shin-Ru Shih (Journal of NeuroVirology, 2004)

Identification of genes involved in the host response to enterovirus 71 infection - Shin-Ru Shih; Victor Stollar; Jing-Yi Lin; Shih-Cheng Chang; Guang-Wu Chen; Mei-Ling Li (Journal of NeuroVirology, 2004)

The mechanism of honokiol-induced and magnolol-induced inhibition on muscle contraction and Ca 2+ mobilization in rat uterus - Yu-Cheng Lu; Hwei-Hsien Chen; Chien-Hsin Ko; Yi-Ruu Lin; Ming-Huan Chan (Naunyn-Schmiedeberg's Archives of Pharmacology, 2003)

An efficient protocol for genomic DNA extraction fromCitrus species - Yun-Jiang Cheng; Wen-Wu Guo; Hua-Lin Yi; Xiao-Min Pang; Xiuxin Deng (Plant Molecular Biology Reporter, 2003)

Daily changes in components of xanthophyll cycle and antioxidant systems in leaves of rice at different developing stage - Cheng-Wei Yang; Yi-Zhu Chen; Chang-Lian Peng; Duan Jun; Gui-Zhu Lin (Acta Physiologiae Plantarum, 2001)

Characterization of stress-responsive genes, hrcA-grpE-dnaK-dnaJ , from phytopathogenic Xanthomonas campestris - Shu-Fen Weng; Pan-Ming Tai; Cheng-Hwa Yang; Cheng-Der Wu; Wan-Ju Tsai; Juey-Wen Lin; Yi-Hsiung Tseng (Archives of Microbiology, 2001)

A simple method to determine urea concentration using intact Helicobacter pylori and BromoCresol Purple as a pH indicator - Yuh-Ling Lin; Chien-Tsu Chen; Su-Cheng Lin; Cheng Lee; Hsien-Shou Kuo; Chun-Mean Shih; Yuan-Hsun Hsu; Yi-Ping Chin; Err-Cheng Chan (Biotechnology Letters, 2000)